Promiscuous activity of ornithine decarboxylase from Enterobacter hormaechei: An alternative pathway for histamine formation in fermented sausages - Wei He; Binbin Li; Kaidi Hu; Xumei Zhong; Yulin Zhang; Jiamei Yu; Jiaxin Xie; Chengtao Li; Fengqin Li; Lanlan Wu; Shuhong Li; Jianlong Li; et al. (Food Microbiology, 2027)

When observed demand is not enough: Assessing the need for unmet-demand imputation - Aoyong Li; Yi Su; Ning Liu; Zhiyong Cui; Pengxiang Zhao; Yizhe Huang; Mingxiao Li (Journal of Transport Geography, 2026)

Multiscale investigation of the structure, interaction mechanism, and physicochemical properties of α-lactalbumin and soybean lecithin complexes: integrating spectroscopy, molecular dynamics, and density functional theory - Yuanyuan Li; Ning Guan; Haifu Jia; Yougui Cheng; Xiaoyan Pei; Biao Liu; Jingzhou Xiao; Yujun Jiang; Qianyu Zhao; Ling Guo (Food Hydrocolloids, 2026)

Controlling nitrosamine accumulation in dry fermented sausages using Lacticaseibacillus rhamnosus H7: The role of physicochemical drivers and precursor depletion - Ying Yue; Ning Zhao; Bingrui Guo; Jing Lv; Xin Nie; Sufang Zhang; Yingxi Chen; Beiwei Zhu; Shengjie Li; Xinping Lin (Food Microbiology, 2026)

Enhanced oxalate decarboxylase biomanufacturing via multi-level optimization and integrated life cycle assessment - Ning Hou; Haojie Guo; Tao Wang; Dapeng Li; Lixin Li; Xinyue Zhao (Bioresource Technology, 2026)

Association of TRPV3 gene polymorphisms with wool production traits in Zhexi Angora rabbits - Rongrong Li; Bohao Zhao; Ning Shen; Yan Liu; Yang Chen; Xinsheng Wu (Molecular Genetics and Genomics, 2026)

Comprehensive study of the tumor immune microenvironment and the prognostic significance of reticulocalbin-1: a pan-cancer analysis - JiangLi Zhao; XuChen Liu; QingYuan Sun; ShuJie Peng; ZhiWei Xue; JunZhi Liu; Bin Huang; JiWei Wang; Chao Li; Ning Yang; Xinyu Wang (Functional & Integrative Genomics, 2026)

Drainage alters bacterial co-occurrence networks and net nitrogen mineralization rate in peatlands under different forest management regimes - Ning Li; Yunuo Hu; Zhao-lei Qu; Heidi Aaltonen; Marjo Palviainen; Annamari Laurén; Frank Berninger; Xudan Zhu; Anne Ojala; Lin Huang; Hui Sun; Jukka Pumpanen (Agriculture, Ecosystems & Environment, 2026)

The circadian clock proteins PRR modulate root hair development via the RHD6/RSL module in Arabidopsis - Ning Bai; Yan Zhao; Tianmei Wang; Minchen Li; Xiao Han; Milian Yang; Lijuan Zhou; Yajin Ye; Zhiqiang Zhang; Yanru Hu; Kunrong He (Plant Science, 2026)

Double-layer coating for nuts preservation: covalently grafted resveratrol for antioxidant activity and protein-polysaccharide complexes for high barrier properties - Yunze Ma; Jian Li; Rui Zhao; Huajiang Zhang; Zhanhui Geng; Hanyu Li; Yuepeng Wang; Ning Xia; Lina Xu (Food Research International, 2026)

Hydrogeomorphic controls on Holocene peat beds evolution in the Ningshao plain, East China - Mengjiao Yu; Yan Liu; Jinqi Dai; Yongzhi Huang; Ning Zhao; Shihao Liu; Xinquan Zhou; Jing Chen; Maotian Li; Qianli Sun (CATENA, 2026)

Coal-to-gas transition modulates multi-timescale emission variations and urban-rural heterogeneity in winter VOC profiles, reactivity, toxicity, and O3 sensitivity across pre- and in-heating seasons - Zhiyong Li; Zihan Shao; Yarou Zhao; Zimo Guo; Zhi Ning; Lan Chen; Xiaohua Ma; Jinming Liu; Shaofei Kong (Atmospheric Environment, 2026)

Multiple ecological mechanisms drive effects of fertilization and herbivore exclusion on species richness in an alpine grassland community - Wei Zhao; Shaohao Bang; Zhenzhen Pan; Ruibing Wang; Huan Chen; Xiaolong Zhou; Defei Liang; Honglin Li; Ning Chen; Shiting Zhang; Zhengwei Ren (Agriculture, Ecosystems & Environment, 2026)

A phenology-aware organ-specific multi-temporal UAV framework for maize shoot phosphorus uptake estimation and field-scale mapping - Tianli Wang; Yubin Zhang; Bin Li; Yi Zhang; Ruimin Gong; Hongyu Zhao; Maofang Gao; Ning Cao; Yongjun Wang (Computers and Electronics in Agriculture, 2026)

Corrigendum to “Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development” [Theriogenology 2026; 118017] - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Sperm cryopreservation of Sebastes schlegelii and application in large scale seed breeding production - XiaoYang Guo; Yichao Zhang; JinWei Huang; Teng Guo; XueYing Wang; ShiHong Xu; Ning Zhao; Zongzhu Liu; Jun Li; QingHua Liu (Theriogenology, 2026)

Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

PpPRE1 and PpPRE2 mediate gibberellin-induced internode elongation by regulating brassinosteroid biosynthesis in peach - Huanbing Lu; Mengmeng Zhang; Ning Liu; Bo Zhao; Jun Cheng; Bin Tan; Xianbo Zheng; Wei Wang; Xia Ye; Haipeng Zhang; Xiaobei Wang; Zhiqian Li; et al. (Plant Science, 2026)

Two new acylated iridoid glycosides with insulin resistance-improving activity from Scrophularia ningpoensis - Wen-Ying Zhou; Yu-Xin Peng; Bi-Qing Zhao; Hong-Yu Jiang; Xi-Ning Sun; Guang-Yun Su; Li Li; Xiao-Jiang Zhou (Phytochemistry Letters, 2026)

Piezoelectric driven ultralow peroxymonosulfate activation over Co3O4/Bi4O7/BiO2-x for rapid degradation of levofloxacin - Chaoqin Zhao; Yigui Tang; Die Yuan; Ping Ning; Shuangyou Bao; Kai Li (Journal of Environmental Chemical Engineering, 2026)

Magnetic OVs-CoFe2O4/g-C3N4 heterojunction for enhanced tribocatalytic degradation of RhB: Performance and mechanism - Baoxiu Zhao; Ning Chen; Mengfan Li; Chaojun Sun; Tingting Xue; Yulu Xing; Yiran Xue; Songxue Wang; Bingrui Ma; Yizhen Tang (Journal of Environmental Chemical Engineering, 2026)

Functional coupling of sulfide oxidation and biosurfactant production mitigates sulfidogenic corrosion in oilfield produced water - Guangming Zhang; Qiannan Yang; Kairui Zhao; Yanhong Zhao; Siyun Cao; Yufei Chang; Fuxin Zhou; Hang Li; Kexin Wang; Xudong Su; Ning Mao; Shiwei Wang; et al. (Journal of Environmental Chemical Engineering, 2026)

Antibacterial activity and multi-target mechanism of naringenin against Alicyclobacillus acidoterrestris and its application in apple juice - Yi Zhang; Ning Zhao; Bin Hu; Yanan Zhang; Xiaoru Chen; Dongge Liu; Kaidi Hu; Qin Li; Jianlong Li; Aiping Liu; Shuliang Liu (International Journal of Food Microbiology, 2026)

Ferrihydrite sulfidation transformation reduces the mobilization of coexisting cadmium under anoxic conditions: Insights into the transformation mechanism - Xiaoming Zhao; Yifei Wang; Yu Song; Xu Ma; Ning Chen; Leo Ka Long Cheung; Ayetullah Tunc; Reza Deevsalar; Jinru Lin; Yuanming Pan; Haibo Li (Hydrometallurgy, 2026)

Dynamic evolution mechanism of carbon oxides during Low-Temperature oxidation and an Early-Warning model for the spontaneous combustion risk of lignite - Zhenshuai Sun; Ning Li; Xianliang Meng; Fan Wu; Ruizhi Chu; Jianqiao Zhao; Shuo Li; Ying Feng; Hengbo Hu; Yihao Sun; Shi Yu (Fuel, 2026)

Comparative analysis of composition, volatile compounds, and bioactivities in pomace skins and seeds from different wine grape varieties prior to and following fermentation - Juan-Juan Zhu; Jia-Ning Yan; Xiao-Fang Li; Hao-Hao Zhao; Wen-Qi Wang; Hai-Jun Ma (Food Chemistry, 2026)

Maternal exposure to particulate matter during pregnancy and offspring liver function - Ziyi Zhou; Bin Sun; Yudiyang Ma; Ning Chen; Haibo Li; Wenpu Shao; Rui Tang; Lei Zheng; Meiqi Xing; Xinru Zhao; Yibing Zhu; Yaohua Tian (Environmental Pollution, 2026)

Perchlorate exposure in Chinese primary children: Levels, potential health risks, and association with sexual development - Yang Xiang; Cui-Lan Bai; Ting-Ting Xu; Yu-Ling Luan; Liang-Ying Liu; Li-Ning Zhao; Ying Guo (Environmental Pollution, 2026)

Divergent effects of fertilization and grazing exclusion on species diversity in alpine grasslands - Zhengwei Ren; Wei Zhao; Zhenzhen Pan; Shaohao Bang; Ruibing Wang; Huan Chen; Defei Liang; Honglin Li; Dexiecuo Ai; Renyi Zhang; Ning Chen; Xiaolong Zhou (Ecological Engineering, 2026)

Accelerating CO2-to-carbonate conversion for electrochemical water softening via a carbonic anhydrase-inspired gas diffusion electrode - Yinghao Xu; Qi Zhang; Congcong Ni; JinFeng Zhao; Li Gao; Xin Huang; Ning Deng (Chemical Engineering Journal, 2026)

Engineering inverse CeO2/Cu interfaces for efficient hydrogen production from methanol steam reforming - Shengchao Chen; Jiayi Zhang; Ruihan Wang; Jiawei Guo; Jinhai Yang; Yan Song; Linda Zhang; Xin Huang; Tengfei Gao; Qiang Wang; Hao Li; Ning Zhao (Chemical Engineering Journal, 2026)

Brown carbon optical emissions from residential coal combustion in china: Dominance of solvent-insoluble components - Fan Li; Qiaoqiao Wang; Nan Ma; Zechao Hu; Xiaocong Zhao; Ning Yang; Zheng Yang; Guangjin Liu; Yuanwei Zhong; Jiangchuan Tao; Juan Hong; Yaqing Zhou; et al. (Atmospheric Research, 2026)

Impacts of stratospheric intrusion on near-surface O3 variations in the Sichuan basin, Southwest China during the last 10 years - Lin Wu; Tianliang Zhao; Guicai Ning; Yuxiang Jin; Yuehan Luo; Kai Yang; Zhikuan Li; Yuqing Zhang (Atmospheric Environment, 2026)

Multi-dimensional coupling framework for soil salinity assessment: Revealing spatiotemporal interactions among soil, environment, and cotton growth - Bowei Xu; Jiajie Yang; Rumeng Zhao; Jilian Li; Xinzhu Ning; Fuguang Li; Hai Lin; Zuoren Yang; Liqiang Fan (Agricultural Systems, 2026)

Salinity reduces cadmium bioavailability and toxicity in the Oryzias melastigma: Evidence from fish exposure and cell-based ion-competition assays - Zhongdian Dong; Jinghua Wang; Haozhong Tian; Jiahao Gao; Yue Liu; Nengneng Ding; Yiqing Yuan; Guohua Zhu; Xiaomin Zhao; Zailiang Li; Ning Zhang; Yanping Zhang; et al. (Marine Pollution Bulletin, 2026)

Methylome and transcriptome profiles reveal the importance of glycometabolism in thermal plasticity of large yellow croaker - Yanfei Yang; Yichen Li; Yidi Wu; Baohua Chen; Ji Zhao; Qiaozhen Ke; Weiqiang Zheng; Yun Li; Tao Zhou; Peng Xu; Ning Li (Aquaculture, 2026)

A critical review on persulfate-based catalytic systems: Deactivation mechanisms and regulation strategies - Ning Li; Yukun Hao; Lan Liang; Shouqiang Wan; Jianhui Zhao; Beibei Yan; Guanyi Chen (Water Research, 2026)

Exogenous microbial metabolites improve rhizosphere microecology and reduce Fusarium abundance to control root rot in wolfberry - Dong Zhao; Tingting Xu; Hongyu Chen; Shuo Shen; Shuqun Deng; Junlong Feng; Chenxu Gao; Jiali Ning; Zhuofei Zhang; Zhongyang Xu; Wei Li; Yang Zhang (Rhizosphere, 2026)

Involvement of sucrose transporter SUT4 in regulating tomato yield and fruit quality - Yufei Liang; Zhaoyuan Lian; Wenjing Dong; Shuyu Qi; Jingyi Zhao; Wanxing Hu; Ning Li; Haijun Gong (Plant Science, 2026)

Permeability estimation based on acoustic wave velocity tests in layered fracture-filling hydrate-bearing clay silty sediments - Zhun Zhang; Wengao Zhao; Qingtao Bu; Zikun Li; Yapeng Zhao; Bin Fang; Wanjun Lu; Fulong Ning (Fuel, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Hypoxia-induced downregulation of cAMP drives Ganoderic acid biosynthesis and restricts biofilm development in Ganoderma lucidum - Siyi Wang; Li Tian; Faqin Li; Qin Wang; Yanan Tan; Yanda Ning; Xuewei Cao; Yueqian Liu; Jiaolei Shangguan; Huihui Li; Ailiang Jiang; Mingwen Zhao; et al. (Food Research International, 2026)

Fe2+ alters carbon and nitrogen metabolic networks in a composite microbial consortium: Metagenomic insights into the shift from denitrification to DNRA - Lin Zhang; Bowei Zhao; Xiao Zhang; Yuan Li; Haibo Li; Shuying Yuan; Haoxiang Ning; Bingcheng Lv; Le Li; Xiaojun Fan; Xiuping Yue (Environmental Research, 2026)

Sex-specific associations between prenatal PM2.5 exposure and reproductive hormone levels in offspring aged 1–2 years: A prospective birth cohort study - Wenpu Shao; Shengli Jiang; Yudiyang Ma; Ning Chen; Zhiping Niu; Rui Tang; Meiqi Xing; Lei Zheng; Xinru Zhao; Bin Sun; Haibo Li; Ziyi Zhou; et al. (Environmental Research, 2026)

Charge-programmable carbon dots tailored by amino acid pKa spectrum for spatiotemporally controlled siRNA delivery and antiviral protection in plants - Fang Wang; Xueyang Ji; Yan Zhao; Jingyan Hu; Ziqi Zhang; Jinxuan Wang; Kailin Su; Jingyan Jia; Ao Zhou; Ning Li; Ying Song; Changjun Zhang; et al. (Chemical Engineering Journal, 2026)

Impact of intraguild predation between Neoseiulus barkeri and Lasioseius scapulatus on thrips control in cowpea - Yuanming Chi; Chen Yu; Yilin Zhu; Kai Shu; Ying Gong; Huiyin Yang; Ning Nong; Zihan Zhao; Mingyue Feng; Maoqing Li; Yanyu Chen; Xinzheng Huang; et al. (Journal of Pest Science, 2026)

Machine learning-empowered spatial environmental health risk management: Causal inference for sustainable urban agglomeration health equity - Zeduo Zou; Yu Liao; Ye Wang; Ruilin Meng; Yue Gao; Dejian Zhao; Ni Xiao; Ning Liang; Baoyu Chen; Xiuyan Zhao; Xiong He; Hao Yao; et al. (Applied Geography, 2026)

Genetic selection response and genomic basis of resistance to Cryptocaryon irritans in large yellow croaker (Larimichthys crocea) - Yin Li; Ji Zhao; Jiaying Wang; Qiaozhen Ke; Hongshu Chi; Sijing Chen; Yujia Chen; Huasong Weng; Fei Pu; Ning Li; José M. Yáñez; Tao Zhou; et al. (Marine Life Science & Technology, 2026)

Nat10-mediated ac4C modification sustains macrophage proliferation and mitigates colitis progression via Mcm2 stabilization - Jinsong Wang; Tao Liu; Jiachen Zhao; Zhiqing Diao; Fuhong Fan; Demeng Qin; Yu Zhang; Xindi Wang; Ning Jiang; Chenbo Ding; Hua-Bing Li; Yuzhang Wu (Science China Life Sciences, 2026)

Energy evolution and failure property of granite from pre- to post-peak under high-temperature and cyclic stress coupled conditions in deeply buried railway tunnels - Houyu Wang; Zaobao Liu; Liang Zhao; Ming Wu; Hongyuan Zhou; Zhenyong Bao; Yudong Duan; Ning Li (Transportation Geotechnics, 2026)

Evolutionary auxiliary optimization for feature selection with multi-indicator task construction - Weizheng Zhang; Yiwei Zhao; Haotian Ning; Weiwei Zhang; Yanting Li; Yanpei Liu; Chuang Han (Swarm and Evolutionary Computation, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

The soybean gene GmSP1L-8 improves salt tolerance through the enhancement of the ROS scavenging system - Hui-Bing Mou; Shuang Jiao; Xiang-Min Zheng; Xiao-Hong Liu; Zhuo Li; Jia-Ning Xun; Ke Zhao; Xianzhong Feng; Hong Zhai; Xi Bai (Plant Science, 2026)

In situ nanoencapsulation of curcumin in egg yolk low-density lipoprotein gels: Calcium-regulated protein network restructuring and stability enhancement - Jian Li; Qingruo Zhao; Xian Fang; Peiyao Si; Huajiang Zhang; Lina Xu; Ying Ma; Ning Xia; Hanyu Li; Mohamed Ghamry; Ahmed M. Rayan (Food Chemistry, 2026)

Effect of psyllium husk gel addition on the quality of whole wheat steamed bread: insights from rheological properties and protein structural changes - Yize Zhao; Nan Wang; Chengwu Cai; Jiayi Ding; Mingqi Huang; Jingting Zhang; Zhenni Li; Ning Li (Food Chemistry, 2026)

Metagenomic and metabolomic integration reveals microbial mechanisms underlying low-temperature-driven flavor diversity in backslopped wheat sourdough - Yuan Zheng; Linyi Lei; Yixue Ou; Qin Li; Kaidi Hu; Ning Zhao; Jianlong Li; Shuliang Liu; Shujuan Chen; Aiping Liu (Food Bioscience, 2026)

The function of stearoyl-CoA desaturase in unsaturated fatty acid biosynthesis and cold tolerance in Haliotis discus hannai - Jie Qi; Wentong Hao; Ming Li; Hailin Zhao; Shiqing Sun; Lixin Feng; Ning Kong; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2026)

DPA-MSCL: A multi-scale supervised contrastive learning method based on dynamic prototype alignment for lithology identification - Xianshan Li; Saiwei Sun; Yao Wang; Ning Shi; Pengwei Zhang; Chao Han; Yurun Shao; Hongjia Ren; Fangfang Pan; Fengda Zhao (Earth Science Informatics, 2026)

Enhancing landslide susceptibility assessment through ensemble learning and PCoA - Ming Chang; Boju Zhao; Yongchao Su; Ning Li; Daolong Yin; Xianxi Zhou; Liang Chen (Bulletin of Engineering Geology and the Environment, 2026)

Improvement of cannabichromenic acid synthase activity and construction of recombinant yeast strain - Laifeng Wang; Jian Chi; Danqi Jiang; Youyin Zhao; Yuan Tian; Ning Cao; Zhijiang Li; Baochang Gao; Lingyan Dai (Archives of Microbiology, 2026)

Isorhamnetin ameliorates active ulcerative colitis potentially involving the Nrf2-PTGS2 axis: an integrative study from clinical evidence mining to in vivo validation - Zhenjia Fan; Luqing Zhao; Ning Ding; Yichong Wang; Danyan Li; Shengsheng Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Ulcerative colitis (UC) is a worldwide health issue with limited therapies. Traditional Chinese Medicine (TCM) shows potential, but lacks systematic efficacy evaluation and detailed mechanistic explanations. This study aims to evaluate the efficacy of TCM for active UC and explore its mechanisms. A meta-analysis of RCTs was conducted to assess TCM efficacy in active UC, and treatment efficacy was ranked. Core Chinese herbs were identified via association rule analysis. Network pharmacology and molecular docking predicted active components, targets, and pathways. Efficacy of the key component was validated in active UC mice. 17 studies (1,598 patients) showed TCM significantly improved active UC (SMD -1.73, 95%CI -2.21 to -1.25). Eight core Chinese herbs were identified. Network pharmacology revealed 76 overlapping targets. Isorhamnetin (Iso) showed strong binding to PTGS2 (binding energy: -9.34 kcal/mol) and Nrf2 (binding energy: -9.16 kcal/mol). In vivo, Iso dose-dependently alleviated disease symptoms, pathological damage, and spleen index in UC mice. TCM could ameliorate active UC. The key active component Iso shows therapeutic effects, with mechanisms potentially involving the Nrf2-PTGS2 axis and immune-inflammatory pathways. The findings offer some insight into the scientific basis of TCM in treating UC and predict that Iso may be a candidate for further mechanistic and clinical investigation.

From reagents to feedstocks: reprogramming heteroatom-containing molecules in modern organic synthesis - Jixiang Ni; Mohd. Aamir Bin Riyaz; Zhenyu An; Yang Lu; Sajid Muhammad; Yanguo Li; Ning Xi; Yufen Zhao (Molecular Diversity, 2026)

A new flavonol glycoside isolated from the stems and leaves of Astragalus membranaceus - Jia-Xin Zhao; Yun Zang; Pei Li; Jia-Ning Zhang; Si-Qi Yang; Hui-Feng Li; Yan Wang; Jin-Yan Tan; Ying-Li Wang; Yan-Gang Cheng (Natural Product Research, 2026)

PLC-Guided Vibration Measurement and Condition-Aware State Characterization of Quay Crane Hoisting Gearboxes Under Non-Stationary Field Operation - Weiguo Zhang; Mingfei Ai; Xiangkun Zeng; Meizhen Li; Dongsheng Wang; Yang Shen; Ning Zhao (Journal of Marine Science and Engineering, 2026)
Field vibration measurements of quay-crane hoisting gearboxes are difficult to interpret because the measured response is generated under short, load-dependent cycles rather than stationary excitation. This study develops a PLC-guided method for constructing condition-tagged steady-state vibration samples from non-stationary field measurements. Multi-rate records are aligned on a common time basis; work cycles and action stages are identified from load and hoist-speed information; steady PLC candidates are selected using operating-context and local-steadiness criteria; and one-second vibration segments are fine-screened within the corresponding search intervals. The accepted segments are stored in a quality-controlled feature table and characterized by acceleration RMS, 10–1000 Hz velocity RMS, kurtosis, peak-to-peak acceleration, dominant frequency, and spectral entropy. Field data from four gearboxes yielded 1140 steady-state segments and 8912 quality-controlled segment-channel records. Stepwise CV analysis showed that action-only grouping reduced the coefficient of variation from 0.692 to 0.658, while full machine–action–channel grouping reduced it to 0.351, corresponding to a 49.35% reduction. Median acceleration RMS ranged from 0.494 to 4.805 m/s2, and 10–1000 Hz velocity RMS ranged from 0.317 to 1.512 mm/s. The method provides a traceable basis for condition-aware baseline modelling and trend analysis without making unsupported fault-diagnostic claims.

Policy and science at a crossroads: integrating new approach methodologies (NAMs) into anticancer drug testing frameworks - Guo Zhao; Jiawei Zhou; Shuhang Wang; Ning Li (Science Bulletin, 2026)

Dolabellane diterpenes with angiogenic activity from the soft coral Clavularia koellikeri collected in the South China sea - Zhongyu Lu; Ning Lv; Congcong Zhao; Xin Zhou; Xiao Han; Guoqiang Li (Phytochemistry, 2026)

Nanobubbles alleviate iron-mediated cell death in algae-bacteria symbiotic systems under sulfamethoxazole stress: Insights into electron transfer and ferrikinetics - Chi Zhang; Qirui Hao; Tong Zhang; Tianyi Sun; Ning Hou; Xinyue Zhao; Dapeng Li (Journal of Hazardous Materials, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

Regulatory roles of rpoS and rpoE on the response profiles of Salmonella enterica serovar Typhimurium to acid and osmosis sequential cross-stress treatment - Ning Zhao; Xianyu Xiang; Dongge Liu; Kang Zhou; Kaidi Hu; Qin Li; Jianlong Li; Aiping Liu; Yong Yang; Xiaolin Ao; Shuliang Liu (Food Research International, 2026)

Construction of a carbon-conserving pathway for D-allulose production by regulating the co-utilization of acetate and glucose in engineered Escherichia coli - Longyan Zhao; Wanting Jia; Tanxiang Huang; Lei Hu; Ning Li; Xiyao Cheng; Chen Liang; Jidong Liu (Food Bioscience, 2026)

1D-confined gravity-driven liquid template strategy to construct high thiophene-S doping gully-shaped carbon nanorods for efficient sodium storage - Ming Zhao; Wenlei Jia; Huihui Zhao; Chao Zhang; Miaomiao Li; Jing Wang; Tengfei Wei; Chuanxiang Zhang; Ning Fu (Chemical Engineering Journal, 2026)

Global divergent responses of soil heterotrophic respiration to nitrogen deposition - Peng Guo; Mengyu Miao; Han Zhao; Tian Zuo; Ning Wang; Luna Yan; Zhaowei Li; Tianming Li (CATENA, 2026)

Antimicrobial Mechanism of Temporin L Peptide Against Bacillus cereus from Fermented Sausage - Tiantian Yu; Fangyu Wang; Ibrahim A. Bakry; Qian Li; Tiange Li; Guangshan Zhao; Yongxia Cheng; Peijun Zhao; Mei Hu; Lianjun Song; Bangbang Zhao; Xianqing Huang; et al. (Probiotics and Antimicrobial Proteins, 2026)

The vertical distribution and redox-dependent mobilization of arsenic in naturally contaminated karstic paddy soils from southwestern China - Qi Gao; Manman Zhao; Ying Wang; Hang Li; Zengping Ning; Jing Sun; Chengshuai Liu; Yizhang Liu (Applied Geochemistry, 2026)

Submarine natural hydrogen resources and potential occurrences in the South China Sea continental margin - Cuimei Zhang; Sanzhong Li; Gianreto Manatschal; Zhiqiang Feng; Nick Kusznir; Qi Li; Jiangyang Zhang; Zhongxian Zhao; Pauline Chenin; Ning Qiu (Science China Earth Sciences, 2026)

Rational design of low-risk and high-efficiency β-triketone herbicide alternatives via integrative computational toxicology and NGBoost modeling - Yuanquan Chi; GuoFeng Zu; Hongyu Ma; Li Tao; Yuhua Ji; Xingmin Zhao; Hongbin Wang; Ning Huang; Chenyu Zhao; Luze Yang (Molecular Diversity, 2026)

Research progress on the fermentation characterization of non- Saccharomyces yeasts in fruit wines: a review - Rong Zhang; Xiaoyan Hou; Qigao Fan; Kaidi Hu; Lunqiong Hou; Ning Kang; Ziyuan Ou; Ning Zhao; Qin Li; Aiping Liu; Yong Yang; Guoquan Han; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Genetic differentiation and machine learning based SNP marker development in the Cryptocaryon irritans resistant large yellow croaker (Larimichthys crocea) strain - Yin Li; Ji Zhao; Ningyuan Ding; Changliang Zhang; Ning Li; Tao Zhou; Peng Xu (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Fe3O4-doped DCD-modified PAN-based nanofiber mat with synergistic photo-Fenton catalytic evaporation performance for multifaceted water treatment - Yifan Niu; Wenxin Wang; Mingzhe Zhao; Ning Wang; Martin Jensen; Na Han; Xianfeng Li (Journal of Environmental Chemical Engineering, 2026)

Smartphone-integrated ratiometric fluorescent probe based on G-CDs@Eu-MOFs for on-site detection of phosphate ions - Yourong Zhao; Yuhong Xie; Yiying Wang; Hongda Li; Daojiang Gao; Zhanglei Ning (Journal of Environmental Chemical Engineering, 2026)

First mapping of subsurface soil temperature profiles by integrating diurnal cycles of microwave and thermal infrared observations - Dabiao Chen; Huazhu Xue; Tianjie Zhao; Yuyang Xiong; Ning Li; Jingyao Zheng; Yipeng Cao; Yu Bai; Songbo Qu; Ling Yao; Tang Liu; Chi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Polystyrene nanoplastics promote adipogenesis by stimulating nuclear translocation of PPARγ - Yuchen Zheng; Zijia Liu; Zijie Zhao; Chao Sheng; Wenzhuo Li; Duo Tang; Yunlu Ning; Renhang Zhou; Ao Li; Zhixiang Zhou (Food and Chemical Toxicology, 2026)

DeepLrn-Source: Deep learning powered landslide source identification - Lu-Yu Ju; Ze-Ning Zhao; Shi-Hao Xiao; Yuan-En Pang; Jian He; Yun-Hong Lv; Ruo-Chen Jiang; Xin He; Li-Min Zhang (Engineering Geology, 2026)

Nanocellulose-reinforced deep eutectic solvent-based smart hydrogel sensor for adaptive window regulation and machine learning-assisted low-temperature motion monitoring - Zhenchun Li; Yucong Sun; Jiarui Shen; Rongfeng Ge; Jieli Hua; Zhiyuan Zhao; Ning Li; Yunqi Peng; Jiaqi Hou; Hong Zhang; Lei Wang (Chemical Engineering Journal, 2026)

The Dorsal CA2 to Ventral CA1 Circuit Contributes to Spatial and Context-Dependent Memories - Ning Li; Bingqing Zhao; Xiaowen Shen; Hua He; Jianxiang Zhou; Jing Zhang; Lin Xu; Xiaochun Chen; Chun Xu (Neuroscience Bulletin, 2026)

Insights into the size effect of Fe3O4 in Fe/AC for Hg0 removal and the corresponding mechanism - Jiawen Tan; Yuan Qin; Jiayi Piao; Zhao Li; Fei Wang; Ping Ning; Kai Li; Yixing Ma; Xin Sun (ENGINEERING Environment, 2026)

Novel rockburst evaluation model based on a KPCA-IF-BorderlineSMOTE-ENN preprocessing framework - Jian-Hua Hu; Zhi-Hao Zhong; Zhi Yu; Jia-Ning Li; Yi-Long Zhao (Computational Geosciences, 2026)

Geospatial Distribution and Autocorrelation of Heavy Metals in the Upper Yishu River Basin, Huai River Tributary: Assessing Impacts of Geological Settings and Human Activities - Ning Liu; Changyan Tang; Xiuwen Zhang; Chuang Zhao; Xiyao Li; Sanzhong Li; Fang Wan; Ming Liu; Haiyin Fan; Yuhua Gao; Yu Wang (Journal of Ocean University of China, 2026)

NOTCH3 signal activation by its extracellular domain accumulation in an iPSC line newly established from a CADASIL patient - Ruihua Sun; Zhenxiang Zhao; Ningning Che; Ning Liu; Xiaoyi Ji; Anqi Li; Fengyu Wang; Junkui Shang; Jiewen Zhang (Human Cell, 2026)

In-depth Characterization of Photo-Stressed Antibody–Drug Conjugates by Mass Spectrometry - Xiao Pan; Yimeng Zhao; Shukun Luo; Joshua Bulos; Jieqiang Zhong; Yuetian Yan; Zhijie Wu; Yue Su; Sisi Zhang; Shunhai Wang; Hui Xiao; Wenhua Wang; et al. (The AAPS Journal, 2026)

Atomic coordination engineering and pollutants synergy co-modulate self-motivated single-atom catalysis with zero-oxidant addition for sustainable water purification - Qingbai Tian; Yanbiao Liu; Qian Li; Xuemin Zhao; Yanwei Li; Ning Li; Yanshan Wang; Yan Shi; Xing Xu (Science Bulletin, 2026)

Phage-based suppression of plasmid-mediated antibiotic resistance: A promising approach for antimicrobial stewardship - Yan-Zi Wang; Hu Li; Bei-Ning Xue; Xiao-Xu Zhao; Yu Rao; Sha Zhao; Kiandro J. Fortuna; Mao Ye; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Division of labor in a synthetic consortium enables high-efficiency waxy oil biodegradation: Interfacial access provided by Bacillus unlocks deep degradation by Pseudomonas - Guangming Zhang; Yong Yang; Yanhong Zhao; Xiangqian Zhu; Wan Lei; Qiannan Yang; Haichen Li; Wei Cheng; Ning Mao; Yanmei Sun; Shiwei Wang (Journal of Hazardous Materials, 2026)

Spatial variability of groundwater nitrate in the loess area of Tongchuan City, China: New insights from farmland leaching quantification - Wei Zhao; Peiyue Li; Tiantian Wang; Fangqiang Sun; Fang Zhang; Jia Yang; Jing Ning; Misbah Fida (Journal of Environmental Sciences, 2026)

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

A metabolomics approach to fingerprint the heat-induced alterations in milk and identify potential thermal biomarkers - Ashikur Rahman; Ning Li; Meiqing Chen; Sanusi Shamsudeen Nassarawa; Xiaowei Zhao; Shengguo Zhao; Nan Zheng; Yangdong Zhang; Jiaqi Wang (Food Research International, 2026)

A novel 3D-printed flexible electrode with rGO/MWCNTs ink for capsaicin detection in chilli peppers - Jiachen Zhao; Huilin Hu; Chao Wang; Yingting Li; Xueyu Jiang; Ming Zhang; Fangkai Han; Ning Yang; Xiaodan Liu; Jiahua Wang; Yingli Wang; Shuo Duan; et al. (Food Chemistry, 2026)

Integrated metabolomic and transcriptomic analyses decipher anthocyanin biosynthesis and regulatory mechanisms in novel purple Chimonobambusa purpurea shoots - Hongli Li; Siyao Li; Zhendong Yan; Siyi Liu; Shuliang Liu; Yong Yang; Likou Zou; Aiping Liu; Shujuan Chen; Ning Zhao; Zhongquan Huang; Xiaolin Ao (Food Bioscience, 2026)

From deterministic to stochastic: Reservoir operations alter phytoplankton assembly processes by mediating nutrient and hydrological regimes - Daqing Zeng; Ning Liao; Linglei Zhang; Min Chen; Jia Li; Yong Li; Hongwei Wang; Yang Zhao (Environmental Research, 2026)

Chemical conformance control technologies in CO2-enhanced oil recovery: State-of-the-art, challenges, and prospects - Wanlei Geng; Yueting Zhang; Feihong Li; Jianpeng Cui; Ning Yan; Yu Si; Caili Dai; Guang Zhao (Chemical Engineering Journal, 2026)

Accumulation pattern, source apportionment and risk assessment of soil heavy metals across diverse land use types: Insights from the northern foothills of Qinling mountains, China - Bingyao Huo; Yanjun Shen; Yibing Ning; Wei Shen; Penghui Ma; Zhijie Jia; Luqing Zhao; Junyan Zhao; Xing Chen; Tao Ding; Sirui Li; Jianbing Peng (CATENA, 2026)

Anti-asthmatic effects and ingredient annotation of the active fraction from Ganoderma lucidum - Ning Li; Qian He; Cunwu W. Chen; Qun Zhao; Yanfei F. He (Journal of Natural Medicines, 2026)

ZNRF2-mediated CD-M6PR degradation and lysosomal dysfunction aggravate cellular senescence and aging - Tingting Zhao; Weitong Xu; Fangfang Wang; Honghan Chen; Hui Gong; Yu Yang; Ning Huang; Ming Yang; Jian Zhang; Chuhui Gong; Xiaoli Huang; Ying Li; et al. (GeroScience, 2026)

New nor-tirucallane triterpenoid with antitumor activity from Ailanthus altissima (mill.) swingle - Can Liu; Jun-ling Guo; Shuo-yu Zhao; Ning-ning Shi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Three phloridzin derivatives capable of anti-oxidant from Malus toringoides (Rehd) Hughes - Li Liu; Wei-wei Tian; Ying-chao Wang; Can Ren; Dong-mei Yu; Jian-bo Wang; Jun-ning Zhao; Hua Hua (Natural Product Research, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Realization of elastic Weyl semimetal phases with skyrmion spin textures - Yuang Pan; Liang Si; Miao Yang; Ning Han; Li Zhang; Qiaolu Chen; Rui Zhao; Fujia Chen; Yudong Ren; Wenhao Li; Yuze Hu; Mingyu Tong; et al. (Science Bulletin, 2026)

Efficient silver leaching from end-of-life photovoltaic panels via a catalyst-free peroxymonosulfate process - Ning Li; Yifan Wang; Aofan Wang; Yanghao Wang; Fuxing Yan; Jianhui Zhao; Beibei Yan; Guanyi Chen (Resources, Conservation and Recycling, 2026)

Integrative metabolomics and machine learning reveal the toxic mechanisms of elaidic acid in polycystic ovary syndrome - Yating Xu; Li Ning; Ruyue Wang; Hua Ma; Hongting Zhao; Yu Si; Xiu Li; Qingling Ren (Reproductive Toxicology, 2026)

Phase separation of the redox sensor RCD1 mediates differential ROS signals to regulate plant growth and stress responses - Jingjing Xing; Kaiwen Li; Wenwen Duan; Zhikun Duan; Yu Zhang; Aiyu Guo; Suting Wang; Ning Ding; Yaling Zou; Xiaobin Wei; Xiaoliang Zhao; Junli Zhang; et al. (Molecular Plant, 2026)

Direct upcycling of Mn-rich residues into γ-MnOOH for efficient Alkaline OER - Wenting Jia; Lin Guo; Zhao Yu; Zhiqiang Li; Pengge Ning; Hongbin Cao (Journal of Environmental Management, 2026)

Effect of densification on dimensional stability and water absorption behavior of pine - Ning Jiang; Xintao Zhao; Qingchuan Lu; Emily Treacher; Alberto Leonardi; Xuejiao Li; Rui Li; Zhongsen Zhang; Thomas James Marrow (Journal of Cleaner Production, 2026)

In-situ construction of multi-site Co/Co-N-O porous carbons for plasma-catalytic toluene degradation - Chao Cao; Yixin Yang; Guangfei Qu; Rui Xu; Chenyang Zhao; Ping Ning; Junyan Li (Journal of Environmental Chemical Engineering, 2026)

High-CH4-selectivity CO2 photoreduction enabled by in-situ constructed S-scheme Cs2CuCl4/NiAl-LDH heterojunction - Hai-bing Zhao; Yue Shu; Sheng-ning Zeng; Wen-rong Ouyang; Duo-fu Li; Hong Zhong; Wei Huang; Yan Sui (Journal of Environmental Chemical Engineering, 2026)

Green recyclable resin-supported sulfur ionic liquid for efficient CO2 cycloaddition to cyclic carbonates - Ju Fang; Guoying Li; Xin Fang; Shilong Guo; Xinran Zhao; Tian-Xing Zhang; Ning Zhu; Qingxiang Guo (Journal of Environmental Management, 2026)

Biodegradable microplastics-induced free-living nitrogen fixation enhancement and diazotrophic community differentiation in soils - Yujuan Han; Peixin Gao; Jiping Song; Yanning Li; Xiao Wang; Ning Yang; Xu Zhao; Bo Liu; Chuankun Zhang; Ran Li; Dan Wen; Ying Teng (Journal of Environmental Management, 2026)

Bioaccessibility of phenolics and anti-inflammatory effects during in vitro simulated digestion of enzymatically broken bee-collected pollen - Keju Li; Jiaqi Zhao; Ruowen Wang; Jingze Cao; Qiuning Wang; Quanquan Liu; Wenjie Yu; Xiali Guo; Jinwang Li; Fangjian Ning; Liping Luo (Food Chemistry, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

A LiF-rich and Ag-embedded dual-artificial solid-electrolyte interphase for stable Li metal anodes - Xun-Lu Li; Jian Bao; Wenyu Zhao; Chong-Yu Du; Rui-Jie Luo; Cui Ma; Jie Zeng; Xuan Xu; Zhe Qian; Zhe Mei; Xinyang Yue; Yong-Ning Zhou (Chemical Engineering Journal, 2026)

Multifunctional conductive hydrogel based on carboxymethyl cellulose/oxidized sodium alginate for machine learning-guided sports training - Zhenchun Li; Rongfeng Ge; Ning Li; Jiaqi Hou; Zhiyuan Zhao; Jieli Hua; Chuang Du; Lei Wang (Carbohydrate Polymers, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

Fertilization and herbivore exclusion promote more deterministic processes in plant community assembly on the Qinghai–Tibet Plateau - Wei Zhao; Shaohao Bang; Zhenzhen Pan; Ruibing Wang; Huan Chen; Dexiecuo Ai; Xiaolong Zhou; Honglin Li; Ning Chen; Shiting Zhang; Zhengwei Ren (Oecologia, 2026)

Tire Wear Particles' Environmental Distribution and Potential Threats to Human Health - Xinjie Li; Yingxia Li; Tianliang Zhao; Siyan Li; Jiangyan Yang; Yanbin Luo; Fanxiang Meng; Ning Liao; Yuxin Hu; Xiangzhi Li (Bulletin of Environmental Contamination and Toxicology, 2026)

Macro-mesoscopic deterioration characteristics of MICP-improved strongly weathered phyllite under wetting-drying cycles - Yuhang Zhao; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Lin Ning; Yang Li (Bulletin of Engineering Geology and the Environment, 2026)

Altered Oceanic Crust Source for the Alkaline Rocks with Superchondritic Nb/Ta Ratios Due to the Steep Subduction - Xu Zhao; Ning-Bo Li; He-Cai Niu; Shu-Cheng Tan (Journal of Earth Science, 2026)

Predatory performances and adaptive strategies of Eocanthecona furcellata (Hemiptera: Pentatomidae) to the larvae of Phauda flammans (Lepidoptera: Phaudidae) - Jian-Zhong Ning; Da-Xing Lu; Xiong Zhao He; Xiao-Yun Wang; Kai Lin; Jun Li; Xia-Lin Zheng (Applied Animal Behaviour Science, 2026)

Modeling and experimental validation of crack-induced bottom-side erosion effects in buried pipelines - Yan-Ning Wang; Tai-Kai Li; Jing-Rui Peng; Xin-Hao Min; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

The miR-140-5p/BMP2 axis mediates T-2 toxin-related injury in both fetal and adult chondrocytes - Bingyu Sun; Yiting Zhao; Fuyuan Li; Ning Zou (Toxicon, 2026)

In vivo CAR-T: a paradigm shift in adoptive cell therapy from bench to beside - Yuanting Cai; Huilei Miao; Yuning Wang; Jiatong Ding; Peiwen Ma; Xiaosong Zhong; Yue Bai; Hengjia Tu; Zhongwei Xu; Guo Zhao; Zhangqiang Xiang; Shuhang Wang; et al. (Science Bulletin, 2026)

Natural forces and human impacts on Holocene peat layers in the lower Yangtze: from initiation to degradation - Yan Liu; Mengjiao Yu; Jinqi Dai; Yongzhi Huang; Haixian Xiong; Ning Zhao; Shihao Liu; Jing Chen; Maotian Li; Qianli Sun (Quaternary Science Reviews, 2026)

Magnetic extraction of highly polar pesticides: Method optimization and mechanism - Zhuangzhuang Shi; Huiling Shi; Ning An; Jinwang Li; Guoping Zhao; Xiaoxu Zhang; Xuefeng Yin (Food Chemistry, 2026)

Conservation mulching with plastic film in maize field of arid irrigation region: Agronomic performance, economic, and environmental effects - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Xiao-Yu Lu; Ying Zhu; Meng Hao; Ning Wang; Meng-Ying Li; Xiao-Feng Zhang; Hong-Yan Tao; You-Cai Xiong (Field Crops Research, 2026)

High-performance fiber-based aerogel evaporator for solar desalination and wastewater purification - Yan Liang; Siqi Wu; Yujie Zhao; Ning Liu; Rong Tian; Jianbin Zhang; Yanhua Liu; Dianming Li; Libang Feng (Desalination, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Nanoplatform-mediated PRMT3 inhibition synergizes cuproptosis and radiotherapy to remodel the NSCLC immune microenvironment - Tianle Zhou; Haoyang Du; Su Zhao; Gen Li; Siyu Wang; Sikai Wang; Jinfeng Ning; Manjie Zhang; Hang Yin (Chemical Engineering Journal, 2026)

Carbon quantum dots as charge bridges: Photogenerated electrons flow alter microbial interactions and electron transfer networks in constructed wetlands - Yibo Shi; Yunan Wang; Shutong Li; Xinyu Zhang; Lixin Li; Ning Hou; Qirui Hao; Dapeng Li; Xinyue Zhao (Bioresource Technology, 2026)

Valorization of lignin-rich biorefinery residues to solution-stable calcium-chelated fertilizer for improved root development and nutrient efficiency - Wenhui Li; Guanhua Wang; Yuze Zhao; Baotao Li; Ranran Yang; Wenjie Sui; Dongmin Li; Ning Wang; Chuanling Si (Biomass and Bioenergy, 2026)

Nr4a2, A Key Factor Controlling the Development and Functional Maintenance of Forebrain Car3 Neurons - Yun-Chao Tao; Li Zhao; Qiong Zhang; Xi-Yue Liu; Wei-Tang Liu; Ze-Xuan Li; Ling Hu; Lei Zhang; Jia-Yin Chen; Yu-Qiang Ding; Ning-Ning Song (Neuroscience Bulletin, 2026)
Nr4a2 ( Nurr1 ) is well known to be vital for midbrain dopaminergic neurons. Recent single-cell RNA analyses reveal that Nr4a2 is expressed in lateral cerebral regions, within neurons named L4/L5/L6 IT Car3 . These neurons have attracted intense attention for the molecular mechanisms underlying their development and functions. We classified Car3 neurons into neocortical (Ncx- Car3 ), claustral (CLA- Car3 ), and dorsal endopiriform nucleus (dEn- Car3 ) subpopulations, focusing on the characterization of Ncx- Car3 neurons. These neurons exhibit distinct birthdates and migratory morphologies compared to CLA- and dEn- Car3 neurons, but share a common transcriptomic profile when Nr4a2 is deleted at the embryonic stage or in adulthood. Notably, Nr4a2 misexpression ectopically induces Car3 -enriched genes in vivo . Mice lacking Nr4a2 in Car3 ensembles during the embryonic stage or in adulthood display hyperactivity and reduced anxiety-like behaviors. Therefore, our results demonstrate that Nr4a2 is a key factor in regulating the development and functional maintenance of the forebrain Car3 neurons.

Soybean Hyperspectral Leaf Area Index (LAI) Estimation Based On Soil-vegetation Separation Algorithm and Derivative Spectroscopy - Nai-ning Zhong; Yu-lin Liu; Yi-zheng Zhao; Yi-xuan Mei; Hao-lin Shen; Xin-Zhou Lei; Yu-ning Wu; Juan-li Ju; Youzhen Xiang (Journal of Soil Science and Plant Nutrition, 2026)

Decoding Plant Growth-Promoting Rhizobacteria Volatile Organic Compounds Mediated Growth Promotion in Malus domestica - Nan Zeng; Dandan Wang; Jiahe Pang; Xin Yu Zhao; Chunji Li; Dingcun Zhang; Junliang Ge; Die Zhao; Rutao Gai; Ziqi Cao; Xinyue Bi; Ning Zhang; et al. (Journal of Plant Growth Regulation, 2026)

High-throughput copper speciation with SEC-UV-ICPMS: Insights from Wilson's disease mouse models - Yu Zhang; Xueqing Zhao; Beth Crowell; Heinrich Lob; Sarah Hatsell; Aris N. Economides; Evangelos Pefanis; Jikang Wu; Haibo Qiu; Ning Li (Analytica Chimica Acta, 2026)

Protective effect of ginseng protein on MPTP-induced Parkinson’s disease model mice - Yunlong Sun; Ning Xu; Jinzhong Liu; Tianxia Sun; Jie Li; Shuyang Xing; Yu Zhao; Bo Pang (Natural Product Research, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Nonnegligible migration of rubber-derived chemicals from road surface to adjacent greenbelt soil - Zhen-Yu Ge; Hai-Yan Zhang; Xue-E Li; Yue-Hong Liu; Li-Ni Wei; Xiang-Ning Liang; Yan-Feng Lv; Tuan-Tuan Wang; Sai Wang; Jian-Liang Zhao (Journal of Hazardous Materials, 2026)

Stable Pacific deep circulation punctuated by episodic intensification during the Mid-Pleistocene Transition - Ke Li; Jun Tian; Ning Zhao; Jianghui Du; Zhonghui Liu; Jinlong Du; Enqing Huang (Global and Planetary Change, 2026)

Investigation into auto-ignition characteristics and kinetics modeling of PODE2/n-heptane mixtures using an RCM - Xiaochen Wang; Jing Zou; Yingtao Wu; Jianbing Gao; Chenglong Tang; Ning Li; Yuwei Zhao (Fuel, 2026)

Low freezing point sustainable aviation fuels through asymmetric cycloalkane design enabled by Ru/NiAlOx catalyst - Jian Li; Xiangrui Lin; Ning Mao; Xiaowei Bai; Zhenghua Dai; Fangjing Liu; Yunpeng Zhao (Fuel, 2026)

Heterogeneous Fe7S8/NiFeCuMoMn HEA: analysis of multicomponent synergistic catalytic mechanism and application in seawater hydrogen production - Shibo Chen; Ning Kang; Zhaojun Liu; Hongxiao Ma; Junzhu Zhao; Meijia Li; Guangwen Xie; Xin Liu; Xiaofu Liu (Fuel, 2026)

Structural stabilization and nutrients delivery of emulsion gels under electrostatic assembly of whey protein isolate fibril and Artemisia sphaerocephala Krasch polysaccharide - Lirong Lu; Xiaolin Yao; Qian Ju; Dan Li; Jianxiong Yue; Ning Liu; Adam Midgley; Mouming Zhao; Katsuyoshi Nishinari; Guoliang Li (Food Hydrocolloids, 2026)

Establishing associations of neighborhood built environment with childhood bedtime - Zeyu Wang; Ye Zhang; Tingjun Chen; Ruoyu Lu; Anda Zhao; Zidi Ning; Zhou Wang; Xiaoman Wang; Jiajun Yuan; Yongfu Li; Shenghui Li (Environmental Research, 2026)

Can urinary OH-PAHs serve as biomarkers for indicating inhalation exposure to PAHs of children: Evidence based on a panel study - Wenjing Zhao; Jiajun He; Zhangning Li; Huanming Li; Xiaojie Zhou; Sreynith Lis; Xinyi Wang; Suzhen Cao; Beibei Wang; Xiaoli Duan; Ning Qin (Environmental Pollution, 2026)

Synergistic effects of amendments and Vetiveria zizanoides on soil quality and heavy metal bioavailability in a historical mine site: A 2-year field evaluation - Xiaolong Lan; Wenjie Lin; Jiaqi Li; Yin Li; Yaqi Zhao; Yili Gan; Yanlong Jia; Zengping Ning; Tangfu Xiao; Enzong Xiao (Ecological Engineering, 2026)

Dual functions of pyrite modified polyethylene carrier in Anammox biofilm: Promoting biofilm growth and enhancing nitrogen removal - Tingting Liu; Dongyue Li; Peng Gao; Yuhan Zhu; Linzhu Du; Xingrong Yao; Wanqi Liu; Kailun Yang; Xingxing Xiong; Ning An; Jiarui Li; Qian Zhao; et al. (Chemical Engineering Journal, 2026)

Nanocarrier-mediated RNAi targeting glutamate decarboxylase synergizes with neonicotinoids for aphid control - Chenxi Liu; Xinyuan Ning; Peng Zhao; Zihan Wei; Yuqing Xie; Lin Zhu; Zhen Li; Xiaoxia Liu (Chemical Engineering Journal, 2026)

Catalytic oxidative depolymerization of lignin into oligomers with multifunctional plant growth regulation in low dose - Yuze Zhao; Guanhua Wang; Yunmeng Luo; Yu Han; Wenhui Li; Yutong Zhao; Ning Wang; Wenjie Sui; Dongmin Li; Chuanling Si (Bioresource Technology, 2026)

Mountain-plain solenoid over a deep basin modified by the Tibetan Plateau terrain effects on synoptic circulations - Zhen Lu; Jun Hu; Tianliang Zhao; Yuqing Zhang; Guicai Ning; Qingjian Yang; Xiaoyun Sun; Zhikuan Li; Deyang Wang (Atmospheric Research, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Alterations in soil moisture and biocrusts modulate the response of soil respiration to simulated rainfall experiment in a dryland ecosystem - Shiyan Zhou; Xinyang Song; Sitao Wei; Haoran Zhao; Boyang Yu; Qianhai Ye; Siqing Wang; Li Ma; Ning Chen; Changming Zhao; Chao Guan (Plant and Soil, 2026)

Spatial analysis of landslides triggered by the 2024 Mw 7.5 Noto earthquake - Jing Zhang; Weile Li; Yu Guo; Huan Liu; Bo Zhao; Ning Chen; Xiao Jin; Gang Sun (Landslides, 2026)

Multi-parameter GNSS monitoring for expansive soil hazards: a case study from coastal Texas - Xiongchuan Chen; Shuangcheng Zhang; Yong Fang; Qingtao Zhang; Lidu Zhao; Peng An; Ning Liu; Qi Liu; Ningkang An; Jun Li; Zhilei Ye (Advances in Space Research, 2026)

Effect of Hong Huang Tang on memory enhancement and mitigation of microgravity-induced oxidative stress in C. elegans - Inam Ullah; Muhammad Zulqarnain Shakir; Xu Chen Zhou; Jixian Liu; Shilan Li; Huabiao Chen; Ning Jiang; Muhammad Wasim Usmani; Muhammad Qasim Barkat; Qiaobei Du; Yufen Zhao; Ning Wang; et al. (Biogerontology, 2026)

An eco-friendly dual-layer parallel control strategy for intelligent hybrid truck platoon considering sustainable emission management and energy optimization - Ning Xie; Wei Zhao; Zihan Wang; Kening Li; Haiwei Wang; Wei Zhang (Process Safety and Environmental Protection, 2026)

Green clarification of Ruditapes philippinarum hydrolysate by freezing - Meihuan Li; Ning Cong; Jiateng Chen; Ling Zhang; Xuanpeng Wang; Ming Du; Xianbing Xu; Jinfeng Pan; Qiyue Zhao (Journal of Food Engineering, 2026)

Chronic C-S-Fe defense dominance over nutrient removal in nanoplastics-exposed constructed wetlands: persistent feoA as the core biomarker - Mengran Guo; Genji Yang; Yunan Wang; Qinglin Li; Qirui Hao; Lixin Li; Ning Hou; Xinyue Zhao (Journal of Cleaner Production, 2026)

Regulatory mechanisms underlying stress-induced accumulation of plant secondary metabolites - Sujing He; Jiangna Wang; Ning Yang; Hongwei Li; Kunqian Li; Lin Li; Wei’e Wen; Tingting Luo; Juanjuan Zhao; Delin Xu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Contrasting drought vulnerability of natural and planted forests in drylands - Xiaoxue Dong; Yue Cui; Jiaqi Zhou; Xuan Li; G. Geoff Wang; Ning Chen; Changming Zhao (Forest Ecology and Management, 2026)

Lentinula edodes-derived exosome-like nanoparticles improve curcumin stability and biotransformation via gut microbiota interactions - Zhengmei Ji; Wenjun Ma; Pengfei Liang; Junjie Zhou; Ning Wang; Yuxin Guo; Miao Zhao; Yue Li; Yurong Guo; Yanhui Han (Food Chemistry, 2026)

Interactive effects of tillage and straw return on crop productivity and soil carbon sequestration in a wheat–maize rotation - Ning Wang; Yunfeng Qiao; Qiuying Zhang; Peifang Leng; Zhao Li; Gang Chen; Fadong Li (European Journal of Agronomy, 2026)

Span80 induced orderly diffusion of monomer for the construction of small pore volume polyamide nanofiltration membrane with high Li/Mg separation ratio - Lu Gao; Yue Miao; Xiaowen Huo; Yingying Zhao; Zhaojing Jing; Xiuling Liu; Haitao Wang; Ning Fan; Qiuying Jia; Kai Ren; Jun Li; Na Chang (Desalination, 2026)

Polystyrene microplastics alter the toxicity of 6PPD to zebrafish (Danio rerio) larvae - Yuexing Zhao; Weitao Liu; Jianfeng Feng; Ning Gao; Jinzheng Liu; Ruiying Shi; Aurang Zeb; Jianling Wang; Qi Wang; Chuan Yin; Xinwei Shi; Xiang Li; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

From mechanism to design: Thermodynamic–metabolic coupling and data-driven optimization of Fe S substrates in constructed wetlands - Xinyue Zhao; Yunan Wang; Mengran Guo; Qinglin Li; Ning Hou; Qirui Hao; Lixin Li; Shunwen Bai (Chemical Engineering Journal, 2026)

Experimental study of bimodal spectral wave-induced dynamic responses in a silty seabed - Linlong Tong; Zhen Huang; Jisheng Zhang; Ning Chen; Dong-Sheng Jeng; Shulin Zhao; Xueyan Li (Coastal Engineering, 2026)

Deciphering mechanisms of stress-induced metabolic shifts in Corynebacterium glutamicum by transcriptomics and contextualised modelling - Xiaomeng Ni; Ning Gao; Wenjing Hu; Xuan Guo; Jiao Liu; Jiuzhou Chen; Ningyun Cai; Xiaojia Zhao; Jibin Sun; Yu Li; Yan Zhu; Ping Zheng (Bioresource Technology, 2026)

An Analytical Solution of the Elastic Compliance Matrix and Its Parameter Characteristics for Jointed Rock Masses - Honglin Luo; Zhechao Wang; Keqi Liu; Liping Qiao; Tao Wang; Ning Wang; LongFei Li; Weiqiang Zhao (Rock Mechanics and Rock Engineering, 2026)

Black Soybean Peptides Attenuate Lead-Induced Neurotoxicity: Role of Oxidative Stress and the RhoA/MAPK Signaling Pathway - Huijie Yang; Fangyu Wang; Qian Li; Tiange Li; Bei Zhang; Lianjun Song; Xianqing Huang; Shuyang Liu; Gianni Galaverna; Peijun Zhao; Ibrahim A. Bakry; Ning Li (Molecular Neurobiology, 2026)

HINT2-Mediated Mitochondrial Modulation Contributes to G-CSF Neuroprotection in Alcohol Use Disorder-Related Ischemic Stroke - Zhi-Chen Guo; Hong-Wei Zhang; Hai-Jian Zhao; Zhi-Li Zhao; Dan Shen; Xiao-Fang Li; Hui-Fang Xi; Teng Fan; Jie Yin; Ning An; Xiu-Qin Yue; Wei-Wei Wang (Molecular Neurobiology, 2026)

Secukinumab improves pregnancy outcomes in recurrent spontaneous abortion with T helper 17 cells/T regulatory cells imbalance: a retrospective cohort study - Guihua Zhu; Xue Wang; Shuqin Bi; Juan Liu; Guiling Yuan; Ning Li; Jinhua Fu; Long Zhao (European Journal of Clinical Pharmacology, 2026)

Dietary supplementation of seaweed reduces methanogenesis from rumen microbial fermentation in vitro via changing keystone microbiota - Jian Sun; Yingyi Xu; Jieyi Zhang; Guangyong Zhao; Delin Duan; Ning Wu; Meng M. Li (Animal Feed Science and Technology, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Ancient DNA sheds light on the mating strategies and genetic identity of Han nobles during the Northern and Southern Dynasties - Youyang Qu; Zhanrui Zhao; Chao Ning; Jiashuo Zhang; Tianshu Li; Dawei Cai; Dongyue Zhao (Archaeological and Anthropological Sciences, 2026)

Four new dammarane nortriterpenoids isolated from mastic ( Pistacia lentiscus L.) and their anti-inflammatory and cytotoxic activities - Xue Tian; Xue-Rui An; Zhi-Qiang Zhao; Jian-Hua Fan; Su-Ning Yuan; Tian-Zhi Li; Wei Liu (Natural Product Research, 2025)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Weight fusion adversarial network based on the self-collaborative strategy for denoising DAS-VSP records - Haitao Ma; Rongkun Zhang; Yi Zhao; Yue Li; Ning Wu (Acta Geophysica, 2025)

Monitoring and determinants analysis of canopy layer urban heat island in China based on both air temperature and apparent temperature - Yuanzheng Li; Chaoqun Ma; Tengbo Yang; Zhifeng Wu; Rui Yao; Guosong Zhao; Xiaojv Ning; Peng Kang (Urban Climate, 2025)

Biochar promoted soil organic carbon accumulation and aggregate stability by increasing the content of organic complex metal oxides in paddy soil - Jiajun Wu; Bin Zhou; Zichuan Li; Cheng Liu; Yan Li; Yulin Wang; Ning Zhao; Zhuozhe Wang; Yanjun Chai; Antonio Scopa; Marios Drosos; Vishnu D. Rajput; et al. (Soil and Tillage Research, 2025)

Welding surface epitaxial layer enables high-loading sulfide all-solid-state batteries - Zhuomin Qiang; Yanbin Ning; Wei Zhao; Yajie Song; Chaoqun Zhang; Shengwei Dong; Yifei Zhao; Yan Zhang; Yinyong Sun; Biao Deng; Xudong Li; Geping Yin; et al. (Science Bulletin, 2025)

Application of data mining to fast prediction of propeller performance - Qingyu Xue; Kang Han; Pengli Zhao; Yu Gu; Ning Li (Ocean Engineering, 2025)

O-Hf-Mg isotopic signals of recycled oceanic crust in the Early Cretaceous I-type granites from NE China - Ao Li; Wu-Bin Yang; Xu Zhao; He-Cai Niu; Ning-Bo Li; Pan Qu (Lithos, 2025)

Integrating RNA sequencing with deep learning–based metabolic toxicity prediction: A new perspective on screening prioritized liquid crystal monomers - Wenjin Zhao; Jiatong Li; Ning Hao; Guodong Shi; Jiapeng Liu; Zhengyang Deng; Yuanyuan Zhao (Journal of Hazardous Materials, 2025)

Driving synergistic Fe-N-Plastic co-metabolism and functional microbial symbiosis via nZVI@RA for enhanced decontamination in constructed wetlands - Qinglin Li; Tuoshi Zhang; Xinyue Zhao; Han Zhang; Mengran Guo; Xiangwei Meng; Ning Hou; Qirui Hao; Lixin Li (Journal of Hazardous Materials, 2025)

Redox fluctuations and iron enrichment orchestrate a time-coordinated Fe–N metabolism in constructed wetlands - Jiacheng Shang; Tuoshi Zhang; Xinyue Zhao; Mengran Guo; Xiangwei Meng; Genji Yang; Ning Hou; Qirui Hao; Lixin Li; Baiwen Jiang (Journal of Cleaner Production, 2025)

Design and screening of low target-site and non-target-site resistance sulfonylurea herbicide alternatives: Evaluation of ecological and health risks - Li Tao; Bohan Xu; Lu Wang; Yuanquan Chi; Weihan Cui; Xingmin Zhao; Hongbin Wang; Ning Huang; Chenyu Zhao; Luze Yang (Journal of Environmental Chemical Engineering, 2025)

A novel structure transformation strategy for rare earth complex recovery from (bio)lixivium - Xiaoyu Meng; Ning Zhang; Yu Zhao; Ni He; Li Shen; Guohua Gu; Guanzhou Qiu; Hongbo Zhao (Journal of Environmental Chemical Engineering, 2025)

Impact of regionally transported biomass burning on carbonaceous aerosol characterization, contribution and degradation in Pu'er, Southwest China - Jianwu Shi; Wenjun Rao; Chenyang Zhao; Li Deng; Xinyu Han; Wei Du; Jianhong Huang; Senlin Tian; Ping Ning; Jiming Hao; Yaoqian Zhong (Journal of Environmental Sciences, 2025)

Probiotic properties and genomic insights of Limosilactobacillus reuteri isolated from Tibetan fermented yak milk with potential anti-hyperuricemic activity - Xingjie Wang; Qiming Li; Wenyi Lai; Ailing Xie; Mengmei Zhang; Kaidi Hu; Jianlong Li; Qin Li; Ning Zhao; Xiaolin Ao; Shuliang Liu (International Dairy Journal, 2025)

Effects of different processing (Paozhi) methods on the structural characteristics and bidirectional immunomodulatory activities of Astragalus polysaccharides - Ning Zhao; Yunchun Li; Qingli Qu; Jing Shao; Dong Pei; Jianfei Liu (Food Research International, 2025)

Characterizing the impact of lactic acid bacteria-fermented vegetable juice on microbial assemblage and quality of pickled suancai - Kaidi Hu; Jing Li; Min Zhang; Yizhuo Wan; Yankang Yang; Jingyi Ren; Zerong Jin; Wen Wang; Yunxiao Wan; Qisheng Zhang; Dongdong Wang; Weiqin Deng; et al. (Food Research International, 2025)

Modulation of gut microbiota and storage stability of yogurt fortified with novel EPS-producing Lactiplantibacillus plantarum DPA1C - Xingjie Wang; Jinghui Lai; Cheng Ye; Liwen Tao; Yuchen Liu; Kaidi Hu; Jianlong Li; Qin Li; Ning Zhao; Shuliang Liu (Food Research International, 2025)

Biofilm with a mechanically strengthened character via enhanced cross-links of soybean proteins with short-chain fatty acid-modified starch - Sheng Ke; Gaoheng Li; Anqi Wang; Haotian Wu; Peng Yu; Ming Ning; Padraig Strappe; Bing Wang; Chris Blanchard; Zhongkai Zhou; Guohua Zhao (Food Chemistry, 2025)

Proteomic insights into DEM-induced oxidative stress: Glycolytic and antioxidant synergy in beef colour stability - Cai-Yun Li; Wen-Jun Zhao; Ya-Ning Qu; Yu-Bin Zhang (Food Chemistry, 2025)

Multi-target anti-inflammatory mechanism of poplar-type propolis based on network pharmacology and metabolomics - Jiaqi Zhao; Ruowen Wang; Wenjie Yu; Keju Li; Liping Luo; Fangjian Ning (Food Bioscience, 2025)

Lysosomal dependent transcytosis of polystyrene nanoplastics within macrophages - Zijia Liu; Yunjiang Yu; Yuchen Zheng; Chao Sheng; Ao Li; Wenzhuo Li; Zijie Zhao; Yunlu Ning; Renhang Zhou; Wenzhe Hou; Zhixiang Zhou (Food and Chemical Toxicology, 2025)

Regulating hydrogen transfer for diverse energetics - Pengcheng Guo; Ning Ding; Qi Sun; Chaofeng Zhao; Xudong Xu; Xiaoting Ren; Jinxuan He; Shenghua Li; Siping Pang (Chemical Engineering Journal, 2025)

Theranostic nanoplatform for triple-negative breast cancer therapy: Autophagy suppression-coordinated siRNA delivery triggers apoptosis, ferroptosis, and pyroptosis via photothermal activation - Guobao Ning; Lishen Yang; Bilian Li; Jianghua Lin; Shufen Li; Fengqi Zhou; Han Chen; Xingye Zheng; Weijie Sun; Hui Zhao; Can-Peng Li (Chemical Engineering Journal, 2025)

Electron engineering via tensile-compressive effect in non-precious metal high-entropy alloy for pH-universal oxygen reduction - Juan Li; Yinze Yang; Ning Zhang; Di Bao; Bing Li; Peitong Li; Yafei Zhao; Huishan Shang; Bing Zhang (Chemical Engineering Journal, 2025)

Chiral multilevel-structured hydroxyapatite nano-bacterial cellulose membrane with anti-inflammatory activity and regulation of immune microenvironment promotes wound healing in the elderly - Jiawen Zhao; Yuan Zong; Tong Wu; Yi Yang; Lei Li; Wenshuo Tang; Xiaoyu Zhao; Xianfei Xie; Yiming Gao; Chao Zhou; Ning Li; Liting Jiang (Chemical Engineering Journal, 2025)

Predicting and interpreting nitrogen removal performance and functional microbial abundance of single-stage partial nitrification and anammox system using machine learning methods - Xiulin Mu; Fangxu Jia; Shengming Qiu; Yiran Li; Ning Mei; Xingcheng Zhao; Baohong Han; Xiangyu Han; Jingjing Zhang; Hong Yao (Bioresource Technology, 2025)

Comparative study of gangue fine aggregate strengthening technologies: microbially induced mineralization, water glass strengthening, and composite strengthening - Chunhua Feng; Linpeng Pan; Ning Li; Yu Chen; Xiaomeng Zhao; Fang Liu; Jianping Zhu; Mingxing Du (Waste Disposal & Sustainable Energy, 2025)

Bacillus megaterium controls melon Fusarium wilt disease through its effects on keystone soil taxa - Xiujun Lu; Qingmei Li; Bowen Li; Fang Liu; Yeqing Wang; Wenshuo Ning; Yanan Liu; Hongbo Zhao (Plant and Soil, 2025)

Physiological and molecular mechanisms of leaf color transformation in ‘Nanguo’ pear and its impact on flower bud quality - Ning Yan; Weichi Wang; Aihao Zhao; Kunfeng Chang; Xin Zhang; Ruihan Li; Yuqi Du; Zhenzhen Song; Ling Zhao; Guodong Du (Plant and Soil, 2025)

Correction: Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Enhanced production of eicosapentaenoic acid and fucoxanthin in Phaeodactylum tricornutum via a two-stage strategy with multifactorial synergistic effects - Xin Dong; Meng-Han Zhao; Chen-Xi Li; Xiao Lin; Ning Ma; Hong-Jin Qiao; Dian-Feng Han; Ying-Jiang Xu (Journal of Applied Phycology, 2025)

LETM2 regulates mitochondrial function and autophagy in diabetic foot ulcers: implications for oxidative stress and therapeutic targeting - Nan Su; Jiwei Wang; Zhiwei Xue; Shujie Peng; Wenchen Xing; Haoyong Jin; Jiangli Zhao; Yanya He; Jiaqi Shi; Wenbo Li; Qijian Wei; Bin Huang; et al. (Functional & Integrative Genomics, 2025)

Transcriptome analysis of the hypothalamus and testes in Brandt’s Vole: new insights into mechanisms of photoperiodic plasticity in postnatal testicular development - Lewen Wang; Yaqi Ying; Ning Li; Ying Song; Lijuan Zhao; Hong Sun; Zhenlong Wang; Xiao-Hui Liu; Dawei Wang (Functional & Integrative Genomics, 2025)

Microscopic Differences and Connectivity Evaluation for Typical Unconsolidated Sandstone Gas Reservoirs in the South China Sea: A Case Study from Lingshui A Area, Qiongdongnan Basin - Di Meng; Yiqiang Li; Chong Zhang; Xiaoyu Tang; Ning Zhao; Wei Zhou; Jian Chen; Yu Sun (Journal of Ocean University of China, 2025)

Mechanical behavior and application of an innovative multistage yielding support structure in squeezing rock tunnel - Zhichun Liu; Fei Wu; Xujie Zhao; Xiaolong Guo; Ning Li; Zhinan Hu; Lijun Tan; Wenzheng Wang; Xianmin Li (Tunnelling and Underground Space Technology, 2025)

The association between urinary levels of organic phosphorus insecticide exposure and subclinical thyroid disorders - Gaohui Wei; Yi Shen; Xian Wang; Dandan Xiong; Lingli Zhang; Tianliang Zhao; Xinjie Li; Mengmeng Sun; Sihui Yu; Xueqi Huang; Shengkang Cao; Ning Liao; et al. (Toxicology Letters, 2025)

Short-term no-tillage improves soil water retention and maintains soil aeration at high moisture conditions despite reduced macroporosity - Jing Tan; Bingcheng Si; Ying Zhao; Yili Lu; Yuxin Chen; Ning An; Song Li; Weichao Wang; Han Fu; Wei Han; Yanli Yi (Soil and Tillage Research, 2025)

Assessing future flood risk using remote sensing and explainable machine learning: A case study in the Beijing-Tianjin-Hebei region - Siying Li; Yi Tang; Yuting Zhao; Xiaojun Ning; Yifan Zhang; Siran Lv; Chenshu Liu (Remote Sensing Applications: Society and Environment, 2025)

Decoding pyrene-induced reactive oxygen species production in the rhizosphere and their role in biodegradation: The repair mechanism of symbiotic driving by Fe(II) and microorganisms - Chi Zhang; Yiming Zhang; Guangming Diao; Ning Hou; Xinyue Zhao; Dapeng Li (Journal of Hazardous Materials, 2025)

RSA-Net: generalized weak signal recovery for DAS VSP data in complex noise environments - Yanwei Li; Yanan Tian; Yue Li; Ning Wu; Yuxing Zhao (Journal of Applied Geophysics, 2025)

Polarization-Guided unsupervised convection networks for marine velocity field recovery - Yang Guo; Naifu Yao; Xi Lin; Ning Li; Yongqiang Zhao; Seong G. Kong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Ionic liquids accelerate the crystallization of a magnetic fluorine-functionalized 3D covalent organic framework for efficient capture of trace benzoylurea insecticides in juices and beverages - Zekun Liu; Lu Liu; Yan Dong; Yan Li; Chong Zhang; Xiao-Li Wang; Lingxi Zhao; Hai-Long Jiang; Yong-Ning Wu; Xiangfeng Chen; Feng Li; Ru-Song Zhao (Chemical Engineering Journal, 2025)

Corrosion-resistant TiZrNbTaW high-entropy alloy coatings for Ti anode polar plates of proton exchange membrane water electrolyzers - Hongwu Zhao; Rui Gao; Hao Li; Muyu Ma; Guoxing Chen; Daiman Zhu; Marcos Antonio Coelho Berton; De Ning; Anke Weidenkaff; Yongli Li (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

A Carbon Fiber-Reinforced Backfill Composite with Self-Sensing Capability for Mine Stability Monitoring - Bozhi Zhao; Shan Ning; Jingmin Xu; Tianyu Li; Wei Luo; Pengjun Gao; Weibing Zhu (Rock Mechanics and Rock Engineering, 2025)

Formation mechanism and evolution characteristics of the loess–mudstone interface landslide in Yan’an, China - Penghui Ma; Qixian Jiao; Yalin Nan; Chuanzhi Zhang; Zekun Li; Luqing Zhao; Lisen Chen; Ning Han; Jianbing Peng (Bulletin of Engineering Geology and the Environment, 2025)

Soil hydrolases and microbial biomass regulate wetland CO2 emissions under warming and water level reduction - Mengyuan Zhu; Yanyu Song; Yisong Feng; Mengting Li; Huanhuan Feng; Shouyang Luo; Wenwen Tan; Ning Chen; Guangying Zhao; Changchun Song (Applied Soil Ecology, 2025)

GPR30-mediated the MEK/ERK signaling pathway promotes porcine oocyte maturation and development - Jiaxin Duan; Anli Xu; Junhao Xie; Linghao Wang; Qipin Lv; Jingxian Yang; Ning Zhao; Bugao Li; Guoqing Cao (Theriogenology, 2025)

A hybrid intelligent optimization algorithm for long-term production planning of open-pit mine considering carbon reduction plan - Ning Li; Jinxin Liu; Liguan Wang; Bibo Dai; Shugang Zhao; Jian Chang; Haiwang Ye; Dairong Yan (Swarm and Evolutionary Computation, 2025)

A lectin receptor-like kinase TaSRK that is deacetylated by TaHDA9 regulates wheat grain length by mediating the photosystem II protein TaPsbO - Ning Zhang; Songgang Li; Zhipeng Sun; Jingjing Dai; Shuyu Zhang; Daiying Chen; Lei Zhao; Aolin Jia; Feng Chen (Science Bulletin, 2025)

Quantifying the relative contributions of key drivers to future changes in PAHs health risks over the Yangtze River Delta: A multi-scenario modeling approach - Ning Nie; Ting Li; Xinran Liu; Xiaodan Guan; Shilun Zhou; Min Liu; Dengzhong Zhao (Journal of Hazardous Materials, 2025)

Piezoelectric polarization-induced electric field in Co-Co2P/BNT composite for enhanced peroxymonosulfate activation and rapid degradation of sulfamethoxazole - Xunwu Yang; Xiaomei Ma; Haodi Yang; Jie Zhao; Yigui Tang; Ping Ning; Chi Wang; Guijian Zhang; Shuangyou Bao; Kai Li (Journal of Environmental Chemical Engineering, 2025)

Bimetallic cobalt-cerium loaded copper foam for enhanced paraxylene low-temperature catalytic oxidation: Mechanistic insights and role of oxygen vacancies - Chenyang Zhao; Huanhuan Wu; Guangfei Qu; Yongheng Yuan; Zheng Yuan; Guojun Liu; Zhishuncheng Li; Junyan Li; Yingying Cai; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

Transdimensional joint inversion of surface wave, refraction, and resistivity data using Modified Barnacles Mating Optimizer for near-surface investigations - Hanbing Ai; Xianhai Song; Xueqiang Zhang; Yunus Levent Ekinci; Çağlayan Balkaya; Arka Roy; Jiazhe Li; Ling Ning; Zhao Le; Yingwei Yan (Journal of Applied Geophysics, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Application of magnetic chitosan gel combined with magnetic solid phase extraction based on deep eutectic solvent for the residue analysis of ofloxacin and enrofloxacin in milk - Wen Li; Yue Na; Wenqi Wang; Yingtong Ma; Ning Liang; Longshan Zhao (Food Chemistry, 2025)

One-pot ATP-free biosynthesis of D-allulose: Enzyme immobilization and process optimization - Zhengwen Zhu; Longyan Zhao; Yifan Tu; Zanyu Ren; Diandong Xie; Ning Li; Chen Liang; Jidong Liu (Food Bioscience, 2025)

Constructing core–void–shell nanoreactors for enhancing production of C5–20 liquid fuels via Fischer–Tropsch synthesis - Ning Zhao; Zhaopeng Liu; Tingting Wang; Zhenhua Li (Chemical Engineering Journal, 2025)

Establishment of an efficient CRISPR-dCas9-SunTag transcriptional activation system in Aspergillus nidulans for enhancing emodin production - Yuan Tian; Qing Xu; Ning Wang; Yanling Li; Wenyu Yang; Fei Huang; Qing Hao; Liping Zhao; Zhiruo Zhang; Fengchun Zhao; Fanglong Zhao (Chemical Engineering Journal, 2025)

Orbital occupancy modulation to optimize the electroactivity towards bidirectional sulfur conversion in lithium-sulfur batteries - Wei Zhou; Zilong Li; Shunlian Ning; Jinchang Xu; Ming-Hsien Lee; Dengke Zhao; Jian Qing; Nan Wang; Hui Meng (Chemical Engineering Journal, 2025)

Surface chlorine doping activates highly stable Cu2O(111) facets for enhanced CO2 photoreduction - Ning Li; Ping Zhang; Reyila Tuerhong; Yongchong Yu; Yapeng Lan; Yu Zhang; Xiaoping Su; Lianbiao Zhao; Lijuan Han; Xiaotian Wang; Hengjiao Gao (Chemical Engineering Journal, 2025)

Hierarchical porous MOF/PEDOT:PSS films with enhanced mechanical properties and thermoelectric performance - Ning Xia; Jiale Zhao; Xinlin Zha; Guanfei Gong; Jie Yu; Xiufang Zhu; Mufang Li; Dong Wang (Chemical Engineering Journal, 2025)

Early Microcirculatory Dysfunction on Perfusion CT Is Related to Prognosis After Aneurysmal Subarachnoid Hemorrhage - Sijia Li; Lei Wu; Ning Li; Xingquan Zhao (Translational Stroke Research, 2025)

Genetic diversity analysis and duplicates identification of new sweetpotato accessions collected in China - Jie Wang; Rui Yuan; Qinglian Li; Yao Wang; Donglan Zhao; Lingxiao Zhao; An Zhang; Xibin Dai; Shizhuo Xiao; Tong Ning; Zhilin Zhou; Qinghe Cao (Genetic Resources and Crop Evolution, 2025)

Integrated network pharmacology and cellular assay revealed an anti-type 2 diabetes effect of Astaxanthin from Haematococcus pluvialis - Ran Chen; Shilin Wu; Zhen Zhang; Kun Li; Jingyun Chen; Ning Yang; Hongxiang Zhao; Rongqing Zhang (Algal Research, 2025)

Influence of long-term inorganic fertilization and straw incorporation on soil organic carbon: Roles of enzyme activity, labile organic carbon fractions, soil aggregates, and microbial traits - Ning Wang; Zhipin Ai; Qiuying Zhang; Peifang Leng; Yunfeng Qiao; Zhao Li; Chao Tian; Hefa Cheng; Gang Chen; Fadong Li (Agriculture, Ecosystems & Environment, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Unveiling the integrated toxicological effects and underlying mechanisms of bisphenol A and cadmium, two hormesis-type endocrine disruptors, on Chromochloris zofingiensis - Rui Feng; Linyuan Song; Haodong Wang; Shixuan Gong; Yangguo Su; Shudong Zhang; Ning Li; Zhao Zhang (Journal of Hazardous Materials, 2025)

Investigation on deactivation periods of ZSM-5/SAPO-34 catalyst in MTA reaction: Carbon deposition behavior - Jingbo Li; Bangming Yang; Ning Li; Jianqiao Zhao; Shuo Li; Ruizhi Chu; Xianliang Meng; Weisong Li; Shi Yu (Fuel, 2025)

Improving Ancha tea aroma quality via innovative processing: Characterization of key odorants by GC–MS, GC-O, Sensomics, and Chemometrics - Zhenbin Chen; Yanqun Jiang; Zhibin Ye; Wei Zhao; Jixin Zhang; Yida Wu; Wenjing Huang; Tiehan Li; Jingming Ning (Food Chemistry, 2025)

Efficient and thermally stable double perovskite phosphor Cs2NaScCl6:Mo4+ with broadband long-wavelength NIR emission - Tinglin Mou; Zhongyuan Li; Haitao Zhao; Mengdi Xu; Xinquan Zhou; Xianju Zhou; Zhen Fang; Lixin Ning (Chemical Engineering Journal, 2025)

High-capacity superlattice La0.55Sm0.20Mg0.25Ni3.27Al0.01 hydrogen storage alloys with series of (A7B23) -(A2B7)1- (x = 0, 0.1, 0.9) structures for nickel-metal hydride batteries - Ning Zhang; Beichen Zhao; Wenfeng Wang; Anyi Zhang; Qiuyue Jia; Yuan Li; Lu Jian; Tianzi Li; Shumin Han; Lu Zhang (Chemical Engineering Journal, 2025)

Solvent mediating hydrogen bonding in oriented FAPbI3 enables efficient air-processed perovskite solar cells - Chong Liu; Haoze Lu; Luyao Ma; Li Yuan; Fengyuan Li; Qinhui Bao; Chuwu Xing; Ning Jia; Pengzhen Zhao; Zhiyu Fang; Duofa Wang; Pengfei Guo; et al. (Chemical Engineering Journal, 2025)

Microreactors in chemical process intensification: Chemical reactions, crystallizations, extractions and emulsifications - Xianglong Zhao; Hanyu Jiang; Su Wang; Xin Yuan; Yirong Feng; Jiming Yang; Yuguang Li; Ning Zhu; Shuangfei Zhao; Wei He; Kai Guo (Chemical Engineering Journal, 2025)

Novel degradable piezoelectric-induced PHBV/CS/HA scaffolds to achieve dual effects of endogenous osteogenesis and antibacterial properties by piezoelectric stimulation and ultrasonic action - Cong Yang; Meilin Zhao; Ning Yu; Sen Wang; Yuanqiang Li; Hang Chen; Yan Xiong; Xiaonan Zhang; Ping Ji (Chemical Engineering Journal, 2025)

Microbiome catalog and dynamics of the Chinese liquor fermentation process - Xue Zhu; Liangqiang Chen; Pengshuo Yang; Sha Luo; Mengjing Teng; Wenjie Zhu; Yuxue Li; Dan Zhao; Nan Wang; Xiaoke Chen; Mingyue Cheng; Huabin Tu; et al. (Bioresource Technology, 2025)

KIAA1522 isoform switching regulates LTR-RTs activity in distinct pluripotency states of hESCs - Ning Yang; Wen Sun; Shiwei Cao; Chen Zhao; Nannan Wang; Pengcheng Li; Yu Zou; Siqi Wang; Tongtong Cui; Shuyu Guo; Wei Li; Haoyi Wang; et al. (Science China Life Sciences, 2025)

Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

MTGGF: A Metabolism Type-Aware Graph Generative Model for Molecular Metabolite Prediction - Peng-Cheng Zhao; Xue-Xin Wei; Qiong Wang; Hao-Yang Wang; Bing-Xue Du; Jia-Ning Li; Bei Zhu; Hui Yu; Jian-Yu Shi (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Sodium silicate enhance induced resistance by regulating DNA methylation in postharvest muskmelon - Liang Lyu; Chenglong Zhao; Lei Li; Yuchao Ning; Yawen Luo; Xining He; Di Gong (European Journal of Plant Pathology, 2025)

Tryptic peptide mapping on antibody-drug conjugates: Improvements in hydrophobic peptide recovery and missed cleavages - Xiao Pan; Yimeng Zhao; Zhijie Wu; Haibo Qiu; Ning Li (Analytica Chimica Acta, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

Coupling crop growth models and machine learning for scalable winter wheat yield estimation across major wheat regions in China - Jiyuan Xie; Dongyan Zhang; Ning Jin; Tao Cheng; Gang Zhao; Dong Han; Zhen Niu; Weifeng Li (Agricultural and Forest Meteorology, 2025)

Genomic Approaches to Enhance Disease Resistance in Large Yellow Croaker: Recent Progress and Future Perspectives - Zhou Jiang; Yulin Bai; Ning Li; Lin Chen; Ji Zhao; Yin Li; Tao Zhou; Peng Xu (Reviews in Aquaculture, 2025)
Large yellow croaker is an important marine aquaculture species in China, but frequent disease outbreaks have led to significant losses in the aquaculture industry. Although traditional genetic selection methods have long been applied in fish breeding, an increasing number of studies are introducing genomic selection methods into large yellow croaker breeding to target complex traits such as disease resistance. Recent advancements in genomic resources, including an updated reference genome and SNP array, have opened up new opportunities for genetic and evolutionary research on this species. This review provides an overview of the current status of the large yellow croaker aquaculture industry and the existing approaches to addressing disease challenges. It also summarizes genomic selection techniques, the genetic mechanisms underlying disease resistance traits, and potential improvements in genomic selection methods. Furthermore, we summarize future directions for large yellow croaker breeding, incorporating the application of genetic research, multi‐dimensional data integration, standardized testing protocols, and artificial intelligence for phenotypic measurement. These strategies have opened new pathways to enhance disease resistance in large yellow croaker and to promote the sustainable development of its aquaculture industry.

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Establishment and characterization of a new Chinese extrahepatic cholangiocarcinoma cell line, EBC-X1 - Yuanhui Su; Huan Tang; Xin Miao; Cheng Yu; Changpeng Chai; Wei Huang; Lu Li; Jieyu Zheng; Tao Xu; Fa Jin; Zhipeng Ye; Zhao Hu; et al. (Human Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Top-of-atmosphere radiometric reference model for stable land sites with relaxed temporal stability requirements and its application to GF6/WFI radiometric calibration and validation - Lingling Ma; Yongguang Zhao; Wan Li; Ruoxi Yang; Renfei Wang; Ning Wang; Qijin Han; Xin Lu; Fang Huang; Jianghong Zhao (Remote Sensing of Environment, 2025)

Hydrodynamic and geomorphological responses of tidal flats to extreme climate events - Renzhi Li; Ya Ping Wang; Rui Yuan; Ning Zhao; Bixuan Tang; Zhixuan Feng; Bruno Castelle (Journal of Hydrology, 2025)

Enhancing ecological risk assessment of dioxins in aquatic environments: AHR diversity and species sensitivity differences in tiger puffer (Takifugu rubripes) - Zhenhong Xue; Wanglong Zhang; Anran Ren; Sibel I. Karchner; Diana G. Franks; Yanjiao Zong; Yongchao Ma; Jiayi Wang; Yiqin Xu; Jiaming Li; Ning Ding; Chunchen Liu; et al. (Journal of Hazardous Materials, 2025)

Cross-protection and cross-feeding mediated by signaling molecules enhanced the viability of P. fluorescens S01 and R. erythropolis S02 under the dual stresses of polycyclic aromatic hydrocarbons (PAHs) and low temperature - Qiuying Song; Zihui Qi; Ning Liang; Ning Hou; Chi Zhang; Chenghao Pei; Xinyue Zhao; Dapeng Li (Journal of Hazardous Materials, 2025)

Methodological guidance to the batch preparation of graphene-based sensor for low-cost and high-performance Cd2+ and Pb2+ detection - Wenshuai Ye; Ning Liu; Sicheng Li; Guo Zhao; Gang Liu (Journal of Hazardous Materials, 2025)

Functionalized FeS2@CQDs as dual-role agents: Enhancing electron availability and transport for improved nitrogen removal in constructed wetlands - Mengran Guo; Qianzi Feng; Xiangwei Meng; Tuoshi Zhang; Yaoxuan Cheng; Ning Hou; Dapeng Li; Xinyue Zhao (Journal of Cleaner Production, 2025)

Electrogenic microorganisms enhance synergistic interactions between algae and bacteria through electron release: Insights from niche succession and nitrogen metabolism - Chi Zhang; Hang Du; Mingwei Zhou; Dapeng Li; Qiuying Song; Ning Hou; Xinyue Zhao (Journal of Cleaner Production, 2025)

Green catalytic oxidation of m-diethylbenzene to m-ethylacetophenone with molecular oxygen over modified nano-sized TS-1 zeolite - Jinhong Li; Chang Cai; Yi’ning Wang; Zhimei Song; Dan Fang; Nan Zhao; Yue Zhang; Lidong Chen; Jianguo Zhang; Yongcun Zou (Journal of Environmental Chemical Engineering, 2025)

Seismic stability evaluation of benched bedding rock slopes with varying landforms - Wenhui Li; Chunlei Xin; Zhao Wang; Wenkai Feng; Xinyuan Yu; Ning Huang; Iman Hajirasouliha (Engineering Geology, 2025)

Carbon stocks in two temperate Zostera meadows in the Yellow Sea, North China - Ruiting Gu; Sichao Pu; Jianwu Tang; Tingting Liu; Linjing Ren; Shaochun Xu; Shuo Yu; Xiuzhen Li; Ning Zhao (CATENA, 2025)

Detecting Deleterious Recessive Variants in Large Yellow Croaker Using Data from 7337 Individuals - Zhou Jiang; Ji Zhao; Ning Li; Jiaying Wang; Fei Pu; Hongshu Chi; Peng Xu; Tao Zhou (Marine Biotechnology, 2025)

Identification of gut microbiota causally associated with aging and longevity and mediation roles of the cerebrospinal fluid proteins: proteomic genetic evidence from Mendelian randomization - Ruonan Liu; Zheng Zhu; Yuanyue Zhu; Xin Lin; Hongjie Li; Tiange Wang; Jie Zheng; Mian Li; Zhiyun Zhao; Yu Xu; Jieli Lu; Weiqing Wang; et al. (GeroScience, 2025)

Expediting the integration of China into the global rare disease drug development and approval - Jiatong Ding; Huiyao Huang; Yuning Wang; Yiru Hou; Guo Zhao; Yuanting Cai; Shuhang Wang; Xuebo Zhang; Ning Li (Science Bulletin, 2025)

Exploring the role of cytochrome bc1 complexes in alleviating the inhibition of microbial nitrogen metabolism by nanoplastics: Insights into the use of recycled aggregates from constructed wetlands - Xiangwei Meng; Han Zhang; Jiacheng Shang; Ning Hou; Lixin Li; Dapeng Li; Xinyue Zhao (Journal of Cleaner Production, 2025)

Microbiome-metabolomic insights into the systemic regulation in Fangxian Huangjiu fermentation - Haiyin Chen; Sicheng Zhong; Zhijie Liu; Zhao Hu; Chao Wang; Yuke Zhou; Ning Xu; Fuquan Zhao; Dongsheng Li; Yong Hu (Food Chemistry, 2025)

A novel daidzein-betaine cocrystal alleviates obesity by improving lipid metabolism, modulating inflammation, and reshaping gut microbiota - Yanling Sun; Shupeng Li; Rongxin Liu; Ning Ma; Xinghua Zhao; Xin He (Food Bioscience, 2025)

Carbon and air pollutant emission dynamics of small-scale industrial sectors based on CEMS: a case of tobacco curing industry - Sishuo Chen; Yi Chen; Yonglei Jiang; Yiting Li; Chen Gu; Ning Ding; Weizhe Zhou; Lei Zhang; Qian Yu; Yu Zhao (Environmental Pollution, 2025)

Mxene quantum dot insertion-induced electron transfer in CoFe LDH for high-performance zinc-air batteries - Qing Sun; Kailin Li; Tie Shu; Ziyang Guo; Yongfei Li; Yuxin Zhang; Liang Li; Jiaoyi Ning; Peng Zhao; Ke Xin Yao (Chemical Engineering Journal, 2025)

Collagen targeting BMSCs-derived extracellular vesicles coupled with decellularized tendon scaffold for anterior cruciate ligament reconstruction - Jie Wang; Jing Cui; Liang-Ju Ning; Yan-Jing Zhang; Fei Xing; Lei-Lei Zhao; Hui-Min Liu; Xuan Li; Min Zhu; Jing-Cong Luo; Zhou Xiang; Ting-Wu Qin (Chemical Engineering Journal, 2025)

Ecohydrological processes can predict biocrust cover at regional scale but not global scale - Ning Chen; Siqing Wang; Liping Yang; Defei Liang; Zhengwei Ren; Xudong Liu; Longwei Dong; Jingyao Sun; Emilio Rodriguez-Caballero; Bettina Weber; Caroline A. Havrilla; Emilio Guirado; et al. (Plant and Soil, 2025)

The failure modes and evolution process of loess landslide dams via flume tests - Zekun Li; Penghui Ma; Ning Han; Qixian Jiao; Lisen Chen; Lin Ran; Zhijie Jia; Luqing Zhao; Jingjing Nan; Jianbing Peng (Landslides, 2025)

Assessment of the rat acute oral toxicity of quinoline-based pharmaceutical scaffold molecules using QSTR, q-RASTR and machine learning methods - Jianing Xu; Ting Ren; Feifan Li; Shuo Chen; Tengjiao Fan; Lijiao Zhao; Rugang Zhong; Guohui Sun; Ning Lin (Molecular Diversity, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Enhancing microplastic removal and nitrogen mitigation in constructed wetlands: An earthworm-centric perspective - Jinyi Yang; Tuoshi Zhang; Shengjun Ma; Jiacheng Shang; Lixin Li; Yucui Ning; Xinyue Zhao (Journal of Hazardous Materials, 2025)

3D printing of high internal phase emulsions stabilized by OSA modified potato starch: Effect of citrus fiber addition - Jiaojiao Wei; Yingkai Li; Andreas Blennow; Feng Zhao; Ning Wang; Xiao Liu; Xingxun Liu; Chi Zhang (Food Hydrocolloids, 2025)

Silica Nanoparticles Induce SH-SY5Y Cells Death Via PARP and Caspase Signaling Pathways - Kai Ma; Tiantian Tian; Xinyue Li; Huan Pang; Xiaofan Ning; Meng Li; Jiali Li; Zhixuan Luo; Tianxiang Liu; Mengyue Liu; Mingqian Wang; Chao Zhao; et al. (Molecular Neurobiology, 2025)

Identification of Key Biomarkers of Growth-Related Traits in the Bay Scallop Argopecten irradians irradians via Multi-omics Analysis Strategies - Bingyu Ning; Chengda Li; Tanjun Zhao; Yang Zou; Yaoyao Zhan; Yaqing Chang (Marine Biotechnology, 2025)

Epidemiological and clinical profiles of respiratory syncytial virus infections in hospitalized children: a retrospective cohort study utilizing targeted next-generation sequencing - Chunyun Fu; Jialing Ruan; Lishai Mo; Jiangyang Zhao; Junming Lu; Ya Huang; Xuehua Hu; Qiang Huang; Yanhua Feng; Wenting Tang; Ning Zhu; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Coexistence Patterns of Biocrust-Vascular Plant in the Loess Plateau - Yali Ma; Li Ma; Liping Yang; Hongyu Jiang; Siqing Wang; Yuhan Qi; Qianhai Ye; Weiqi Yao; Yafeng Zhang; Defei Liang; Changming Zhao; Ning Chen (Ecosystems, 2025)

Key local atmospheric processes of the heat extreme over the middle-lower Yangtze River basin in August 2022 - Yue Sun; Jianping Li; Yang Zhao; Hongyuan Zhao; Hao Wang; Mian Zhu; Ning Wang (Climate Dynamics, 2025)

Valorization of quinoa by-products and their potential applications - Guangjie Zhang; Chenxi Ren; Ning Li; Ganghui Chu; Abdulla Yusuf; Hongmei Zhao; Tianzhu Guan (Cereal Research Communications, 2025)

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Correction: Atorvastatin inhibits the apoptosis of human umbilical vein endothelial cells induced by angiotensin II via the lysosomalmitochondrial axis - Ye Chang; Yuan Li; Ning Ye; Xiaofan Guo; Zhao Li; Guozhe Sun; Yingxian Sun (Apoptosis, 2025)

Aggregation behavior of photoaging nanoplastics in artificial sweat solutions - Yanlin Yang; Haoran Song; Yan Cao; Jiao Li; Jie Li; Xiangfen Cui; Xuewei Hu; Anjum Mahfuza; Ping Ning; Linfeng Zhang; Qun Zhao; Senlin Tian (Journal of Hazardous Materials, 2025)

Effect of oxygen concentration on volatile compounds and their formation in Keemun black tea fermentation - Yanqun Jiang; Zhenbin Chen; Jixin Zhang; Wei Zhao; Caiyan Sheng; Mingxia Lu; Tiehan Li; Jingming Ning (Food Research International, 2025)

Role of earthworms and their excretion products in reducing antimicrobial resistance and putative pathogens during vermicomposting - Ning Liu; David W. Graham; Yi Zhao; Xiao-Ru Yang; Gang Li; Yong-Guan Zhu (Chemical Engineering Journal, 2025)

Fabrication of flexible polymer-MOF composite electrolyte for solid-state lithium metal batteries with high rate performance - Jiansheng Gao; Yan Chai; Jialun Ni; Yong Zeng; Gaoyuan Zhang; Xueling Liu; De Ning; Xinghui Jin; Huajun Zhao; Dong Zhou; Rui Gao; Wei Wu; et al. (Chemical Engineering Journal, 2025)

Tailoring hetero-precursor transformation for simultaneous surface-coating and subsurface-doping of Ni-rich layered oxide cathodes - Junfan Zhang; Ran Wang; Kunkun Guo; Mohan Yang; Zenan Zhao; Jing Wang; Qi Liu; Lai Chen; Ning Li; Yuefeng Su; Feng Wu; Guoqiang Tan (Chemical Engineering Journal, 2025)

Dynamic covalent synthesis of highly-crystalline and fully-cyclized aromatic COF as an artificial interphase layer toward stable lithium metal batteries - Wei Shao; Da Xu; Tiantian Wang; Huanghao Pan; Ying Liu; Xue Gao; Jiahuan Luo; Jing Wang; Zhong-Kun Li; Yao Guo; Huihui Zhao; Ning Fu; et al. (Chemical Engineering Journal, 2025)

Efficient degradation of dye wastewater with a novel tribocatalytic process initiated by CQDs-Bi2MoO6 catalyst: Preparation, degradation, kinetics, DFT calculations and mechanism - Baoxiu Zhao; Yulu Xing; Yiran Xue; Ning Chen; Chaojun Sun; Mengfan Li; Huanxin Shi; Bingrui Ma; Songxue Wang; Yizhen Tang; Jie Liu (Chemical Engineering Journal, 2025)

Revealing the Effect of Pore Size Distribution Characteristics on Macroscopic Properties of Red Sandstone Under Instantaneous High Temperature Through the Lens of Shannon Entropy Theory - Lin Ning; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Yang Li; Yuhang Zhao; Xiaojiang Deng (Rock Mechanics and Rock Engineering, 2025)

Successful treatment of carbapenem-resistant Acinetobacter baumannii meningitis and purulent ventriculitis using cefiderocol combination therapy: a case report and literature review - Xuan Wang; Qihui Liu; Biwu Wu; Huaiyin Zhao; Jin Hu; Ning Li (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Risk prediction of catastrophic debris flows against the background of material changes and human engineering activity in the Wenchuan earthquake disturbance area - Jiang Xiong; Huayong Chen; Chuan Tang; Wanyu Zhao; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Jiangang Chen (Bulletin of Engineering Geology and the Environment, 2025)

Hybrid path planning methods for complete coverage in harvesting operation scenarios - Ning Wang; Zhiwen Jin; Tianhai Wang; Jianxing Xiao; Zhao Zhang; Hao Wang; Man Zhang; Han Li (Computers and Electronics in Agriculture, 2025)

Rice farming mediated internal competition and reduced external risks during the Neolithic period - Xiaolong Chen; Yan Liu; Xiaoshuang Zhao; Shihao Liu; Ning Zhao; Xiaohe Lai; Jing Chen; Maotian Li; Qianli Sun (Quaternary Science Reviews, 2025)

Qualities and bitter substances profile of Chinese winter jujube (Ziziphus jujuba Mill. cv. Dong zao) under the ultra-low oxygen environment - Xiaoxue Li; Xiaomei Zhao; Shaojin Wang; Bin Wu; Yuxing Du; Chenghu Dong; Zhonghong Wu; Fang Sun; Jiahui Wu; Li Wang; Ning Liu; Boya Zhang; et al. (Postharvest Biology and Technology, 2025)

Degradation mechanism of octadecylamine and 4-dodecylmorpholine in Salk Lake Brine under UV light - Taotao Liu; Wenwen Nie; Wei Song; Tong Zhou; Haiying Tang; Xinghai Li; Xuefeng Yu; Guoyu Zhang; Ning Zhao; Changsong Wang (Journal of Environmental Chemical Engineering, 2025)

Regulating the valence and size of the active center of Co/Al2O3 catalyst improved the performance and selectivity of NH3-SCO - Shengyi Wu; Jiaxin Li; Junjun Qiu; Chunxue Wang; Fei Wang; Zhao Li; Ping Ning; Kai Li (Journal of Environmental Sciences, 2025)

The dual effects of NADESs on inhibiting acyl transfer and improving the sn-1,3 positional selectivity of lipase contribute to the selective and efficient synthesis of 1,3-diacylglycerol - Duan Zhou; Mouming Zhao; Xiaorong Zhong; Ning Liu; Xuefeng Chen; Daoming Li (Food Research International, 2025)

Green biotechnological synthesis of rare sugars/alcohols: D-allulose, allitol, D-tagatose, L-xylulose, L-ribose - Xin Wen; Mesfin Angaw Tesfay; Yuhang Ning; Huibin Lin; Guangwen Liu; Hongtao Hu; Xixian Xu; Xingbo Jiang; Chunxia Zhao; Yilin Ren; Can Li; Chengjia Zhang; et al. (Food Research International, 2025)

Sucrose laurate and nisin synergistically inhibit Bacillus subtilis by multiple antibacterial targets and play promising application potential in bread preservation - Danya Tong; Panpan Han; Mingrui Li; Zhixin Wang; Zhen Zhao; Yingmin Jia; Yawei Ning (Food Chemistry, 2025)

Innovative manufacturing process to enhance the taste and color of Ancha tea: A comprehensive analysis using sensory evaluation, chemometrics, and metabolomics - Zhenbin Chen; Yanqun Jiang; Zhibin Ye; Wei Zhao; Jixin Zhang; Wenjing Huang; Yida Wu; Tiehan Li; Qian Xu; Jingming Ning (Food Bioscience, 2025)

Construct favorable solid electrolyte interphase by applying alternating current discharge during battery formation - Yulong Zhang; Shiyou Li; Meiling Wu; Lijuan Wang; Ning He; Yin Quan; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2025)

Ruthenium-doped carbon dots with “three-in-one” chemodynamic, photodynamic, and photothermal activity induce panoptosis for tumor therapy - Xiaokang Lu; Weijie Sun; Xingye Zheng; Lishen Yang; Tan Feng; Xiaoqin Deng; Fengqi Zhou; Hongmin Zhu; Ding Ma; Bilian Li; Guobao Ning; Hang Chen; et al. (Chemical Engineering Journal, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

AGV Scheduling and Energy Consumption Optimization in Automated Container Terminals Based on Variable Neighborhood Search Algorithm - Ning Zhao; Rongao Li; Xiaoming Yang (Journal of Marine Science and Engineering, 2025)
Automated Guided Vehicles (AGVs) for automated container terminals are mainly used for horizontal transportation at the forefront of the terminal. They shoulder the responsibility of container transportation between the quay cranes and yard cranes. Optimizing their scheduling can not only improve operational efficiency, but also help reduce energy consumption and promote green development of the port. This article first constructs a mathematical model with the goal of minimizing the total energy consumption of AGVs, considering the impact of different states of AGVs on energy consumption during operation. Secondly, by using the variable neighborhood search algorithm, the AGV allocation for container operation tasks is optimized, and the operation sequence is adjusted to reduce energy consumption. The algorithm introduces five types of operators and a random operator usage order to expand the search range and avoid local optima. Finally, the influence of the number and speed of AGVs on the total energy consumption is discussed, and the optimization performance of the variable neighborhood search algorithm and genetic algorithm is compared through computational experiments. The research results show that the model and variable neighborhood search algorithm proposed in this paper have a significant effect on reducing the total energy consumption of AGVs and show good stability and practical application potential.

Biochar promotes the dissolution of inorganic inactive phosphorus by mediating the bacterial community during corn stover and cattle manure composting - Linqin Zhao; Ying Li; Bowen Fan; Mengmeng Wang; Ning Sun; Fengjun Yang (Chemosphere, 2025)

Enhanced iodinated disinfection byproducts formation in iodide/iodate-containing water undergoing UV-chloramine sequential disinfection: Machine learning-aided identification of reaction mechanisms - Zhen-Ning Luo; Huan He; Tian-Yang Zhang; Xiu-Li Wei; Zheng-Yu Dong; Meng-Yuan Xu; Heng-Xuan Zhao; Zheng-Xiong Zheng; Ren-Jie Pan; Chen-Yan Hu; Chao Zeng; Mohamed Gamal El-Din; et al. (Water Research, 2025)

Fecal microbiota transplantation: transitioning from chaos and controversial realm to scientific precision era - Xinjun Wang; Di Zhao; Dexi Bi; Long Li; Hongliang Tian; Fang Yin; Tao Zuo; Gianluca Ianiro; Ning Li; Qiyi Chen; Huanlong Qin (Science Bulletin, 2025)

Efficient fluconazole degradation by activating peroxymonosulfate with LDH-coated nickel foam: Synergism of radical and non-radical pathways - Xiang-Yang Li; Ling-Xi Zhao; Meng Xie; Ning Liu; Xiang-Feng Chen; Ru-Song Zhao (Journal of Water Process Engineering, 2025)

A novel framework for river organic carbon retrieval through satellite data and machine learning - Shang Tian; Anmeng Sha; Yingzhong Luo; Yutian Ke; Robert Spencer; Xie Hu; Munan Ning; Yi Zhao; Rui Deng; Yang Gao; Yong Liu; Dongfeng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Population migration with improved productivity caused a heterogeneity pattern of Holocene vegetation succession in typical areas of the lower Yangtze region - Li Xiao; Xiaoyu Zhang; Jinqi Dai; Xueming Li; Ning Zhao; Shihao Liu; Jing Chen; Maotian Li; Yuanhao Sun; Haoyan Wang; Kai Li; Yan Liu; et al. (Global and Planetary Change, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Efficient adsorption behavior of Fe-based ternary magnetic LDHs for naphthalene acetic acid: Role of Fe element - Ning Liu; Ti-Bo Fang; Ling-Xi Zhao; Na Li; Xiang-Feng Chen; Ru-Song Zhao (Environmental Research, 2025)

Coupling zinc oxide nanopatterns with low-power acoustics for synergistic two-phase cooling enhancement - Junsheng Hou; Dongyu Li; Li Ma; Ning Wei; Lei Huang; Xiong Zhao; Jinjia Wei; Nanjing Hao (Chemical Engineering Journal, 2025)

Core-shell hydrogel microspheres with sequential delivery of cerium oxide nanoparticles and spinal white matter extracellular matrix for improved functional recovery in spinal cord injury - Yixiang Ai; Chunping Hu; Yifan Wang; Youjun Liu; Renfeng Liu; Hailiang Xu; Hui Li; Yuqi Zhao; Yuhao Wang; Ruojie Ning; Cheng Ju; Weidong Wu; et al. (Chemical Engineering Journal, 2025)

Sustainable aviation fuel (SAF) from lignin: Pathways, catalysts, and challenges - Xianqing Lv; Chengke Zhao; Ning Yan; Xinbing Ma; Shixing Feng; Li Shuai (Bioresource Technology, 2025)

Uncovering the microbial community dynamics and metabolic pathways of primary organic acids in Sichuan Baoning vinegar through metagenomics - Aiping Liu; Jie Wu; Jianlong Li; Qin Li; Ning Zhao; Kaidi Hu; Shuliang Liu; Giuseppe Blaiotta; Jiang Zhou (World Journal of Microbiology and Biotechnology, 2025)

A wild-allele GsPP2C-51-a1 enhances tolerance to drought stress in soybean and Arabidopsis - Cheng Liu; Xianlian Chen; Wei Han; Xiaoshuai Hao; Liang Qin; Wei Luo; Lizhi Zhao; Ning Li; Lei Sun; Jiaoping Zhang; Guangnan Xing; Jianbo He; et al. (Theoretical and Applied Genetics, 2025)

SETD3-mediated histidine methylation of MCM7 regulates DNA replication by facilitating chromatin loading of MCM - Hongguo Duan; Shuang Wang; Wen-Jie Shu; Yongjia Tong; Hai-Zhen Long; Guohong Li; Hai-Ning Du; Meng-Jie Zhao (Science China Life Sciences, 2025)

Rapid Mapping of Quantitative Trait Loci for the Growth Habit in Peanuts Using Bulked Segregant Analysis - Qia Ning; Li Li; Hailong Liu; Xiaoshu Chen; Yongchao Lv; Xiaoping Sun; Yue Zhao; Meijun Li; Huayuan Gao; Yu Han; Ridan Sun; Lianxi Zhang (Plant Molecular Biology Reporter, 2025)

Inhibition of STRA6 suppresses NSCLC growth via blocking STAT3/SREBP-1c axis-mediated lipogenesis - Yue Zhou; Rong Zhou; Ning Wang; Tingfeng Zhao; Pan Qiu; Chenzi Gao; Meijia Chang; Ning Lin; Xu Zhang; John Zhong Li; Qian Wang (Molecular and Cellular Biochemistry, 2025)

Roles of straw return in shaping denitrifying bacteria in rice rhizosphere soils through effects on root exudates and soil metabolites - Pei Chen; Yu Cheng; Ning Wang; Jian-Guang Yu; Ying Zhao; Li-Hong Xue (Soil Ecology Letters, 2025)

Interaction of microalgae, nitrogen and arsenic in a water environment co-polluted by nitrogen and arsenic: current knowledge and future perspectives - Youwen Li; Xinxin Zhao; Zhaoqi Zhong; Fanfan Ju; Hui Liu; Ning Lin; Xianghao Zha (Aquatic Ecology, 2025)

Design and Testing of an autonomous laser weeding robot for strawberry fields based on DIN-LW-YOLO - Peng Zhao; Junlin Chen; Jiahao Li; Jifeng Ning; Yongming Chang; Shuqin Yang (Computers and Electronics in Agriculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Adaptive responses of Alicyclobacillus acidoterrestris in acidic broth and fruit juices: Focus on the influences of organic acids and temperature conditions - Ning Zhao; Yi Zhang; Jun Li; Junnan Xu; Lingxia Jiao; Kaidi Hu; Qin Li; Jianlong Li; Aiping Liu; Mingtao Fan; Shuliang Liu (International Journal of Food Microbiology, 2025)

Pacific Walker Circulation modulated millennial-scale East Asian summer monsoon rainfall variability over the past 40 kyr - Yi Zhong; Yuxing Liu; Xiaojing Du; Xiaoxu Shi; Xing Xu; Zhengyao Lu; Stefanie Kaboth-Bahr; Mark J. Dekkers; Juan C. Larrasoaña; Keiji Horikawa; Chijun Sun; Liang Ning; et al. (Global and Planetary Change, 2025)

Study on the kinetics and reaction mechanism of low-temperature oxidation of lignite with different coalification - Jianqiao Zhao; Zheng Wei; Chang Shi; En Meng; Bingchen Gu; Ning Li; Shi Yu; Xianliang Meng; Ruizhi Chu; Guoguang Wu; Xiaofeng Jiang; Xiao Li; et al. (Fuel, 2025)

Defect confinement in CuO/HZSM-5-T catalysts: A novel approach for enhancing stability in AsH3 catalytic oxidation - Xinyu Yang; Ziruo Zeng; Zhao Li; Yaxi Zhang; Wei Mao; Zhongxian Wang; Xin Sun; Kai Li; Fei Wang; Ping Ning (Fuel, 2025)

In-depth study on the good resistance to coke deposition of SAPO-34/ZSM-5/quartz composite zeolite film with hierarchical structure in MTA reaction - Ning Li; Pengcheng Li; Jianqiao Zhao; Huili Liu; Jiayun Tang; Ruizhi Chu; Xianliang Meng; Chenxiao Wang; Weisong Li; Xiao Li (Fuel, 2025)

Current advances in the biosynthesis and sustainable production strategies of carotenoids and their multifaceted applications in the food industry: A comprehensive review - Die Zhao; Chunji Li; Nan Zeng; Dandan Wang; Ning Zhang; Bingxue Li (Food Bioscience, 2025)

Highly electrostatic cellulose acetate materials assisted by copper ion coordination for air filtration - Ning Yan; Ting Gao; Li Hua; Fan Xie; Rui-Xin Liu; Ding-Gen Hu; Zhao-Qing Lu (Chemical Engineering Journal, 2025)

Solid-state ion-conductive elastomers with high mechanical robustness and ion-conductivity for highly durable triboelectric nanogenerators - Fangyan Ou; Xinze Li; Liang Tuo; Zhichao Zhang; Wei Tang; Ting Xie; Chuang Ning; Wenyu Pan; Qizhi Chen; Qihua Liang; Zhiyong Qin; Wei Gao; et al. (Chemical Engineering Journal, 2025)

Stem cells vesicles-loaded type I pro-photosensitizer for synergetic oxygen-independent phototheranostics and microenvironment regulation in infected diabetic wounds - Qin Zeng; Ying Zhang; Judun Zheng; Jingyan Lin; Ning Li; Minghai Zhao; Xu Chen; Xipeng Li; Meijiao Zhao; Jialin Huang; Qiulin Xie; Ronghua Yang; et al. (Chemical Engineering Journal, 2025)

An All-Solid-State fluorinated Ion-Conductive elastomer with outstanding mechanical properties and high environmental stability for flexible electronics - Zequan Li; Changsheng Wang; Xueying Duan; Xiangning He; Fuqi Wang; Chuang Ning; Muqun Wang; Zhiyong Qin; Wei Gao; Shuangliang Zhao (Chemical Engineering Journal, 2025)

Butterfly-shaped dendrimers with photosensitizer recruitment function for enhanced light-controlled precise cascaded ROS and NO release in multimodal diabetic foot ulcers infections treatment - Xiangyu Huang; Zucheng Shen; Qi Deng; Chengfei Zhao; Xiaofeng Cai; Shaoteng Huang; Mingbo Zhang; Yanzhuo Lv; Dongliang Yang; Junyang Zhuang; Ning Li (Chemical Engineering Journal, 2025)

Precipitation regulates soil organic carbon affected by shrub encroachment along the altitude gradient - Li Liu; Guang Zhao; Daijun Yao; Ning Zong; Yunlong He; Wenchao Wu; Qianxin Jiang; Yangjian Zhang (CATENA, 2025)

Spatiotemporal Mapping of the Oxytocin Receptor at Single-Cell Resolution in the Postnatally Developing Mouse Brain - Hao Li; Ying Li; Ting Wang; Shen Li; Heli Liu; Shuyi Ning; Wei Shen; Zhe Zhao; Haitao Wu (Neuroscience Bulletin, 2025)
The oxytocin receptor (OXTR) has garnered increasing attention for its role in regulating both mature behaviors and brain development. It has been established that OXTR mediates a range of effects that are region-specific or period-specific. However, the current studies of OXTR expression patterns in mice only provide limited help due to limitations in resolution. Therefore, our objective was to generate a comprehensive, high-resolution spatiotemporal expression map of Oxtr mRNA across the entire developing mouse brain. We applied RNAscope in situ hybridization to investigate the spatiotemporal expression pattern of Oxtr in the brains of male mice at six distinct postnatal developmental stages (P7, P14, P21, P28, P42, P56). We provide detailed descriptions of Oxtr expression patterns in key brain regions, including the cortex, basal forebrain, hippocampus, and amygdaloid complex, with a focus on the precise localization of Oxtr + cells and the variance of expression between different neurons. Furthermore, we identified some neuronal populations with high Oxtr expression levels that have been little studied, including glutamatergic neurons in the ventral dentate gyrus, Vgat + Oxtr + cells in the basal forebrain, and GABAergic neurons in layers 4/5 of the cortex. Our study provides a novel perspective for understanding the distribution of Oxtr and encourages further investigations into its functions.

A Zinc Uptake Transporter ZIP1-II Is Involved in Zinc Accumulation in the Hepatopancreas of Pacific Oyster Crassostrea gigas - Ning Kong; Cong Luo; Mengjia Wang; Junyan Zhao; Xiang Li; Lingling Wang; Linsheng Song (Marine Biotechnology, 2025)

From metabolomics to therapeutics: identifying causal metabolites and potential drugs for the treatment of osteoarthritis - Heng Li; Jingyan Sun; Jiewen Zhang; Yang Chen; Yiwei Zhao; Ruomu Cao; Ning Kong; Xudong Duan; Huanshuai Guan; Run Tian; Kunzheng Wang; Pei Yang (Inflammopharmacology, 2025)

Investigating residual trace metals in recombinant monoclonal antibodies to facilitate drug development with LC-UV-ICPMS-HRMS - Xueqing Zhao; Jikang Wu; Yu Zhang; Hongxia Wang; Haibo Qiu; Ning Li (Analytica Chimica Acta, 2025)

High-efficiency fungicide screening and field control efficacy of maize southern corn rust - Yigeng Wang; Yifei Shao; Xiaoyan Zhao; Qinghui Pei; Ning Nan; Fengwen Zhang; Xingyin Jiang; Xiangdong Li (Crop Protection, 2025)

A smartphone-based enhanced colorimetric immunoassay for the detection of Trichinella spiralis infection - Yao Yu; Lianjing Zhao; Nuo Xu; Xiaolei Liu; Lin Li; Ning Xu; Xue Bai (Veterinary Parasitology, 2025)

Rare tumor list provide vast opportunities for novel drug development in China - Rongshou Zheng; Shuhang Wang; Guo Zhao; Wenqiang Wei; Ning Li (Science Bulletin, 2025)

The measurement of agricultural disaster vulnerability in China and implications for land-supported agricultural resilience building - Yuheng Li; Guangya Gao; Jiuyao Wen; Ning Zhao; Guoming Du; Monika Stanny (Land Use Policy, 2025)

Probe on the pivotal role of green rust in improving the enzymatic activity and facilitating the formation of 1O2 in Fenton-like process for degradation of 4-chlorophenol - Jie Peng; Meng Li; Qian Zhang; Zefeng Li; Ziqi Zhao; Yuwei Ding; Ning Du (Journal of Environmental Management, 2025)

Integrating spatial-temporal features into prediction tasks: A novel method for identifying the potential water pollution area in large river basins - Yuqing Tian; Yanhui Zhao; Zhiqiang Yin; Ning Deng; Sen Li; Hailong Zhao; Bo Huang (Journal of Environmental Management, 2025)

Stalagmite records of spatiotemporal hydroclimatic variations in monsoonal China during 47–12 ka BP - Miaomiao Wang; Haiwei Zhang; Youwei Li; Rui Zhang; Jian Wang; Hanying Li; Yuteng Zhao; Xiaomei Zhang; Zeyuan Liang; Youfeng Ning; Hai Cheng (Global and Planetary Change, 2025)

Effect of micro-granular activated carbon on bacteriophage MS2 removal and fouling control in flat-plate MBR - Yikan Zhao; Yingxue Sun; Yuting Han; Jiahao Li; Ning Ding; Toshiyuki Shibata; Qianyuan Wu (Environmental Research, 2025)

3D CFD-DEM modeling of sand production and reservoir compaction in gas hydrate-bearing sediments with gravel packing well completion - Xiaofeng Dou; Zhichao Liu; Dianheng Yang; Yingjie Zhao; Yanlong Li; Deli Gao; Fulong Ning (Computers and Geotechnics, 2025)

Triple modifications of Li-rich manganese-based cathode materials using LiMnPO4 one-step method - Jianan Hao; Jinyang Dong; Yuefeng Su; Kang Yan; Jiayu Zhao; Huiquan Che; Yun Lu; Ning Li; Bin Zhang; Ping Zhang; Feng Wu; Lai Chen (Chemical Engineering Journal, 2025)

Experimental Investigation on Mechanical Behaviors and Damage Evolution of Soft Rock Analog Containing Internal Fracture Network - Yang Zhao; Lishuai Jiang; Jianguo Ning; Pimao Li; Yiming Yang; Chaolei Wu; Quansen Wu; Quanlin Wu (Rock Mechanics and Rock Engineering, 2025)

A winter cold nights pattern in the Northern Hemisphere lands: Circum–hemisphere teleconnection of extreme cold events - Ning Wang; Jianping Li; Hao Wang; Hao Li; Zixiang Wu; Hongyuan Zhao (Climate Dynamics, 2025)

Novel robust GNSS velocity estimation with a residual-based multithreshold constraint algorithm - Yanlong Liu; Zengke Li; Yipeng Ning; Jingxiang Gao; Kefan Shao; Zhisheng Zhao (GPS Solutions, 2025)

gCMEbox: A MATLAB toolbox for extracting and analyzing common-mode errors from GNSS time series - Shuangcheng Zhang; Jun Li; Lijiang Zhao; Anmin Zeng; Feng Ming; Ning Liu; Xiongchuan Chen; Zhijie Feng; Hengli Wang (Advances in Space Research, 2025)

Research on improvement strategies for a lightweight multi-object weed detection network based on YOLOv5 - Jiandong Sun; Jinlong You; Fengmei Li; Jianhong Sun; Mengjiao Yang; Xueguan Zhao; Ning Jin; Haoran Bai (Crop Protection, 2024)

Rich nutrition decreases the concentration of metals in Chaeturichthys stigmatias - Tao Yang; Jinghua Wang; Hua Guo; Yongsong Zhao; Haozhong Tian; Yingying Li; Guangliang Teng; Ning Liu (Marine Pollution Bulletin, 2024)

Effect of the LIF gene on the cell cycle and apoptosis of ovarian granulosa cells in white Muscovy ducks - Qing-hua Tao; Ning-ning Sun; Meng-shi Wang; Wan-xin Zhao; Wei Liu; Xu Zhang; Ang Li (Theriogenology, 2024)

Temperature sensitivity of soil respiration to elevated temperature and nitrogen availability - Yufei Li; Kaiping Zhang; Yuling Li; Pingxing Wan; Zhongke Zhou; Wucheng Zhao; Ningning Zhang; Ning Chai; Zhixin Li; Yalan Huang; Feng Zhang (Soil and Tillage Research, 2024)

Remediation of multi-metal(loid) contaminated soils using Mn-modified biochar: Mechanistic insights and influencing factors - Jin-Zhou Su; Xiao-Ning Feng; Ping Xiang; Zhao-Lai Guo; Li-Xin Li; Tao Zhang; Jun-Bao Yu (Process Safety and Environmental Protection, 2024)

Flow induced acoustic characteristics analysis of propulsion pump by indirect acoustic variable method and FEM - Zhengchuan Zhang; Bo Gong; Tao Chen; Ning Li; Yongxin Jin; Heng Jiang; Jianfu Zhao; Kai Li (Ocean Engineering, 2024)

From insects to mammals! Tissue accumulation and transgenerational transfer of micro/nano-plastics through the food chain - Yijing Wang; Xinrui Nan; Huayang Sun; Yutian Shi; Jixing Miao; Yuheng Li; Xiaoyu Han; Ning Zhang; Huaqin Wang; Nanqi Ren; Xin Zhao; Baoqin Liu (Journal of Hazardous Materials, 2024)

Application of electrochemical flow-through oxidation technology in the treatment of concentrated water from nanofiltration and reverse osmosis in the coal chemical industry - Ning Liu; Xin Zhao; Can Wang; Yanchao Li; Shuang Pan; Weiqi Huang; Israel Hakizimana; Wei Kong; Yan Wang (Journal of Environmental Chemical Engineering, 2024)

Chiral FeNC single-atom nanozymes with multi-enzyme activity for dye degradation - Guobao Ning; Huan Liang; Linjiang Guo; Xiaokang Lu; Lin Xiao; Tianle Qi; Hui Zhao; Can-Peng Li (Journal of Environmental Chemical Engineering, 2024)

Metagenomics reveals differences in spore-forming bacterial diversity in raw milk in different regions and seasons in China - Ning Li; Wenjun Xu; Lu Meng; Yankun Zhao; Xiaowei Zhao; Nan Zheng; Yangdong Zhang; Jiaqi Wang (Food Research International, 2024)

Overexpression of ZlMYB1 and ZlMYB2 increases flavonoid contents and antioxidant capacity and enhances the inhibition of α-glucosidase and tyrosinase activity in rice seeds - Wanhong Li; Yali Li; Bintao Zhang; Qing Ma; Hehe Hu; Anming Ding; Lianguang Shang; Zhaohui Zong; Weicai Zhao; Hao Chen; Hongbo Zhang; Zhongfeng Zhang; et al. (Food Chemistry, 2024)

Physical properties and antioxidant activity of curcumin‑zinc metal-organic frameworks - Li-Hang Chen; Tao Chen; Ru-Nan Zhao; Di Wu; Yi-Nan Du; Jiang-Ning Hu (Food Chemistry, 2024)

Vine tea kombucha ameliorates non-alcoholic fatty liver disease in high-fat diet fed mice via antioxidation, anti-inflammation and regulation of gut microbiota - Jin Cheng; Si-Yu Huang; Ruo-Gu Xiong; Si-Xia Wu; Zhi-Jun Yang; Dan-Dan Zhou; Adila Saimaiti; Cai-Ning Zhao; Hui-Lian Zhu; Hua-Bin Li (Food Bioscience, 2024)

Deep enzymatic hydrolysis of bee pollen with multiple enzymes: Improves nutrient release and potential biological activity of bee pollen - Keju Li; Jiaqi Zhao; Wenjie Yu; Yaxun Qiao; Xin Shu; Fangjian Ning; Liping Luo (Food Bioscience, 2024)

Nanoencapsulation enhances the antimicrobial and antioxidant stability of cyclic lipopeptides for controlling Fusarium graminearum - Yanjie Yi; Youtian Shan; Pengyu Luan; Zhongke Sun; Xingquan Wu; Zhiwen Ning; Zhengkun Chen; Yunxiang Zhang; Shuyun Zhao; Chengwei Li (Food Microbiology, 2024)

Hepcidin defense patterns in intestine of mandarin fish (Siniperca chuatsi) against Aeromonas hydrophila infection - Jin-hua Gao; Jin-liang Zhao; Ning-xin Guo; Temesgen Tola; Wen-bo Xue; Kang-ning Cai; Xiao-li Yao; Miao Hu (Fish & Shellfish Immunology, 2024)

Simulation study on static pressure crushing performance of demolished reinforced concrete beams for recycling - Jiaqian Ning; Jianzhuang Xiao; Qiong Liu; Long Li; Zengfeng Zhao (Engineering Structures, 2024)

Skin-inspired bimodal pressure sensor for static and dynamic intelligent interactive perception system - Ning Li; Jianwen Liu; Songfang Zhao; Yang Li; Qin Wei (Chemical Engineering Journal, 2024)

Design and optimization of novel vortex microreactors for ultrasound-assisted synthesis of high-performance Fe3O4 nanoparticles - Su Wang; Jiaxiang Zhang; Kaixuan Ma; Wanyao Zhang; Yan Gao; Pengjie Yu; Shuangfei Zhao; Yirong Feng; Jiming Yang; Ruiyan Sun; Yuguang Li; Ning Zhu; et al. (Chemical Engineering Journal, 2024)

Dependence of the hydrate-based CO2 storage characteristics on sand particle size and clay content in unconsolidated sediments - Jiaxian Wang; Yunkai Ji; Changling Liu; Fulong Ning; Qingguo Meng; Yapeng Zhao; Jing Li; Zhun Zhang; Yongchao Zhang; Feng Cai (Chemical Engineering Journal, 2024)

Partitioned granular sludge coupling with membrane-aerated biofilm reactor for efficient autotrophic nitrogen removal - Ning Mei; Fangxu Jia; Hui Wang; Zhifeng Hu; Baohong Han; Yao Chen; Xingcheng Zhao; Xiangyu Han; Jingjing Zhang; Dongmei Li; Hong Yao; Jianhua Guo (Bioresource Technology, 2024)

Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.

Effects of Dietary 5-Aminolevulinic Acid on Growth, Nutrient Composition, and Intestinal Microflora in Juvenile Shrimp, Litopenaeus vannamei - Yiming Li; Yucong Ye; Yashi Zhu; Zongli Yao; Kai Zhou; Yuxing Wei; Lin Zhang; Ning Bao; Yunlong Zhao; Qifang Lai (Marine Biotechnology, 2024)

Dedolomitization arises the knife-like structure of dolostone: insights from the oolitic dolostone of Cambrian Zhangxia formation, North China Craton - Zhe-Xin Cai; Shan-Shan Li; Yi-Ning He; Tao Cui; Xin-Yu Wu; Hao-Cheng Yu; Zhao-Liang Hou; Yu-Tian Tao; Da Wang; Kun-Feng Qiu (Carbonates and Evaporites, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Unravelling the nature differences of halide anions affecting the sorption of U(VI) by hydrous titanium dioxide supported waste polyacrylonitrile fibers in the presence of carbonates - Cheng Wang; Jun Liu; Bingtao Gui; Chao Li; Junxiang Shu; Shuwen An; Changsong Zhao; Juan Zhai; Ning Liu; Tu Lan (Science of The Total Environment, 2024)

Green synthesis of diatom–allophane bio-nanocomposites for highly efficient oxytetracycline adsorption - Mengyuan Li; Shun Wang; Dong Liu; Dusan Losic; Ning Zhao; Qian Tian; Yuguo Shen; Rongda Yu; Hao Liu; Qiyi Ma; Peng Yuan (Science of The Total Environment, 2024)

Synergistic management of nitrogen contamination in overflow wastewater and algal proliferation in lake receiving wastewater based on electrochemical oxidation process - Ya-Ning Wang; Ding Li; Lin Liu; Jia-Fang Xie; Zhi-Tang Lyu; Quan-Bao Zhao; Yu-Ming Zheng (Process Safety and Environmental Protection, 2024)

Biocontrol potential of nicotinamide from Arachis hypogaea roots against Meloidogyne incognita - Jianqing Ma; Zixuan Wang; Li He; Keran Li; Ning Wang; Gangyong Zhao; Dandan Cao (Physiological and Molecular Plant Pathology, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Impacts of nitrogen (N), phosphorus (P), and potassium (K) fertilizers on maize yields, nutrient use efficiency, and soil nutrient balance: Insights from a long-term diverse NPK omission experiment in the North China Plain - Ning Wang; Zhipin Ai; Qiuying Zhang; Peifang Leng; Yunfeng Qiao; Zhao Li; Chao Tian; Hefa Cheng; Gang Chen; Fadong Li (Field Crops Research, 2024)

Metagenomic insights into the influence of pH on antibiotic removal and antibiotic resistance during nitritation: Regulations on functional genus and genes - Ning Guo; Hengyi Zhang; Lin Wang; Zhuhui Yang; Zhao Li; Daoji Wu; Feiyong Chen; Zhaoliang Zhu; Li Song (Environmental Research, 2024)

Facilitating Response/Recovery of cellulosic humidity sensor by Densificating fibril Arrays - Mengru Geng; Jiaqi Zhao; Jie Li; Boyue Liu; Ruiming Liu; Xiaojuan Wang; Wanlong Song; Mingzhe Shao; Yihao Luan; Qun Li; Meng Gao; Fengshan Zhang; et al. (Chemical Engineering Journal, 2024)

Novel strategies for enhancing energy metabolism and wastewater treatment in algae-bacteria symbiotic system through carbon dots-induced photogenerated electrons: The definitive role of accelerated electron transport - Chi Zhang; Mingwei Zhou; Yiming Zhang; Dapeng Li; Ning Hou; Xinyue Zhao (Chemical Engineering Journal, 2024)

From Skin to Gut: Understanding Microbial Diversity in Rana amurensis and R. dybowskii - Ming-he Yang; Hong Liu; Hao Wang; Zhao-ning Lu; Xiao-yun Han; Zhi-wen Luo; Li-gang Wu; Qing Tong (Current Microbiology, 2024)

Stable isotopic evidence of cadmium enrichment in soils of black shale distribution areas - Wanfu Zhao; Yinxian Song; Wei Li; Dongxing Guan; Tao Li; Chao Guo; Ning Wei; Junfeng Ji (Applied Geochemistry, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Spatiotemporal distribution and inter-media transfer of polycyclic aromatic hydrocarbons in Shanghai, China: Historical patterns and future trends - Ting Li; Ning Nie; Yiyi Miao; Dengzhong Zhao; Min Liu (Science of The Total Environment, 2024)

Sea surface carbon dioxide during early summer at the Tuandao nearshore time series site - Lu Cao; Yongqi Qiu; Liang Xue; Yingying Zhang; Shuwei Zhang; Ning Wu; Da Yuan; Quanlong Li; Zheng Zhao; Ning Wang; Yan Zhou; Wei Yang; et al. (Marine Environmental Research, 2024)

Complete genome sequence of the 4-hydroxybenzoate-degrading bacterium Gymnodinialimonas sp. 57CJ19, a potential novel species from intertidal sediments - Dong-Hui Li; Ning Zheng; Zhen-Hai Liu; Xiao-Rui Dong; Chen Zhao; Shi-Gan Yan; Bin-Bin Xie (Marine Genomics, 2024)

An accurate and efficient forecast framework for fine PM2.5 maps using spatiotemporal recurrent neural networks - Ning Liu; Bin Zou; Yi Li; Zengliang Zang; Shan Xu; Sha Li; Shenxin Li; Lu Zhi; Jun Chen; Fang Zhao (Journal of Cleaner Production, 2024)

Nonradical peroxymonosulfate activation via high-level pyrrolic-nitrogen and electron-deficient carbon at 2D ultrathin carbonaceous nanosheets for efficient BPA removal - Ning Zhang; Haibin Wu; Yueshuang Mao; Huazhang Zhao; Jianfeng Li (Journal of Environmental Chemical Engineering, 2024)

3D DEM investigation on macro-meso mechanical responses of gas hydrate-bearing sediments in process of unloading confining pressure - Xiaofeng Dou; Qi Wu; Zhichao Liu; Yingjie Zhao; Yanlong Li; Zhangxin Chen; Deli Gao; Fulong Ning (Gas Science and Engineering, 2024)

Characteristics of dietary patterns, and serum metabolites during the low-gluten diet among Chinese young adults - Ning Wang; Qianhui Zhang; Li Zhang; WenWei Lu; Yue Xiao; Hongchao Wang; Wei Chen; Feng Zhang; JianXin Zhao (Food Bioscience, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

MiR-210, not let-7, regulates Akt gene expression against Vibrio splendidus infection in the sea cucumber Apostichopus japonicus - Li Liu; Bingyu Ning; Yaoyao Zhan; Tanjun Zhao; Yaqing Chang (Fish & Shellfish Immunology, 2024)

Corrigendum to “Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig” [Environ. Pollut. 329 (2023) 121729] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2024)

Surface phosphorylated Li5FeO4 prelithiation additive synergistically improves the air-stability and lithium-ion conductivity - Lei Niu; Meiling Wu; Yulong Zhang; Cankun Gao; Xin Li; Hao Ding; Ning He; Peng Wang; Jiawen Zhang; Jingxuan Yan; Ningshuang Zhang; Dongni Zhao; et al. (Chemical Engineering Journal, 2024)

Adaptive shifts in constructed wetland microbial communities and GHG emissions under different NPs concentrations disturbances - Xinyue Zhao; Tuoshi Zhang; Ming Jin; Aiqi Sha; Wei Li; Ning Hou (Chemical Engineering Journal, 2024)

Salt Stress Induces Complicated miRNA Responses of Sugar Beet (Beta vulgaris L.) - Ziqiang Zhang; Zengjuan Fu; Wenjin Chen; Liang Wang; Shangmin Zhao; E Yuanyuan; Hui Zhang; Bizhou Zhang; Mengyuan Sun; Wenzhe Zheng; Jing Dong; Zhiqi Zhang; et al. (Sugar Tech, 2024)

Effects of combined biochar and maize straw applications on soil greenhouse gas emissions - Yongchun Zhou; Zili Zhao; Danyang Li; Liulin Wu; Zhimin Chen; Ning An; Jinrong Yang; Yapeng Wang (Applied Soil Ecology, 2024)

Research on In Situ Observation Method of Plankton Based on Convolutional Neural Network - Chengzhi Yuan; Zhongjie He; Chunlin Ning; Weimin Wang; Jinkai Zhao; Guozheng Yuan; Chao Li (Journal of Marine Science and Engineering, 2024)
The marine ecosystem is one of the most extensive and abundant ecosystems on Earth. Marine plankton is an important component, and its abundance, number of species, and dominant species are regarded as important monitoring indicators. Aiming at the problems of low accuracy and high complexity in identifying plankton based on convolutional neural networks, this study proposes a lightweight identification algorithm for plankton images based on the improved MobileNetV2. Firstly, the network layer structure is extracted by redesigning features to balance the depth and width of the network to reduce the model parameters; secondly, the lightweight coordinate attention (CA) mechanism is introduced to strengthen the attention and extraction ability of key areas; in addition, the structure of the network classifier is optimized to improve the utilization efficiency of the model parameters. The results show that the model achieves a 95.46% accuracy and 94.48% recall in 12 kinds of images. Compared with the initial MobileNetV2, the parameters and calculation amount are reduced by 72.47% and 52.09%, respectively, and the reasoning time for a single image is 6.15 ms. The model realizes the accurate identification of plankton in situ under the premise of ensuring it is lightweight. Combining time information and depth data, it is of great significance for marine ecological environment monitoring and prediction to obtain the abundance of various plankton.

An ultra-efficient pretreatment method adopted LPUV/CoFe2O4/PMS-based photolysis for accurate detection of Cd(II) and Pb(II) in water via SWASV - Liya Feng; Renjie He; Haonan Li; Shaowen Chen; Cheng Lv; Shijie Zhang; Ning Liu; Yujie Shi; Gang Liu; Guo Zhao (Water Research, 2024)

Insights gained into the injury mechanism of drug and herb induced liver injury in the hepatic microenvironment - Xiaomeng Zhang; Qi Geng; Lin Lin; Lulu Zhang; Changqi Shi; Bin Liu; Lan Yan; Zhiwen Cao; Li Li; Peipei Lu; Yong Tan; Xiaojuan He; et al. (Toxicology, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

Recombinant strains expressing oxalate decarboxylase efficiently and environmental characteristics of their life cycle assessment - Ning Hou; Jian Wang; Xinyue Zhao; Rongchen Wang; Xin Zhao; Dapeng Li (Journal of Cleaner Production, 2024)

Reliable detection of malachite green by self-assembled SERS substrates based on gold–silicon heterogeneous nano pineapple structures - Yu-ning Liu; Jian-jun Li; Guo-jun Weng; Jian Zhu; Jun-wu Zhao (Food Chemistry, 2024)

Smartphone-assisted mobile fluorescence sensor for self-calibrated detection of anthrax biomarker, Cu2+, and cysteine in food analysis - Sheng Wang; Jun Xu; Fengzhi Yue; Lina Zhang; Ning Bi; Jian Gou; Yongxin Li; Yuanyuan Huang; Tongqian Zhao; Lei Jia (Food Chemistry, 2024)

An intelligent controlled release hydrogel with photothermal effect for the treatment of bone defects - Hewei Wei; Ting Zhao; Xinglong Liu; Qiteng Ding; Shuai Zhang; Jiali Yang; Ning Wang; Lifeng Zhang; Guodong Chai; Guofeng Xia; Anning Li; Chuanbo Ding; et al. (Chemical Engineering Journal, 2024)

Continuous deposition of pre-aged organic carbon in the southern Mariana Trench since the last deglaciation - Da-Wei Li; Mengna Chen; Shuai Liu; Hailong Zhang; Zicheng Wang; Xiaoyan Ning; Jiwei Tian; Meixun Zhao (Chemical Geology, 2024)

Recovery capacity of constructed wetlands in response to multiple disturbances: Microbial interaction perspective - Xinyue Zhao; Tuoshi Zhang; Jinyi Yang; Han Zhang; Lan Yang; Qinglin Li; Ning Hou (Bioresource Technology, 2024)

Direct and indirect impacts of fine root functional traits on decomposition and N loss - Zhiying Ning; Yulin Li; Xueyong Zhao; Jiannan Lu; Jin Zhan (Plant and Soil, 2024)

Effects of halophyte Suaeda salsa continuous cropping on physical and chemical properties of saline soil under drip irrigation in arid regions - Sihai Liu; Ning Wang; Dongze Li; Changyan Tian; Ke Zhang; Mingfang Hu; Haishan Niu; Zhenyong Zhao (Agriculture, Ecosystems & Environment, 2024)

Overcoming mechanistic limitations of process-based phenological models: A data clustering method for large-scale applications - Jiaojiao Tan; Gang Zhao; Qi Tian; Lei Zheng; Xiaofeng Kang; Qinsi He; Yu Shi; Bin Chen; Dingrong Wu; Ning Yao; Liang He; Amit Kumar Srivastava; et al. (Agricultural and Forest Meteorology, 2024)

More sensitive microbial responses to the interactive effects of warming and altered precipitation in subsoil than topsoil of an alpine grassland ecosystem - Qi Qi; Shijie Ning; Xue Guo; Jianshu Zhao; Renmao Tian; Haoran Gui; Jin‐Sheng He; Hao Wang; Zhenhua Zhang; Konstantinos T. Konstantinidis; Qun Gao; Yuxin Wang; et al. (Global Change Biology, 2024)
Subsoil is a large organic carbon reservoir, storing more than half of the total soil organic carbon (SOC) globally. Conventionally, subsoil is assumed to not be susceptible to climate change, but recent studies document that climate change could significantly alter subsoil carbon cycling. However, little is known about subsoil microbial responses to the interactive effects of climate warming and altered precipitation. Here, we investigated carbon cycling and associated microbial responses in both subsoil (30–40 cm) and topsoil (0–10 cm) in a Tibetan alpine grassland over 4 years of warming and altered precipitation. Compared to the unchanged topsoil carbon ( β = .55, p = .587), subsoil carbon exhibited a stronger response to the interactive effect of warming and altered precipitation ( β = 2.04, p = .021), that is, warming decreased subsoil carbon content by 28.20% under decreased precipitation while warming increased subsoil carbon content by 18.02% under increased precipitation.Furthermore, 512 metagenome‐assembled genomes (MAGs) were recovered, including representatives of phyla with poor genomic representation. Compared to only one changed topsoil MAG, 16 subsoil MAGs were significantly affected by altered precipitation, and 5 subsoil MAGs were significantly affected by the interactive effect of warming and precipitation. More than twice as many populations whose MAG abundances correlated significantly with the variations of carbon content, components and fluxes were observed in the subsoil than topsoil, suggesting their potential contribution in mediating subsoil carbon cycling. Collectively, our findings highlight the more sensitive responses of specific microbial lineages to the interactive effects of warming and altered precipitation in the subsoil than topsoil, and provide key information for predicting subsoil carbon cycling under future climate change scenarios.

Plant–Soil Moisture Positive Feedback Maintaining Alternative Stable States in the Alpine Marsh Ecosystem - Guorui Hu; Haonan Bai; Yunpeng Zhao; Ning Chen; Honglin Li; He Mao; Zengpeng Guo; Xiongjie Sheng; Hui Zhang; Hang An; Panhong Zhang; Zhengkuan Zhang; et al. (Ecology Letters, 2024)
A self‐reinforcing positive feedback is regarded as a critical process for maintaining alternative stable states (ASS); however, identification of ASS and quantification of positive feedbacks remain elusive in natural ecosystems. Here, we used large‐scale field surveys to search for ASS and a positive feedback mechanism under a wide range of habitats on the Tibetan Plateau. Using multiple methods, we proved that three stable states exist that accompany alpine marsh degradation. Positive feedbacks between changing soil moisture and plant community composition forced the ecosystem into another stable state, and the alteration of water use efficiency (WUE) of the component species contributed to this shift. This study provides the first empirical evidence that positive feedback loops maintain ASS in the alpine marsh ecosystem on the Tibetan Plateau. Our research revealed the powerful driving role of plants in transitions between states, which may support the conservation and restoration of global alpine marsh ecosystems.

Revealing the potential of quantum dot nanomaterials in photocatalytic applications - Le Zhao; Ping Zhang; Longjian Li; Ning Li; Reyila Tuerhong; Xiaoping Su; Wanhong Sun; Lijuan Han (Chemosphere, 2024)

Colletotrichum cliviicola as a new causal agent causing leaf spot disease on Tilia tomentosa moench (silver linden) in China - Lin Chang; Xue-hai Li; Yi-lin Li; Zi-wen Gao; Yue-mei Zhang; Ning-Li; Zhao-lei Qu; Yi-hong Yang; Hui Sun (Crop Protection, 2024)

Territorial spatial suitability assessment and optimization of coastal port reclamation in China - Gaoru Zhu; Panlong Zhao; Liguo Zhang; Xinyang Li; Wentao Ding; Huiying Yu; Ning Zhang; Siqi Yang; Chun Zhang; Zhenglei Xie (Ocean & Coastal Management, 2024)

Butylparaben induces glycolipid metabolic disorders in mice via disruption of gut microbiota and FXR signaling - Haining Du; Lili Cui; Xinyi Zhao; Ziteng Yu; Tianyue He; Boya Zhang; Xingpei Fan; Meimei Zhao; Ruijiao Zhu; Ziyi Zhang; Mengcong Li; Jiaxin Li; et al. (Journal of Hazardous Materials, 2024)

Loss of microbial functional diversity following Spartina alterniflora invasion reduces the potential of carbon sequestration and nitrogen removal in mangrove sediments—from a gene perspective - Zetao Dai; Ning Zhang; Feifei Wang; Yujie Li; Jiarui Peng; Tao Xiang; Xiaoyu Zhao; Shengchang Yang; Wenzhi Cao (Journal of Environmental Management, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Effects of dietary 5-aminolevulinic acid on growth performance and nonspecific immunity of Litopenaeus vannamei, as determined by transcriptomic analysis - Yucong Ye; Siwen Li; Xinglin Du; Lin Zhang; Ning Bao; Yiming Li; Yunlong Zhao (Fish & Shellfish Immunology, 2024)

ZnO/g-C3N4 photocatalyst activated by low-pressure ultraviolet for restoring the SWASV signals: A fast pretreatment method for electrochemically detecting Cd2+ and Pb2+ in soil extracts - Haonan Li; Renjie He; Ning Liu; Liya Feng; Shaowen Chen; Hao Wang; Cheng Lv; Xinyi Chen; Gang Liu; Guo Zhao (Environmental Pollution, 2024)

Design of a bio-inspired nanofiltration channel for self-driven desalination and cleansing - Yue Zhang; Xujun Xu; Zhen Li; Yang Xue; Chunlei Wang; Qianwen Li; Junhua Zhao; Ning Wei (Desalination, 2024)

Prickly Janus magnetic and photonic microrobots for exosome assays - Ning Li; Lijun Cai; Minhui Lu; Feika Bian; Weijian Sun; Yuanjin Zhao (Chemical Engineering Journal, 2024)

Tailoring metal-support interactions via spatial confinement of Ni/CeO2 interfaces on h-BN for efficient CO2 methanation - Shuangxi Lin; Longchen Gong; Ning Zhao; Huibo Zhao; Feigang Zhao; Yang Bai; Zhenhua Li; Wen Liu (Chemical Engineering Journal, 2024)

Regulation of I1-imidazoline receptors on the sedation effect of dexmedetomidine in mice - Xiao Han; Zhi-fang Yang; Tai-yun Zhao; Guan-yi Lu; Zhi-yuan Wang; Ning Wu; Jin Li; Fei Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Caspase-12 is Expressed in Purkinje Neurons and Prevents Psychiatric-Like Behavior in Mice - Lin-Yan Huang; Yi-Ning Liu; Jie Chen; Hai-Xue Zhu; Li-Li Li; Zhi-Yan Liang; Jin-Xiu Song; Yu-Jie Li; Zhao-Li Hu; Dieter Demon; Andy Wullaert; Wan Wang; et al. (Molecular Neurobiology, 2024)

Foliar uptake screening: A promising strategy for identifying wheat varieties with low lead accumulation - Liu-Xu Feng; Yu-Ning Li; Li-Ping Geng; Pei-Pei Gao; Xiang-Yu Li; Ding-Hao Li; Gui-Li Hua; Quan-Li Zhao; Wen-Ju Liu; Pei-Ying Xue (Science of The Total Environment, 2024)

Considering the bioavailability and bioaccessibility of metal(loid)s for risk assessment of soils affected by different non-ferrous metal activities in Southwest China - Hao Li; Jun Yao; Ning Min; Geoffrey Sunahara; Yan Zhao; Robert Duran (Journal of Hazardous Materials, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Advancing the pH-driven encapsulation technique of curcumin: Molecular interaction shifts due to structural and charge variations - Hanyu Li; Minghui Zhao; Jinghong Li; Jiaqi Wang; Huajiang Zhang; Jing Wang; Ning Xia; Zhongjiang Wang; Ahmed M. Rayan (Food Hydrocolloids, 2024)

NLRP3 inflammasome activation triggers severe inflammatory liver injury in N, N-dimethylformamide-exposed mice - Xiu-Ning Zhang; Yan-Jing Zhang; Lin Wang; Shu-Jun Hong; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2024)

Preparation of mesoporous TiO2/g-C3N4 heterojunction catalyst and visible-light-driven photocatalytic reduction of Cr6+ - Yiran Xue; Ning Chen; Yuxin Zha; Baoxiu Zhao; Hao Xu; Huanxin Shi; Yulu Xing; Mengfan Li; Chaojun Sun; Yilin Wang; Bingrui Ma; Jie Liu (Journal of Water Process Engineering, 2024)

Challenges and perspectives of tribocatalysis in the treatment for dye wastewater - Baoxiu Zhao; Ning Chen; Yiran Xue; Huanxin Shi; Hao Xu; Mengfan Li; Chaojun Sun; Yulu Xing; Bo Gao; Bingrui Ma (Journal of Water Process Engineering, 2024)

Understanding the metal-electrode-correlated degradation of organic solar cells under illumination/thermal stress - Zhipeng Yin; Huan Zhao; Lijun Chen; Yunjie Li; Xingyu Liu; Jianfei Fu; Hai-Qiao Wang; Ning Li (Chemical Engineering Journal, 2024)

Was the 2022 drought in the Yangtze River Basin, China more severe than other typical drought events by considering the natural characteristics and the actual impacts? - Siquan Yang; Hongquan Sun; Ruxin Zhao; Lisong Xing; Zhuoyan Tan; Yuan Ning; Ming Li (Theoretical and Applied Climatology, 2024)

Di- and tri-methylation of histone H3K36 play distinct roles in DNA double-strand break repair - Runfa Chen; Meng-Jie Zhao; Yu-Min Li; Ao-Hui Liu; Ru-Xin Wang; Yu-Chao Mei; Xuefeng Chen; Hai-Ning Du (Science China Life Sciences, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Characteristics and mechanisms of soil structure damage under salt weathering - Zhao Duan; Kun Song; Ning Zhang; Li-Cai Zheng; Xu-Sheng Yan; Meng-Meng Zhang (Soil and Tillage Research, 2024)

Molecular insights into the catabolism of dibutyl phthalate in Pseudomonas aeruginosa PS1 based on biochemical and multi-omics approaches - Huan Du; Ji-Liang Cheng; Zhi-Yong Li; Huai-Ning Zhong; Shuang Wei; Yu-Juan Gu; Can-Can Yao; Miaoyue Zhang; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Antimony and arsenic migration in a heterogeneous subsurface at an abandoned antimony smelter under rainfall - Chao Li; Yiyuan Ran; Pan Wu; Peng Liu; Boyi Yang; Xueyuan Gu; Ping Zhao; Shirong Liu; Lei Song; Yuhui Liu; Yizhang Liu; Zengping Ning; et al. (Journal of Hazardous Materials, 2024)

Sulfur-containing iron carbon nanocomposites activate persulfate for combined chemical oxidation and microbial remediation of petroleum-polluted soil - Mengyu Ma; Ning An; Yanqin Wang; Chao Zhao; Zhaojie Cui; Weizhi Zhou; Meixia Gu; Qian Li (Journal of Hazardous Materials, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Occurrence of ochratoxin A in Sichuan bacon from different geographical regions and characterization and biocontrol of ochratoxigenic Aspergillus westerdijkiae strain 21G2-1A - Kaidi Hu; Keyu Guo; Xingjie Wang; Song Wang; Jianlong Li; Qin Li; Ning Zhao; Aiping Liu; Li He; Xinjie Hu; Yong Yang; Likou Zou; et al. (Food Research International, 2024)

A sensitive fluorometric-colorimetric dual-mode intelligent sensing platform for the detection of formaldehyde - Xiangzhen Chen; Jun Xu; Lina Zhang; Ning Bi; Jian Gou; Yongxin Li; Tongqian Zhao; Lei Jia (Food Chemistry, 2024)

Electrochemical field emission effect of ordered bismuthene electrode for supercapacitive iontronic skin with high thermal adaptability - Yanhong Zhou; Li Xiang; Zhiyuan Zhao; Tao Xu; Qi Wang; Xiaoyu Zhang; Zichu Zhang; Wei Zeng; Ning Wei; Limin Ruan; Yi Xiong; Siliang Wang; et al. (Chemical Engineering Journal, 2024)

Evaluation of the Efficacy of Stem Cells Therapy in the Periodontal Regeneration: A Meta-Analysis and Mendelian Randomization Study - Jing Hu; Ze-Yue Ou-Yang; Ya-Qiong Zhao; Jie Zhao; Li Tan; Qiong Liu; Min-yuan Wang; Qin Ye; Yao Feng; Meng-Mei Zhong; Ning-Xin Chen; Xiao-Lin Su; et al. (Stem Cell Reviews and Reports, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Correction to: BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Middle to late Holocene hydroclimate instability in the Yangtze River Delta region of China inferred from phytolith records, and its implications for societal disruption - Li Xueming; Liu Yan; Jiang Jun; Dai Jinqi; Xiao Li; Zhang Xiaoyu; Zhao Xiaoshuang; Chen Jing; Liu Shihao; Zhao Ning; Sun Qianli (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Water stratification alters phytoplankton assemblages in scallop farming waters of the North Yellow Sea in China - Junyan Zhao; Bao Zhao; Ning Kong; Ming Li; Fuzhe Li; Jinyu Liu; Lingling Wang; Linsheng Song (Marine Environmental Research, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

The removal mechanisms of HF and HCl gases using Mg-Al adsorbent prepared by sol-gel synthesis method - Peng Gao; Jiayu Feng; Yuxuan Xie; Xinyu Yang; Ping Ning; Xin Sun; Fei Wang; Lei Shi; Jie Zhao; Kai Li (Journal of Environmental Chemical Engineering, 2024)

In situ removal of Cr6+ with an intelligent adsorbent: Microwave synthesis, interface adsorption, thermodynamics, mechanism and self-regeneration - Baoxiu Zhao; Bo Gao; Huanxin Shi; Yiran Xue; Ning Chen; Hao Xu; Yulu Xing; Xuan Zhao; Bingrui Ma; Jie Liu; Jincheng Li (Journal of Environmental Chemical Engineering, 2024)

Insights into the differences in metal anchoring mechanisms and the impact on HCN catalytic oxidation performance - Zhao Li; Jiawen Tan; Yuxuan Xie; Xinyu Yang; Chunxue Wang; Kai Li; Ping Ning; Fei Wang (Fuel, 2024)

Enhancing encapsulation of curcumin by pH-driven and sodium alginate blending with ovalbumin as a carrier - Hanyu Li; Minghui Zhao; Sijie Zhou; Huajiang Zhang; Jing Wang; Ning Xia; Yujia Liu; Shihui Hua; Guixin Tan (Food Hydrocolloids, 2024)

Hepatotoxicity induced in rats by chronic exposure to F–53B, an emerging replacement of perfluorooctane sulfonate (PFOS) - Xiaohan Li; Qian Zhang; Aiqing Wang; Shan Shan; Xueying Wang; Yarong Wang; Jianmei Wan; Ping Ning; Chengjiao Hong; Hailin Tian; Yun Zhao (Environmental Pollution, 2024)

Regulating crystal growth of Cs2SnCl6 perovskite for rapid response and durable humidity-triggered non-contact sensor - Mengru Geng; Xiaosen Pan; Jiaqi Zhao; Xiaojuan Wang; Ruiming Liu; Zijun Xu; Ning Ma; Meng Gao; Mingzhe Shao; Jie Li (Chemical Engineering Journal, 2024)

Comprehensive evaluation of sewage sludge dewatering performance with supercritical CO2: Parameters optimization, mechanism, feasibility assessment - Liping Li; Zhi Wang; Junyu Tao; Yongjie Hu; Ning Li; Yingxin Zhao; Yuan Wang; Beibei Yan; Guanyi Chen (Biomass and Bioenergy, 2024)

A novel safer CD19CAR with shRNA interference of IFN-γ can reduce multiple cytokine levels without significantly compromising its killing efficacy - Ping Zhang; Peiting Ying; Hongzhe Li; Ning Zhao; Rongrong Liu; Sisi Li; Weiqun Xu; Yang Tang; Yongmin Tang (Apoptosis, 2024)

Effects of the Glucocorticoid-Mediated Mitochondrial Translocation of Glucocorticoid Receptors on Oxidative Stress and Pyroptosis in BV-2 Microglia - Ruonan Dang; Xuyang Hou; Xinglan Huang; Caifeng Huang; Xiaoqing Zhao; Xingrong Wang; Ning Zhang; Yuqi Yang; Nan Li; Sheng Liu; Peng Yan; Ping Fan; et al. (Journal of Molecular Neuroscience, 2024)

Weak correlations among leaf thermal metrics, economic traits and damages under natural heatwaves - Qiu-Rui Ning; Qiang Li; Hao-Ping Zhang; Yi Jin; Xue-Wei Gong; Rui-Fang Jiao; Emily Patience Bakpa; Han Zhao; Hui Liu (Science of The Total Environment, 2024)

Bbhox2 is a key regulator for conidiation and virulence in Beauveria bassiana - Juanjuan Li; Yan Zhang; Shouhao Jiao; Lian He; Yanhua Fan; Xuemeng Han; Binda Sun; Wenqi Zhao; Yanlin Mei; Ning Wei; Haiyue Zeng; Dan Jin (Journal of Invertebrate Pathology, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Environmental fate and health risks of polycyclic aromatic hydrocarbons in the Yangtze River Delta Urban Agglomeration during the 21st century - Ning Nie; Ting Li; Yiyi Miao; Xinyi Wei; Dengzhong Zhao; Min Liu (Journal of Hazardous Materials, 2024)

Polystyrene nanoplastics induce glycolipid metabolism disorder via NF-κB and MAPK signaling pathway in mice - Xingpei Fan; Xiaoyan Li; Jiaxin Li; Yuxia Zhang; Xiangjuan Wei; Hailong Hu; Boya Zhang; Haining Du; Meimei Zhao; Ruijiao Zhu; Daqian Yang; Yuri Oh; et al. (Journal of Environmental Sciences, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Biochar application can enhance phosphorus solubilization by strengthening redox properties of humic reducing microorganisms during composting - Bowen Fan; Changjiang Zhao; Liqin Zhao; Mengmeng Wang; Ning Sun; Zoutong Li; Fengjun Yang (Bioresource Technology, 2024)

Transgenerational effects of extracts containing Microcystin-LR exposure on reproductive toxicity and offspring growth inhibition in a model organism zebrafish - Qing Yang; Lanlan Huang; Ning Yang; Hongyang Cui; Yanbin Zhao; Zipeng Li; Yindong Tong (Aquatic Toxicology, 2024)

A novel cold-adapted pyrethroid-degrading esterase from Bacillus subtilis J6 and its application for pyrethroid-residual alleviation in food matrix - Mengmei Zhang; Kun Yang; Li Yang; Yangyu Diao; Xingjie Wang; Kaidi Hu; Qin Li; Jianlong Li; Ning Zhao; Li He; Shujuan Chen; Aiping Liu; et al. (Journal of Hazardous Materials, 2024)

Plastic film mulching application improves potato yields, reduces ammonia emissions, but boosts the greenhouse gas emissions in China - Yalan Huang; Rongzhu Qin; Huihui Wei; Ning Chai; Yang Yang; Yuling Li; Pingxing Wan; Yufei Li; Wucheng Zhao; Siam Lawawirojwong; Tanita Suepa; Feng Zhang (Journal of Environmental Management, 2024)

Biodegradation properties and mechanism of triketone herbicide mesotrione via newly isolated bacterium Klebsiella pasteurii CM-1 - Xiaotian Cao; Yuanfu Li; Wei Liu; Ning Hou; Feng Zhao; Ping Han; Huihua Tan (International Biodeterioration & Biodegradation, 2024)

Study on formation process and reservoir damage mechanism of blockages caused by polyacrylamide fracturing fluid in production wells - Zhongzheng Xu; Mingwei Zhao; Jiawei Liu; Yiming Zhang; Mingwei Gao; Xuguang Song; Ning Sun; Lin Li; Yining Wu; Caili Dai (Fuel, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

Heterostructure nanozymes with sustainable tumor microenvironment regulation and reinforced hyperthermia-responsive catalytic activities for orchestrated osteosarcoma catalytic therapy - Xing Zhang; Xiang Li; Mengying Fu; Jeremiah Ong'achwa Machuki; Wandong Wang; Liang Wu; Qun Zhao; Ning Xin; Lei Hua; Fenglei Gao (Chemical Engineering Journal, 2024)

Elastomers with ultrahigh mechanical properties for flexible sensing and triboelectric nanogenerators - Zhichao Zhang; Wenhao Cao; Muqun Wang; Liang Tuo; Ting Xie; Fangyan Ou; Xueying Duan; Riyao Cong; Chuang Ning; Wenyu Pan; Shuangliang Zhao; Zequan Li; et al. (Chemical Engineering Journal, 2024)

Role of sleep in asthenospermia induced by di (2-ethyl-hexyl) phthalate - Xiao-lu Li; Xiao-yue Cai; Xia Ning; Yue-yue Liang; Yun Hong; Qi-meng Li; Die Hu; Yuan-zhuo Zheng; Yang Cai; Tao Xu; Ling-li Zhao (Environmental Science and Pollution Research, 2024)

Identification of Immune Infiltration and Iron Metabolism–Related Subgroups in Autism Spectrum Disorder - Wenyan Huang; Zhenni Liu; Ziling Li; Si Meng; Yuhang Huang; Min Gao; Ning Zhong; Sujuan Zeng; Lijing Wang; Wanghong Zhao (Journal of Molecular Neuroscience, 2024)

A novel methodology for calculating the aerosol direct radiative effect using a non-uniform five-dimensional lookup table - Zhenwei Shi; Ning Xu; Jianzhong Li; Zhaoxu Zhang; Hui Zhao; Hui Long (International Journal of Remote Sensing, 2024)

Ammonia release characteristics during desulfurization wastewater evaporation: Mechanisms and implications - Heng Chen; Dawei Hou; Zhihao Li; Lingxiao Zhan; Lijian Jin; Suoqi Zheng; Yurui Wang; Hao Wu; Ning Zhao; Liliang Lin; Linjun Yang (Journal of Water Process Engineering, 2024)

Aquatic toxicity, ecological effects, human exposure pathways and health risk assessment of liquid crystal monomers - Wei He; Yuhan Cui; Hao Yang; Jiaxuan Gao; Yuanyuan Zhao; Ning Hao; Yu Li; Meng Zhang (Journal of Hazardous Materials, 2024)

DNA hypomethylation-associated transcriptional rewiring enables resistance to heavy metal mercury (Hg) stress in rice - Weixuan Cong; Ning Li; Yiling Miao; Yuxi Huang; Wenhao Zhao; Ying Kang; Bingqi Zhang; Jinbin Wang; Jiayu Zhang; Yinhe Lv; Jiamo Li; Jian Zhang; et al. (Journal of Hazardous Materials, 2024)

GC–MS, GC–O, and sensomics analysis reveals the key odorants underlying the improvement of yellow tea aroma after optimized yellowing - Yuming Wei; Jixin Zhang; Tiehan Li; Mengjie Zhao; Zhenshuo Song; Yujie Wang; Jingming Ning (Food Chemistry, 2024)

Paper-based fluorescent materials containing on-demand nanostructured brain-cells-inspired AIE self-assembles for real-time visual monitoring of seafood spoilage - Lijuan Chen; Xiaomin Luo; Xuechuan Wang; Lulu Ning; Nihao Li; Suqiu Zhao; Qian Zhang; Xinhua Liu; Huie Jiang (Food Chemistry, 2024)

Huogu injection protects against SONFH by promoting osteogenic differentiation of BMSCs and preventing osteoblast apoptosis - Xin Zhang; Ziyu Li; Xilin Xu; Zhao Liu; Yuanyuan Hao; Fubiao Yang; Xiaodong Li; Ning Zhang; Yunlong Hou; Xiaofeng Zhang (Cell and Tissue Research, 2024)
To investigate the effect and mechanism of Huogu injection (HG) on steroid-induced osteonecrosis of the femoral head (SONFH), we established a SONFH model in rabbits using horse serum and dexamethasone (DEX) and applied HG locally at the hip joint. We evaluated the therapeutic efficacy at 4 weeks using scanning electron microscopy (SEM), micro-CT, and qualitative histology including H&E, Masson’s trichrome, ALP, and TUNEL staining. In vitro, we induced osteogenic differentiation of bone marrow stromal cells (BMSCs) and performed analysis on days 14 and 21 of cell differentiation. The findings, in vivo, including SEM, micro-CT, and H&E staining, showed that HG significantly maintained bone quality and trabecular number. ALP staining indicated that HG promoted the proliferation of bone cells. Moreover, the results of Masson’s trichrome staining demonstrated the essential role of HG in collagen synthesis. Additionally, TUNEL staining revealed that HG reduced apoptosis. ALP and ARS staining in vitro confirmed that HG enhanced osteogenic differentiation and mineralization, consistent with the WB and qRT-PCR analysis. Furthermore, Annexin V-FITC/PI staining verified that HG inhibited osteoblast apoptosis, in agreement with the WB and qRT-PCR analyses. Furthermore, combined with the UPLC analysis, we found that naringin enhanced the osteogenic differentiation and accelerated the deposition of calcium phosphate. Salvianolic acid B protected osteoblasts derived from BMSCs against GCs-mediated apoptosis. Thus, this study not only reveals the mechanism of HG in promoting osteogenesis and anti-apoptosis of osteoblasts but also identifies the active-related components in HG, by which we provide the evidence for the application of HG in SONFH.

Immunomagnetic capture and traceless release of native tumor-derived exosomes from human plasma for exploring interaction with recipient cells by aptamer-functionalized nanoflowers - Haoyang Zheng; Ning Su; Guoquan Yan; Mengran Li; Huimin Chu; Jin Zhang; Bing Li; Jiandong Zhao; Jiaxi Wang; Mingxia Gao; Xiangmin Zhang (Analytica Chimica Acta, 2024)

Polyphenols and polyphenols-based biopolymer materials: Regulating iron absorption and availability from spontaneous to controllable - Yafei Zhang; Xiaojing Tian; Anguo Teng; Yu Li; Yuzhen Jiao; Kaixuan Zhao; Yang Wang; Ruonan Li; Ning Yang; Wenhang Wang (Critical Reviews in Food Science and Nutrition, 2023)

Effects and mechanisms of resveratrol for prevention and management of cancers: An updated review - Si-Xia Wu; Ruo-Gu Xiong; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Cai-Ning Zhao; Ao Shang; Yun-Jian Zhang; Ren-You Gan; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2023)

Exaggerated interaction of biofilm-developed microplastics and contaminants in aquatic environments - Zigong Ning; Shuang Zhou; Pengxiang Li; Rong Li; Feihua Liu; Zilong Zhao; Nanqi Ren; Lu Lu (Chemosphere, 2023)

An efficient pretreatment method based on AgNPs-doped SnO2 photocatalyst for the accurate detection of heavy metals in organic-rich water samples - Liya Feng; Renjie He; Haonan Li; Jiali Wang; Shaowen Chen; Ning Liu; Gang Liu; Xiaochan Wang; Guo Zhao (Chemosphere, 2023)

Design strategies for renovation of public space in Beijing's traditional communities based on measured microclimate and thermal comfort - Ning Li; Zhao Guo; Wenying Geng; Lin Li; Ziwei Li (Sustainable Cities and Society, 2023)

High temperatures and urban entrepreneurship levels: Evidence from China - Yuanshuang Zhao; Liang Dong; Jiaying Li; Kehan Yang; Ning Zhang (Science of The Total Environment, 2023)

Interactions between CuO NPs and PS: The release of copper ions and oxidative damage - Yan Cao; Senlin Tian; Yingxue Geng; Linfeng Zhang; Qun Zhao; Jie Chen; Yingjie Li; Xuewei Hu; Jianhong Huang; Ping Ning (Science of The Total Environment, 2023)

Subchronic feeding study of glyphosate-tolerant maize GG2 with the gr79-epsps and gat genes in Wistar Han RCC rats - Qinghong Zhou; Shufei Li; Miao Zhao; Yinghua Liu; Ning He; Xiaoli Zhou; Dianming Zhou; Zhiyong Qian (Regulatory Toxicology and Pharmacology, 2023)

Effect mechanisms of leading-edge tubercle on blade cavitation control in a waterjet pump - Guoshou Zhao; Ning Liang; Qianqian Li; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2023)

Degradation of polyvinyl chloride microplastics via electrochemical oxidation with a CeO2–PbO2 anode - Ziqi Ning; Xiaoyue Duan; Yitong Li; Xuesong Zhao; Limin Chang (Journal of Cleaner Production, 2023)

Sorption behavior and mechanism of U(VI) on Tamusu clay in the presence of U(VI)-CO3 complexes - Xiaoyu Yin; Peng Wu; Shilong Shi; Yufan Zhao; Honghui Li; Feize Li; Jiali Liao; Ning Liu; Yuanyou Yang; Tu Lan (Journal of Environmental Radioactivity, 2023)

Metabolomics analysis reveals the mechanism underlying the improvement in the color and taste of yellow tea after optimized yellowing - Yuming Wei; Xuchao Yin; Mengjie Zhao; Jixin Zhang; Tiehan Li; Yiyi Zhang; Yujie Wang; Jingming Ning (Food Chemistry, 2023)

Harnessing the potential of postbiotics derived from Bacillus coagulans: A promising avenue for obesity management via the gut-liver axis - Long Chen; Chao Ning; Liying Ma; Meiqing Wang; Yujuan Zhao; Shengyu Li; Zijian Zhao (Food Bioscience, 2023)

Microplastics Pollution and Risk Assessment in Selected Surface Waters of the Wei River Plain, China - Hanghang Zhao; Peiyue Li; Xiaodong He; Jing Ning (Exposure and Health, 2023)

Dietary sources, health benefits, and risks of caffeine - Adila Saimaiti; Dan-Dan Zhou; Jiahui Li; Ruo-Gu Xiong; Ren-You Gan; Si-Yu Huang; Ao Shang; Cai-Ning Zhao; Hang-Yu Li; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2023)

An Automatic Internal Wave Recognition Algorithm Based on CNN Applicable to an Ocean Data Buoy System - Guozheng Yuan; Chunlin Ning; Lin Liu; Chao Li; Yanliang Liu; Chalermrat Sangmanee; Xuerong Cui; Jinkai Zhao; Jiuke Wang; Weidong Yu (Journal of Marine Science and Engineering, 2023)
The application of internal wave recognition to the buoy system is of great significance to enhance the understanding of the ocean internal wave phenomenon and provide more accurate data and information support. This article proposes an automatic internal wave recognition algorithm based on convolutional neural networks (CNN), which is used in the tight-profile intelligent buoy system. The sea profile temperature data were collected using the Bailong buoy system in the Andaman Sea in 2018. The CNN network structure is applied to feature compression of ocean temperature profile data, reducing the input feature amount of the feature recognition network, thereby reducing the overall algorithm parameters and computational complexity. By adjusting the number of convolution kernels and the length of convolution steps, the original data features in the time domain and the space domain are compressed, respectively. The experimental results show that the identification accuracy and robustness of this method are clearly superior to those of other methods. Additionally, the parameter number and calculation amount of this algorithm are very tiny, which greatly improves the possibility of its deployment in the buoy system.

Machine learning framework for intelligent aeration control in wastewater treatment plants: Automatic feature engineering based on variation sliding layer - Yu-Qi Wang; Hong-Cheng Wang; Yun-Peng Song; Shi-Qing Zhou; Qiu-Ning Li; Bin Liang; Wen-Zong Liu; Yi-Wei Zhao; Ai-Jie Wang (Water Research, 2023)

Identifying the key factors affecting the trimethylamine N-oxide content of teleost fishes collected from the marginal seas of China and the epipelagic zone of the northwest Pacific Ocean - Qingjing Hu; Wanyu Zhao; Keming Qu; Ning An; Lingxiao Li; Yuqiu Wei; Ying Bai; Tao Jiang; Jufa Chen; Fangqun Dai; Hongsheng Wang; Zhengguo Cui (Science of The Total Environment, 2023)

Biodegradability analysis of Dioxins through in silico methods: Model construction and mechanism analysis - Qing Li; Hao Yang; Ning Hao; Meijn Du; Yuanyuan Zhao; Yu Li; Xixi Li (Journal of Environmental Management, 2023)

Changes in Maillard reaction products, volatile substances and active proteins of goat milk under different heat treatments - Yinping Guo; Hongjuan Li; Xiaoxuan Zhao; Yumeng Zhang; Xiaoyang Pang; Ning Xie; Yunna Wang; Jinghua Yu; Jiaping Lv; Shuwen Zhang (International Dairy Journal, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Label-free quantitative proteomic analysis of milk fat globule membrane proteins in porcine colostrum and mature milk - Huiwen Zhao; Mohan Li; Qing Zhu; Aicheng Liu; Jiayang Bi; Zhizhong Quan; Xue Luo; Yan Zheng; Ning Yang; Xiqing Yue; Xueyan Cao (Food Chemistry, 2023)

Impacts of autochthonous dissolved organic matter on the accumulation of methylmercury by phytoplankton and zooplankton in a eutrophic coastal ecosystem - Bo Shao; Zhike Li; Zhengyu Wu; Ning Yang; Xiaoyu Cui; Huiming Lin; Yiwen Liu; Wei He; Yingxin Zhao; Xuejun Wang; Yindong Tong (Environmental Pollution, 2023)

A new empirical model for flexural stiffness of corroded post-tensioned concrete beams - Zhao-Hui Lu; Zhong-Ning Yang; Chun-Qing Li (Engineering Structures, 2023)

Mechanistic insights into suppressing microcracks by regulating grain size of precursor for high-performance Ni-rich cathodes - Kangyu Zou; Mingzhu Jiang; Zixiang Zhao; Shangchen Xie; Tianxiang Ning; Lei Tan; Hongxing Li; Youyuan Zhou; Wanlin Wang; Xianwen Wu; Lingjun Li (Chemical Engineering Journal, 2023)

Realization of dual crosslinked network robust, high toughness self-healing polyurethane elastomers for electronics applications - Xueying Duan; Wenhao Cao; Xiangning He; Muqun Wang; Riyao Cong; Zhichao Zhang; Chuang Ning; Changsheng Wang; Shuangliang Zhao; Zequan Li; Wei Gao (Chemical Engineering Journal, 2023)

Role of nitrogen dual reaction sites in N-doped graphene aerogels for synergistic sulfamethoxazole adsorption and peroxymonosulfate activation in Fenton-like process - Ning An; Shijing Li; Bentuo Xu; Linbo Qian; Yi Shen; Kun Wang; Xiangyu Li; Min Zhao; Xiangyong Zheng; Renlan Liu (Chemical Engineering Journal, 2023)

Insights into ecotoxicity effects of PAHs and ecosystem responses of remediation strategies under cold stress: From PAHs degradation to ecological restoration regulated by signal molecular - Qiuying Song; Xianyue Li; Zhiyong Zhao; Dapeng Li; Yunying Li; Ning Hou (Chemical Engineering Journal, 2023)

Atomic pins bridging integrated surface to assist high-rate stability for Co-free Li-rich cathode - Yuefeng Su; Jiayu Zhao; Jinyang Dong; Qi Shi; Jianan Hao; Wenbo Li; Liying Bao; Yun Lu; Ning Li; Duanyun Cao; Lai Chen; Feng Wu (Chemical Engineering Journal, 2023)

VDAC1 Protein Regulation of Oxidative Damage and Mitochondrial Dysfunction-Mediated Cytotoxicity by Silica Nanoparticles in SH-SY5Y Cells - Xiaofan Ning; Xinyue Li; Kai Ma; Huan Pang; Tiantian Tian; Huifang Hao; Qiaohong Hou; Meng Li; Tianxiang Liu; Shanshan Hou; Haiying Du; Xiuling Song; et al. (Molecular Neurobiology, 2023)

Age-specific difference in the temporal relationships between updated cardiovascular health construct and arterial stiffness in middle-aged and older adults - Jiaojiao Huang; Xiaoli Xu; Yingxia Zhou; Zhuojun Xin; Qiuyu Cao; Ruixin He; Tianzhichao Hou; Yi Ding; Jieli Lu; Tiange Wang; Zhiyun Zhao; Yu Xu; et al. (GeroScience, 2023)

M1 polarization of chicken macrophage HD11 can be activated by duck Tembusu virus via MyD88-NF-κB-mediated signaling pathway - Ningwei Geng; Ji Fu; Zehao Lv; Jing Li; Yuxin Kong; Lei Qu; Zhiyun Guo; Jun Zhao; Liya Zhu; Feng Wang; Cui Zhao; Sidang Liu; et al. (Veterinary Microbiology, 2023)

Comprehensive competitiveness assessment of four typical municipal sludge treatment routes in China based on environmental and techno-economic analysis - Yanqin Huang; Yuhang Zhen; Lanling Liu; Xiaoyang Ning; Chenzhou Wang; Kai Li; Li Zhao; Qiang Lu (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Asymmetry of blue and green water changes in the Yangtze river basin, China, examined by multi-water-variable calibrated SWAT model - Ning Nie; Ting Li; Yiyi Miao; Wanchang Zhang; Huiran Gao; Hongming He; Dengzhong Zhao; Min Liu (Journal of Hydrology, 2023)

Porphyrin-based hydrogen-bonded organic framework for visible light driven photocatalytic removal of U(VI) from real low-level radioactive wastewater - Peng Wu; Xiaoyu Yin; Yufan Zhao; Feize Li; Yuanyou Yang; Ning Liu; Jiali Liao; Tu Lan (Journal of Hazardous Materials, 2023)

Environmentally friendly PAEs alternatives with desired synthesizability by in silico methods - Hao Yang; Qing Li; Yang Wu; Yuanyuan Zhao; Ning Hao; Wei He; Yu Li (Journal of Cleaner Production, 2023)

Towards low energy-carbon footprint: Current versus potential P recovery paths in domestic wastewater treatment plants - Qian Zhao; Hao Ying; Yu Liu; Hongbo Wang; Jingtao Xu; Wei Wang; Juan Ren; Shujuan Meng; Ning Wang; Ruimin Mu; Shasha Wang; Jingjing Li (Journal of Environmental Management, 2023)

Red mud with enhanced dealkalization performance by supercritical water technology for efficient SO2 capture - Zimeng Nie; Qun Zhao; Qilin Zhao; Yingjie Li; Dian Yang; Huaying Liu; Shupu Yang; Jie Li; Senlin Tian; Chen Li; Cheng Tie; Jianhong Huang; et al. (Journal of Environmental Management, 2023)

Activation of peroxymonosulfate by N, S co-doped magnetic FeCoS for the degradation of ciprofloxacin hydrochloride: Catalytic performance and mechanism - Congya Tian; Jiayi Li; Lin Zhao; Yuanzhi Wang; Shangtong Li; Zhibo Zhao; Ning Liang (Journal of Environmental Chemical Engineering, 2023)

A wearable gloved sensor based on fluorescent Ag nanoparticles and europium complexes for visualized assessment of tetracycline in food samples - Jun Xu; Junxi Wang; Yongxin Li; Lina Zhang; Ning Bi; Jian Gou; Tongqian Zhao; Lei Jia (Food Chemistry, 2023)

The intestinal bacterial community over seasons and its relationship with physiological status of Yesso scallop Patinopecten yessoensis - Fuzhe Li; Ning Kong; Junyan Zhao; Bao Zhao; Jinyu Liu; Chuanyan Yang; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2023)

A 90-day feeding study of genetically modiﬁed maize LP007-1 in wistar han RCC rats - Qinghong Zhou; Shufei Li; Miao Zhao; Yinghua Liu; Ning He; Xiaoli Zhou; Dianming Zhou; Zhiyong Qian (Food and Chemical Toxicology, 2023)

Understanding the time-activity pattern to improve the measurement of personal exposure: An exploratory and experimental research - Zhenglei Li; Yan Ding; Danlu Wang; Ning Kang; Yan Tao; Xiuge Zhao; Bin Zhang; Zuming Zhang (Environmental Pollution, 2023)

Effects of hydrate distribution heterogeneity on the mechanical properties of hydrate-bearing sediments with consideration of the coalescence phenomenon: Insights from DEM simulations - Xiaofeng Dou; Qi Wu; Zhichao Liu; Yingjie Zhao; Yanlong Li; Deli Gao; Fulong Ning (Computers and Geotechnics, 2023)

Unlocking the effect of monocyclic and fused backbones on energy and stability of fully nitrated compounds - Zhiyi Jiang; Ning Ding; Qi Sun; Chaofeng Zhao; Baojing Tian; Shenghua Li; Siping Pang (Chemical Engineering Journal, 2023)

Intensive adsorption of tetracycline by cobalt oxide quantum dots-loaded mineral carbon - Ning Zhao; Qiyi Ma; Baifa Zhang; Yanfu Wei; Dong Liu; Mengyuan Li; Haoyu Li; Peng Yuan (Bioresource Technology, 2023)

Modeling of breaching parameters for debris flow dams - He-chun Ruan; Hua-yong Chen; Xiao-qing Chen; Wan-yu Zhao; Jian-gang Chen; Tao Wang; Yao Jiang; Xi-an Wang; Xiang-ning Li; Xiao Li; Yun-han Yu (Journal of Mountain Science, 2023)

A generalized elastoplastic load-transfer model for axially loaded piles in clay: Incorporation of modulus degradation and skin friction softening - Lin Li; Ning Lai; Xuefeng Zhao; Tantan Zhu; Zhongming Su (Computers and Geotechnics, 2023)

Phase behavior tuning enable high-safety and crack-free Ni-rich layered cathode for lithium-ion battery - Na Liu; Lai Chen; Haoyu Wang; Jiayu Zhao; Fei Gao; Jing Liu; Jinyang Dong; Yun Lu; Ning Li; Qi Shi; Yuefeng Su; Feng Wu (Chemical Engineering Journal, 2023)

Confinement boosted heterogeneous advanced oxidation processes - Haoxi Dai; Ning Li; Jingya Ye; Jianhui Zhao; Xu He; Xiaoguang Duan; Beibei Yan; Guanyi Chen; Shaobin Wang (Chemical Engineering Journal, 2023)

Achieving multi-dimensional Li+ transport nanochannels via spatial-partitioning in crystalline ionic covalent organic frameworks for highly stable lithium metal anode - Wenbo Wang; Yantao Zhang; Haichao Jiang; Ruijuan Zhang; Ning Wang; Yaying Dou; Zhiyi Zhao; Xue Yang; Xiaoyun Fan; Xiaodi Li; Xiaomeng Guo; Qingliang Feng; et al. (Chemical Engineering Journal, 2023)

AIEgens-integrated structural color barcodes for binary screening of microRNAs - Feika Bian; Hanxu Chen; Lingyu Sun; Ning Li; Yuanjin Zhao (Chemical Engineering Journal, 2023)

Cuproptosis-related gene SLC31A1 expression correlates with the prognosis and tumor immune microenvironment in glioma - Jun Wang; Shenglun Li; Yuduo Guo; Chao Zhao; Yujia Chen; Weihai Ning; Jingjing Yang; Hongwei Zhang (Functional & Integrative Genomics, 2023)
Cuproptosis is a newly discovered form of cell death. It is regulated by a string of genes. The genes are identified to influence the tumor progression, but in glioma, the cuproptosis-related genes are little studied. The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) were used to screen for SLC31A1 gene expression in glioma and healthy tissue samples. The results were validated using the Gene Expression Omnibus (GEO) and quantitative real-time polymerase chain reaction (qPCR). The Human Protein Atlas (HPA) and the National Cancer Institute’s Clinical Proteomic Tumor Analysis Consortium (CPTAC) were used to validate our results at the protein level. Multivariable analysis and Kaplan–Meier survival curves were used to examine the relationship among SLC31A1 gene expression, clinical parameters, and survival rates. The online Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) was used to find the genes and proteins that correlate to SLC31A1 . The immune infiltration analysis was performed using the Tumor Immune Estimation Resource (TIMER) databases. Small interfering RNA was used to knock down the SLC31A1 expression, and the cell proliferation, apoptosis, and migration were analyzed using cell counting kit-8, flow cytometry, and transwell. The glioma patients have higher SLC31A1 expression levels, which increase as the World Health Organization (WHO) grade escalates. The survival analysis illustrates that the SLC31A1 gene expression negatively correlates with overall survival (OS), progression-free survival (PFS), and disease-specific survival (DSS). The immune infiltration analysis shows the SLC31A1 gene positively correlates with T helper 2 (Th2) cells, macrophages, and M2-type macrophages and negatively correlates with plasmacytoid dendritic cells (pDCs), natural killer (NK) CD56bright cells, and CD8 T cells. The in vitro KD experiment shows the SLC31A1 knockdown depressed the glioma cell proliferation and migration and promoted the apoptosis rate. The SLC31A1 gene expression can shorten the survival time of glioma patients. In vitro study shows that SLC31A1 can promote cell proliferation, and migration, and depress the cell apoptosis of glioma cells. It also can promote the formation of a tumor-suppressive microenvironment.

Delays in heading and improvements in both spikelet number and spike length are associated with the Aegilops tausschii photoperiod-sensitive ppd-D1b allele - Shunzong Ning; Laibin Zhao; Shijie Li; Shengke Li; Tianqing Zang; Yu’e Liu; Hongkun Yang; Xuejiao Chen; Xue Chen; Yingjin Yi; Ming Hao; Lianquan Zhang; et al. (Cereal Research Communications, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

The paleo-lithospheric structure and rifting-magmatic processes of the northern South China Sea passive margin - Zhongxian Zhao; Zhen Sun; Ning Qiu; Minghui Zhao; Jiazheng Zhang; Fucheng Li; Jian Lin; Eun Young Lee (Gondwana Research, 2023)

Changes in gut microbiota structure and function in gout patients - Feiyan Zhao; Zhixin Zhao; Dafu Man; Zhihong Sun; Ning Tie; Hongbin Li; Heping Zhang (Food Bioscience, 2023)

Attenuating UVA-induced oxidative stress of human skin fibroblasts by enhancing bioactive components of Armillaria luteo-virens by Lactobacillus delbrueckii subsp. Bulgaricus fermentation - Jingsha Zhao; Shiquan You; Dongdong Wang; Ning Su; Li Yang; Dan Zhao; Jiachan Zhang; Meng Li; Changtao Wang (Food Bioscience, 2023)

Contribution of amino acids to Alicyclobacillus acidoterrestris DSM 3922T resistance towards acid stress - Junnan Xu; Ning Zhao; Xuemei Meng; Tong Zhang; Jun Li; Huayu Dong; Xinyuan Wei; Mingtao Fan (Food Microbiology, 2023)

Solar-driven dry reforming of methane using RuNi single-atom alloy catalyst coupled with thermal decomposition of carbonates - Qian Yin; Tianyang Shen; Jinhao Li; Chenjun Ning; Yao Xue; Guangbo Chen; Ming Xu; Fenglong Wang; Yu-Fei Song; Yufei Zhao; Xue Duan (Chemical Engineering Journal, 2023)

New insights into dry-coating-processed surface engineering enabling structurally and thermally stable high-performance Ni-rich cathode materials for lithium ion batteries - Feng Wu; Qi Shi; Lai Chen; Jinyang Dong; Jiayu Zhao; Haoyu Wang; Fei Gao; Jing Liu; Hongyun Zhang; Ning Li; Yun Lu; Yuefeng Su (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Effects and mechanisms of tea on obesity - Xiao-Yu Xu; Cai-Ning Zhao; Bang-Yan Li; Guo-Yi Tang; Ao Shang; Ren-You Gan; Yi-Bin Feng; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2023)

Graphene nano zinc oxide reduces the expression and release of antibiotic resistance-related genes and virulence factors in animal manure - Haibo Zhang; Weikun Guan; Jun Shu; Sen Yu; Yingmin Xiong; Gao Liu; Yuhong Zhong; Jia Chen; Zhigang Zhao; Ning He; Qingfeng Xing; Dongsheng Guo; et al. (Science of The Total Environment, 2023)

Phosphorus doping significantly enhanced the catalytic performance of cobalt-single-atom catalyst for peroxymonosulfate activation and contaminants degradation - Ning Chen; Yu Zeng; Tai Li; Peixin Cui; Dionysios D. Dionysiou; Xiaolei Wang; Cun Liu; Guodong Fang; Chengcheng Ding; Yuan Zhao; Juan Gao; Yujun Wang; et al. (Journal of Hazardous Materials, 2023)

Discrete element simulation of the hydrate-bearing sediments mechanical behaviors under typical hydrate dissociation patterns - Qi Wu; Xiaofeng Dou; Yingjie Zhao; Zhichao Liu; Yanlong Li; Norimasa Yoshimoto; Fulong Ning (Gas Science and Engineering, 2023)

Insight into the soil aggregate-mediated restoration mechanism of degraded black soil via biochar addition: Emphasizing the driving role of core microbial communities and nutrient cycling - Chi Zhang; Xin Zhao; Aijie Liang; Yunying Li; Qiuying Song; Xianyue Li; Dapeng Li; Ning Hou (Environmental Research, 2023)

Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2023)

Effect of MOF-derived carbon–nitrogen nanosheets co-doped with nickel and titanium dioxide nanoparticles on hydrogen storage performance of MgH2 - Zhiqiang Lan; Feifan Hong; Weitao Shi; Ruolin Zhao; Renhuan Li; Yi Fan; Haizhen Liu; Wenzheng Zhou; Hua Ning; Jin Guo (Chemical Engineering Journal, 2023)

Experimental Investigation into the Mechanical Behavior of Jointed Soft Rock Using Sand Powder 3D Printing - Yang Zhao; Lishuai Jiang; Chunang Li; Qingjia Niu; Atsushi Sainoki; Hani S. Mitri; Jianguo Ning (Rock Mechanics and Rock Engineering, 2023)

A techno-economic analysis of ammonia-fuelled powertrain systems for rail freight - Yuqi Zhang; Ning Zhao; Mingqiang Li; Zhan Xu; Dawei Wu; Stuart Hillmansen; Athanasios Tsolakis; Kevin Blacktop; Clive Roberts (Transportation Research Part D: Transport and Environment, 2023)

Microalgae-based constructed wetland system enhances nitrogen removal and reduce carbon emissions: Performance and mechanisms - Xinyue Zhao; Tuoshi Zhang; Bin Dang; Mengran Guo; Ming Jin; Chunyan Li; Ning Hou; Shunwen Bai (Science of The Total Environment, 2023)

Source toxicity characteristics of short- and medium-chain chlorinated paraffin in multi-environmental media: Product source toxicity, molecular source toxicity and food chain migration control through silica methods - Wei He; Peixuan Sun; Yuanyuan Zhao; Qikun Pu; Hao Yang; Ning Hao; Yu Li (Science of The Total Environment, 2023)

Photoelectrocatalytic selective removal of group-targeting thiol-containing heterocyclic pollutants - Baoling Niu; Zhiming Wang; Jianwei Wu; Junzhuo Cai; Ziwen An; Jie Sun; Yanbo Li; Shuyu Huang; Ning Lu; Qihao Xie; Guohua Zhao (Journal of Hazardous Materials, 2023)

Characteristics analysis of plastisphere biofilm and effect of aging products on nitrogen metabolizing flora in microcosm wetlands experiment - Jian Zhang; Yuanyuan Shao; Zhao Li; Guolan Han; Xinxin Jing; Ning Wang; Jingtao Xu; Gao Chen (Journal of Hazardous Materials, 2023)

An integrated strategy combining network toxicology and feature-based molecular networking for exploring hepatotoxic constituents and mechanism of Epimedii Folium-induced hepatotoxicity in vitro - Zhen Zhao; Jin-Fa Du; Qiao-Lei Wang; Fang-Ning Qiu; Xu-Yan Chen; Feng-Jie Liu; Ping Li; Yan Jiang; Hui-Jun Li (Food and Chemical Toxicology, 2023)

Effects of bisphenols on lipid metabolism and neuro–cardiovascular toxicity in marine medaka larvae - Xueyou Li; Xiaoxu He; Xiaona Lin; Weihao Li; Jiahao Gao; Ning Zhang; Yusong Guo; Zhongduo Wang; Na Zhao; Bo Zhang; Zhongdian Dong (Aquatic Toxicology, 2023)

Effects of Bacillus subtilis BS-Z15 on Intestinal Microbiota Structure and Body Weight Gain in Mice - Jun Yang; Huan-Chen Ning; Qi Zhang; Jun-Qi Yue; Xi-Yuan Cao; Jin-Yu Li; Ling Liu; He-Ping Zhao; Hui-Xin Zhao (Probiotics and Antimicrobial Proteins, 2023)

Effects of Surface Mulching on Soil Water Temperature, Physiological Characteristics and Yield of Maize - Lihua Zhang; Chen Xu; Weiping Yan; Guobo Tan; Ning Sun; Hongxiang Zhao; Fei Li; Jiang Yu; Xiangmeng Meng; Shaofeng Bian (International Journal of Plant Production, 2023)

Loss of MuRF1 in Duroc pigs promotes skeletal muscle hypertrophy - Jiaping Li; Yiqing Hu; Jiajia Li; Haitao Wang; Hanyu Wu; Chengcheng Zhao; Tan Tan; Li Zhang; Di Zhu; Xu Liu; Ning Li; Xiaoxiang Hu (Transgenic Research, 2023)

Alternative tree-cover states of dryland ecosystems: Inconsistencies between global and continental scales - Li Ma; Liping Yang; Qinqin Chang; Siqing Wang; Chao Guan; Ning Chen; Changming Zhao (Agricultural and Forest Meteorology, 2023)

The sensitivity of mechanical properties and pore structures of Beishan granite to large variation of temperature in nuclear waste storage sites - Yun Wu; Li-Hua Hu; Jin Yu; Xiao-Zhao Li; Li-Ning Yang; Sen Xue; Kai Zhang (Environmental Science and Pollution Research, 2023)

Converting commonly-used paper into nano-engineered fluorescent biomass-based platform for rapid ClO− quantitative detection in living cells and water sources - Nihao Li; Huie Jiang; Lijuan Chen; Zhijian Li; Qingxin Han; Lulu Ning; Zhenjuan Chen; Suqiu Zhao; Xinhua Liu (Chemosphere, 2023)

Organic substitution stimulates ammonia oxidation-driven N2O emissions by distinctively enriching keystone species of ammonia-oxidizing archaea and bacteria in tropical arable soils - Qi Zhang; Miao Chen; Youfeng Leng; Xiaotong Wang; Yajun Fu; Danfeng Wang; Xiongwei Zhao; Wenlong Gao; Ning Li; Xin Chen; Changhua Fan; Qinfen Li (Science of The Total Environment, 2023)

Overlooked impacts of natural organic matter conversion in a Fe(II)-induced peroxymonosulfate activation system for river water remediation - Lan Liang; Guanyi Chen; Jianhui Zhao; Penghui Shao; Ning Li; Mengting He; Qinglong Fu; Beibei Yan; Li-an Hou (Science of The Total Environment, 2023)

Colonic mechanism of serum NAD+ depletion induced by DEHP during pregnancy - Yun Hong; Xia Ning; Yue-yue Liang; Xiao-lu Li; Ya Cui; Wei Wu; Yang Cai; Shuai Zhao; Meng Zhu; Tian-xiao Zhong; Hua Wang; De-xiang Xu; et al. (Science of The Total Environment, 2023)

Molecular insights into effects of PBAT microplastics on latosol microbial diversity and DOM chemodiversity - Yuqin Liu; Wen Zhang; Miao Chen; Xiongwei Zhao; Huiran Liu; Meihong Ge; Ning Li; Ziyu Ning; Wenlong Gao; Changhua Fan; Qinfen Li (Journal of Hazardous Materials, 2023)

Extracellular biomineralization of uranium and its toxicity alleviation to Bacillus thuringiensis X-27 - Ting Zhu; Qian Zeng; Changsong Zhao; Yufeng Wen; Shangqing Li; Feize Li; Tu Lan; Yuanyou Yang; Ning Liu; Qun Sun; Jiali Liao (Journal of Environmental Radioactivity, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

Retraction Note: Characterization of Preclinical Pharmacokinetic Properties and Prediction of Human PK Using a Physiologically Based Pharmacokinetic Model for a Novel Anti-Arrhythmic Agent Sulcardine Sulfate - Chang Ren; Yao Wang; Mei Zhang; Dexuan Kong; Chen Ning; Yujie Cheng; Yueying Bian; Mengqi Sun; Shengdi Su; Yucong Wang; Yongjie Zhang; Yang Lu; et al. (Pharmaceutical Research, 2023)

Tacrolimus improved the pregnancy outcomes of patients with refractory recurrent spontaneous abortion and immune bias disorders: a randomized controlled trial - Juan Liu; Meiqin Li; Jinhua Fu; Guiling Yuan; Ning Li; Yinghui Fu; Long Zhao (European Journal of Clinical Pharmacology, 2023)

Microbial species from multiple maternal body sites shape the developing giant panda ( Ailuropoda melanoleuca ) cub gut microbiome - Wei Guo; Ke Ren; Ruihong Ning; Caiwu Li; Yu Zhang; Yunong Gan; Xiaoyan Fu; Cenjun Xiao; Yaoyu Pang; Lei Cheng; Siyuan Zhang; Desheng Li; et al. (Molecular Ecology, 2023)
The gut microbiome of the giant panda ( Ailuropoda melanoleuca ) plays a vital role in nutrient acquisition from its specialized bamboo diet. Giant panda cubs harbour significantly different gut microbiota during their growth and development when feeding on milk before switching to bamboo. The fetal gut is sterile, and following birth, mother‐to‐infant microbial transmission has been implicated as a seeding source for the infant gut microbiota. Details of this transmission in giant pandas remain unclear. In this study, faecal samples were collected from seven panda mother–cub pairs when the cubs were 4–16 months old. Additional samples from the cubs' diet, soil and drinking water, and multiple body sites of the mothers were collected. Bacterial 16S rRNA gene sequencing and shotgun metagenomic sequencing were performed to determine the source and potential transmission routes of the cub gut microbiome. Source tracking analysis showed that maternal vagina, milk and faeces were the primary contributory sources of microbes, shaping the cub gut microbiome. Bacterial species from maternal faeces persisted the longest in the cub gut. Bacterial species in the diet contributed to the microbial community. Metagenomics analysis indicated that the predicted metabolic pathways of the gut microbiome also varied at different growth stages. Gut colonization with bacteria from various body sites of the mothers provides a foundational microbial community that is beneficial in fulfilling the evolving dietary needs of the cubs. This study suggests that mother‐to‐cub transmission is indispensable in shaping the gut microbiome of the developing panda cub.

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

Euphorfinoids A and B, a pair of ent -atisane diterpenoid epimers from the roots of Euphorbia fischeriana, and their bioactivities - Jiang-Chun Wei; Yu-Ning Gao; Hui-Hui Huang; Xiao-Yu Zhang; Xuan-Li Liu; Xiao-Xu Gao; Na Li; Yue Zhao; An-Hua Wang; Jing-Ming Jia (Natural Product Research, 2023)

Progressively narrow the gap of PM2.5 pollution characteristics at urban and suburban sites in a megacity of Sichuan Basin, China - Ning Wang; Li Zhou; Miao Feng; Tianli Song; Zhuoran Zhao; Danlin Song; Qinwen Tan; Fumo Yang (Journal of Environmental Sciences, 2023)

Multiplex single-cell droplet PCR with machine learning for detection of high-risk human papillomaviruses - Yizheng Huang; Linjun Sun; Wenwen Liu; Ling Yang; Zhigang Song; Xin Ning; Weijun Li; Manqing Tan; Yude Yu; Zhao Li (Analytica Chimica Acta, 2023)

Oxidation of simulated wastewater by Fe2+-catalyzed system: The selective reactivity of chlorine radicals and the oxidation pathway of aromatic amines - Xiaojun Lai; Nuoyi Huang; Xiaohua Zhao; Yang Li; Yao He; Jiesen Li; Jinhuan Deng; Xun-an Ning (Chemosphere, 2023)

Corrigendum to “First deliveries of felines by transcervical transfer of in vitro-cultured embryos” [Theriogenology 193 (2022) 30–36] - Li Hui; Wang Ning; You Rongjing; Yin Shen; Yuan Bao; Chen Jian; Ren Wenzhi; Liang Shuang; Zhao Minghui (Theriogenology, 2023)

Effects of high temperature stress on the intestinal histology and microbiota in Yesso scallop Patinopecten yessoensis - Ning Kong; Junyan Zhao; Bao Zhao; Jinyu Liu; Fuzhe Li; Lingling Wang; Linsheng Song (Marine Environmental Research, 2023)

Ultrafast extraction of uranium from seawater using photosensitized biohybrid system with bioinspired cascaded strategy - Man Wang; Lijuan Feng; Guangsheng Luo; Tiantian Feng; Shilei Zhao; Hui Wang; Se Shi; Tao Liu; Qiongyao Fu; Jingquan Li; Ning Wang; Yihui Yuan (Journal of Hazardous Materials, 2023)

Perfluoroalkyl and polyfluoroalkyl substances (PFAS) adsorbed on microplastics in drinking water: Implications for female exposure, reproductive health risk and its mitigation strategies through in silico methods - Meijin Du; Qikun Pu; Xixi Li; Hao Yang; Ning Hao; Qing Li; Yuanyuan Zhao; Yu Li (Journal of Cleaner Production, 2023)

Human exposure to a mixture of endocrine disruptors and serum levels of thyroid hormones: A cross-sectional study - Bing Yue; Shangyong Ning; Hongjian Miao; Congrong Fang; Jingguang Li; Lei Zhang; Yan Bao; Sai Fan; Yunfeng Zhao; Yongning Wu (Journal of Environmental Sciences, 2023)

Transcriptomic analysis of entomopathogenic fungus Beauveria bassiana infected by a hypervirulent polymycovirus BbPmV-4 - Qin Kang; Siyu Ning; Li Sui; Yang Lu; Yu Zhao; Wangpeng Shi; Qiyun Li; Zhengkun Zhang (Fungal Biology, 2023)

Quality assessment of royal jelly based on physicochemical properties and flavor profiles using HS-SPME-GC/MS combined with electronic nose and electronic tongue analyses - Lili Chen; Fangjian Ning; Li Zhao; Huihui Ming; Jinping Zhang; Wenjie Yu; Shengxiang Yi; Liping Luo (Food Chemistry, 2023)

Succession dynamics of microbial communities responding to the exogenous microalgae ZM-5 and analysis of the environmental sustainability of a constructed wetland system - Xinyue Zhao; Xiangwei Meng; Bin Dang; Tuoshi Zhang; Wen Shi; Ning Hou; Qingsheng Yan; Chunyan Li (Bioresource Technology, 2023)

Research on the Purification Performance of a Floating Island System Treating the Effluent of WWTP Under Different Seasons - Zhao-xu Peng; Ning-qi Niu; Ting-mei Li; Lu-ji Yu; Li-kun Gu; Ming-hui Liu (Water, Air, & Soil Pollution, 2023)

Dynamic modeling of tectonic carbon processes: State of the art and conceptual workflow - Liang Zhao; Zhengtang Guo; Huaiyu Yuan; Xinxin Wang; Hao Shen; Jianfeng Yang; Baolu Sun; Ning Tan; Hui Zhang; Yonggang Liu; Yang Li; Jiamin Wang; et al. (Science China Earth Sciences, 2023)

RNA interference-induced silencing of the SlHSP17.7 gene delays fruit ripening in tomato - Wenchao Liu; Xiaoming Zhao; Bing Bai; Yang Xie; Dan Li; Xiujie Mao; Ning Zhang (Journal of Plant Biochemistry and Biotechnology, 2023)

Spatial distribution and inventory of natural gas hydrate in the Qiongdongnan Basin, northern South China Sea - Zhongxian Zhao; Ning Qiu; Zhen Sun; Wen Yan; Genyuan Long; Pengchun Li; Haiteng Zhuo (Journal of Oceanology and Limnology, 2023)

A combination of umbilical cord mesenchymal stem cells and monosialotetrahexosy 1 ganglioside alleviates neuroinflammation in traumatic brain injury - Yanwei Fang; Wenna Qiu; Xin Li; Qianxu Jin; Hongshan Yan; Ning Yu; Jianhui Zhao; Yi Tan; Zongmao Zhao (Experimental Brain Research, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Two new tetrahydroisoquinoline alkaloids from Portulaca oleracea - Kai-Jun Tang; Yu Chen; Jing Li; Xu Tao; Lu-Ping Yang; Tian-Yun Jin; Jia-Shun Zhu; Yu Zhao; Tao Shen; Xiao-Ning Wang; Dong-Mei Ren; Lan Xiang (Phytochemistry Letters, 2023)

A novel exposure mode based on UVA-LEDs for bacterial inactivation - Ning Zhao; Li-Ping Lv; Ping Ma; Yang-Yang Zhang; Jiang Deng; Yan-Yu Zhang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Occurrence, spatial distribution, and sources of PFASs in the water and sediment from lakes in the Tibetan Plateau - Yu Chen; Lijia Wei; Wei Luo; Ning Jiang; Yali Shi; Pin Zhao; Bila Ga; Zhiguo Pei; Yingming Li; Ruiqiang Yang; Qinghua Zhang (Journal of Hazardous Materials, 2023)

Novel highly active and selective Co N S C efficient ORR catalyst derived from in-situ egg gel pyrolysis - Yue Cao; Yegeng Sun; Ning Han; Xue Li; Qing Wang; Kuizhao Sun; Weimeng Si; Fagang Wang; Xiaolin Zhao; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; et al. (Fuel, 2023)

Flexible demographic strategies promote the population persistence of a pioneer conifer tree (Pinus massoniana) in ecological restoration - Jiazheng Wang; Xianyu Yang; Gabriel Silva Santos; Hongtao Ning; Tian Li; Wenhao Zhao; Xiaoqian Si; Sihang Lu; Shouzhong Li (Forest Ecology and Management, 2023)

Quantitative determination of d-psicose based on flexible copper film materials and electrochemical scanning methods - Jingyu Zhang; Chengxiang Yong; Xiangchen Li; Runhao Zhu; Yongzhi Lai; Rui Peng; Ruizhi Zhao; Tianxi Yu; Jingyuan Ning; Siyi Xiong; Guohua Hui; Peng Wu (Food Chemistry, 2023)

3D DEM modeling on mechanical weakening of gas hydrate-bearing sandy sediments during hydrate dissociation - Xiaofeng Dou; Zhichao Liu; Fulong Ning; Yanlong Li; Xiaodong Li; Yingjie Zhao; Wei Hu; Deli Gao (Computers and Geotechnics, 2023)

Enhanced biodegradation of PAHs by biochar and a TiO2@biochar composite under light irradiation: Photocatalytic mechanism, toxicity evaluation and ecological response - Dapeng Li; Yongping Fang; Jia Lu; Jinao Sun; Xin Zhao; Ning Hou; Jie Xing (Chemical Engineering Journal, 2023)

Bio-inspired superhydrophobic interface of nano-gaseous film for reducing injection pressure in oil reservoirs - Zhongzheng Xu; Mingwei Zhao; Yiming Zhang; Pan Wang; Yining Wu; Lin Li; Xin Cui; Ning Sun; Caili Dai (Chemical Engineering Journal, 2023)

Analysis of microplastics released from plastic take-out food containers based on thermal properties and morphology study - Jia-Ling Hu; Yipin Duan; Huai-Ning Zhong; Qin-Bao Lin; Tianlong Zhang; Chuang-Chuang Zhao; Sheng Chen; Ben Dong; Dan Li; Jing Wang; Ming-Zhen Mo; Jie Chen; et al. (Food Additives & Contaminants: Part A, 2023)

Spatial distributions of intra-community tree species under topographically variable conditions - Ting Lv; Rong Zhao; Ning-jie Wang; Lei Xie; Yue-yao Feng; Yao Li; Hui Ding; Yan-ming Fang (Journal of Mountain Science, 2023)

Genetic characteristics and growth patterns of the hybrid grouper derived from the hybridization of Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male) - Liu Cao; Pan Chen; Xingrong Hou; Jun Ma; Ning Yang; Yanping Xu; Yanjin Zhang; Anqi Zhao; Jiyuan Zhang; Xinyu Li; Hai Huang (Journal of Fish Biology, 2023)
Hybridization is one of the primary methods used to cultivate farmed grouper species. The hybrid grouper derived from crossing Epinephelus fuscoguttatus (♀) and E. polyphekadion (♂) exhibits growth superiority over its parents. The genetic characteristics and growth patterns of the hybrid grouper have not yet been defined. This study confirms the ploidy level of the hybrid grouper (2 n = 48) using chromosome count analysis and flow cytometry. The 5S rDNA family was used to evaluate genetic diversity. Only one 5S class (~400 bp) was detected in the hybrid grouper, which could be used to distinguish between two different types based on nucleotide sequences, likely representing homologous unit classes from the female and male parental species. Growth patterns of 5–8‐month‐old hybrid groupers were also monitored. In this phase, a positive allometric growth pattern in body mass with total length was found. Body height and body mass were significantly correlated based on correlation and path coefficient, suggesting that body height could serve as an excellent index to increase body mass. These results aid our understanding of the genetic evolution of the hybrid grouper and inform the development of improved rearing techniques.

Predicting the monthly consumption and production of natural gas in the USA by using a new hybrid forecasting model based on two-layer decomposition - Shuai Jiang; Xiu-Ting Zhao; Ning Li (Environmental Science and Pollution Research, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Preclinical pharmacokinetics, biodistribution, excretion, and plasma protein binding study of 58Fe-labeled hemin by ICP-MS - Yongjie Zhang; Jie Xu; Jie Zhao; Huili Chen; Ning Li; Xijing Chen; Di Zhao (Journal of Trace Elements in Medicine and Biology, 2023)

Passivation of positively charged cationic defects in perovskite with nitrogen-donor crown ether enabling efficient perovskite solar cells - Yuxuan Yang; Tao Zhao; Ming-Hua Li; Xiaoxue Wu; Mingyue Han; Shih-Chi Yang; Qiaoling Xu; Lede Xian; Xiang Chi; Ning-Jiu Zhao; Hong Cui; Sihan Li; et al. (Chemical Engineering Journal, 2023)

Shading reduced the compensation and enhancement effects of soil nutrition on the growth of cotyledon-damaged Quercus acutissima seedlings - Haonan Chen; Mingming Zhao; Luyu Qi; Xinke Sun; Qiang Li; Xiao Liu; Ning Wang; Janusz J. Zwiazek; Wenqing Zhang; Weihua Guo; Renqing Wang; Fengyu Zhang; et al. (Plant and Soil, 2023)

How do temperature, humidity, and air saturation state affect the COVID-19 transmission risk? - Ning Mao; Dingkun Zhang; Yupei Li; Ying Li; Jin Li; Li Zhao; Qingqin Wang; Zhu Cheng; Yin Zhang; Enshen Long (Environmental Science and Pollution Research, 2023)

Detection and assessment of dust mite allergens in an indoor environment in Anhui, China - Qiqi Xue; Minghui Zou; Junjie Guo; Qiao Teng; Qiqi Zhang; Lingwei Sheng; Sijia Xu; Can Fang; Ning Yao; Yuanyuan Li; Jinhong Zhao (Environmental Science and Pollution Research, 2023)
Dust in the home environment is thought to be a potential trigger for increasing allergic diseases, such as allergic rash, rhinitis, asthma, and other conditions, associated with dust mites. To verify the status of dust mite prevalence in indoor surroundings, we collected 189 dust samples from the air conditioner filters ( n = 75) and floors ( n = 114) of households, schools, and hotels in the Anhui area, China. All samples were measured for dust mite breeding rate and breeding density under light microscopy and analyzed for dust mite species Dermatophagoides farinae 1 (Der f 1) and Dermatophagoides pteronyssinus 1 (Der p 1) allergen using enzyme-linked immunosorbent assay (ELISA). The dust mite breeding rates were 34.67% (26/75) and 20.18% (23/114), respectively, in the dust samples from the floor and air conditioning filters. The breeding density was the highest in households (10/g), followed by schools (9/g) and hotels (4/g). ELISA indicated that the allergen threshold (2.0 µg/g dust) of Der f 1 was exceeded in only two samples and Der p 1 in one sample. Additionally, a questionnaire was used to investigate the health knowledge on allergic diseases involved in indoor facilities, finding that most allergy sufferers were aware that indoor dust might be responsible for their conditions. The findings suggest that regular maintenance of indoor hygiene and cleaning of air-conditioning filters should reduce the risks of exposure to indoor allergens.

Geoacoustic monitoring technology of debris flow based on piezoelectric sensor - Hanchuan Dong; Lide Fang; Zhigang Tao; Lili Pang; Ning Zhao; Xiaoting Li (Arabian Journal of Geosciences, 2023)

Therapeutic Effects of Human Pluripotent Stem Cell-Derived Mesenchymal Stem Cells on a Murine Model of Acute Type-2-Dominated Airway Inflammation - Si-Yuan Ma; Ning Zhao; Lele Cui; Ying Li; Hang Zhang; Jing Wang; Jie Pang; Ming Wang; Chengshuo Wang; Sun Ying; Zi-Bing Jin; Luo Zhang (Stem Cell Reviews and Reports, 2022)

Failure criteria of unreinforced masonry walls of rural buildings under the impact of flash floods in mountainous regions - Guang-wu Si; Xiao-qing Chen; Jian-gang Chen; Wan-yu Zhao; Shuai Li; Xiang-ning Li (Journal of Mountain Science, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Mitigation of atrazine-induced oxidative stress on soybean seedlings after co-inoculation with atrazine-degrading bacterium Arthrobacter sp. DNS10 and inorganic phosphorus-solubilizing bacterium Enterobacter sp. P1 - Zhao Jiang; Qi Shao; Yuxin Chu; Ning An; Bo Cao; Zheyi Ren; Jin Li; Jianhua Qu; Maofeng Dong; Ying Zhang (Environmental Science and Pollution Research, 2022)

Analysis of Host Cell Proteins in Monoclonal Antibody Therapeutics Through Size Exclusion Chromatography - Bo Zhao; Polat Abdubek; Sisi Zhang; Hui Xiao; Ning Li (Pharmaceutical Research, 2022)

A novel hollow microsphere composite MnOx/PAA: effective catalyst for ozone decomposition at high humidity - Wei Liu; Jingwen Zhang; Zhao Dai; Ning Luo; Jing Qu; Peiyun Sun; Da Li; Weilong Liao; Junfu Wei; Huan Zhang (Environmental Science and Pollution Research, 2022)

Stem Cell-Derived Exosomes: A New Method for Reversing Skin Aging - Jin-Yan Wu; Sai-Nan Wu; Li-Ping Zhang; Xian-Sheng Zhao; Yue Li; Qu-Yang Yang; Ruo-Yue Yuan; Jian-Lan Liu; Hong-Ju Mao; Ning-Wen Zhu (Tissue Engineering and Regenerative Medicine, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

Effects of straw returning on soil moisture and maize yield in semi-humid area - Lihua Zhang; Hongxiang Zhao; Chen Xu; Weiping Yan; Ning Sun; Guobo Tan; Jiang Yu; Xiangmeng Meng; Fei Li; Shaofeng Bian (Cereal Research Communications, 2022)

Stability analysis of complex terrain slope based on multi-source point cloud fusion - Wen-bo Zan; Wen-jie Zhang; Ning Wang; Chun-chen Zhao; Qian Yang; Hao Li (Journal of Mountain Science, 2022)

Comparative genomic analysis of the genus Marinomonas and taxonomic study of Marinomonas algarum sp. nov., isolated from red algae Gelidium amansii - Jian-Heng Xue; Bei-Ning Zhang; Feng Zhang; Ying-Ying Liu; Wen-Jie Wu; Zhao-Ming Wu; Yue Si; Peng-Xi Yang; Xiang Xing; Li-Hua Zhao (Archives of Microbiology, 2022)

Oxytocin Receptor in Cerebellar Purkinje Cells Does Not Engage in Autism-Related Behaviors - Li-Ping Shen; Wei Li; Ling-Zhu Pei; Jun Yin; Shu-Tao Xie; Hong-Zhao Li; Chao Yan; Jian-Jun Wang; Qipeng Zhang; Xiao-Yang Zhang; Jing-Ning Zhu (The Cerebellum, 2022)

Identification and expression of potential olfactory-related genes related to Niemann–Pick C2 protein and ionotropic receptors in Haemaphysalis longicornis - Yingying Cui; Jungang Wang; Qiyong Liu; Dongmei Li; Wen Zhang; Xiaobo Liu; Jun Wang; Xiuping Song; Feng Yao; Haixia Wu; Ning Zhao (Experimental and Applied Acarology, 2022)

The impacts of carbon emissions and voluntary carbon disclosure on firm value - Zhao-Yong Sun; Shu-Ning Wang; Dongdong Li (Environmental Science and Pollution Research, 2022)

Folic acid alleviates lead acetate-mediated cardiotoxicity by down-regulating the expression levels of Nrf2, HO-1, GRP78, and CHOP proteins - Ning Li; Yali Zhao; Fangyu Wang; Lianjun Song; Mingwu Qiao; Tianlin Wang; Xianqing Huang (Environmental Science and Pollution Research, 2022)

Development of molecular markers based on CRa gene sequencing of different clubroot disease-resistant cultivars of Chinese cabbage - Ting Lei; Ning Li; Jinjian Ma; Maixia Hui; Limin Zhao (Molecular Biology Reports, 2022)

ArsZ from Ensifer adhaerens ST2 is a novel methylarsenite oxidase - Jun Zhang; Yan‐Ning Li; Jian Chen; Yu Yan; Barry P. Rosen; Fang‐Jie Zhao (Environmental Microbiology, 2022)
Summary Trivalent methylarsenite [MAs(III)] produced by biomethylation is more toxic than inorganic arsenite [As(III)]. Hence, MAs(III) has been proposed to be a primordial antibiotic. Other bacteria evolved mechanisms to detoxify MAs(III). In this study, the molecular mechanisms of MAs(III) resistance of Ensifer adhaerens ST2 were investigated. In the chromosome of E. adhaerens ST2 is a gene encoding a protein of unknown function. Here, we show that this gene, designated arsZ , encodes a novel MAs(III) oxidase that confers resistance by oxidizing highly toxic MAs(III) to relatively nontoxic MAs(V). Two other genes, arsRK , are adjacent to arsZ but are divergently encoded in the opposite direction. Heterologous expression of arsZ in Escherichia coli confers resistance to MAs(III) but not to As(III). Purified ArsZ catalyses thioredoxin‐ and NAPD + ‐dependent oxidation of MAs(III). Mutational analysis of ArsZ suggests that Cys59 and Cys123 are involved in the oxidation of MAs(III). Expression of arsZ , arsR and arsK genes is induced by MAs(III) and As(III) and is likely controlled by the ArsR transcriptional repressor. These results demonstrate that ArsZ is a novel MAs(III) oxidase that contributes to E. adhaerens tolerance to environmental organoarsenicals. The arsZRK operon is widely present in bacteria within the Rhizobiaceae family.

Sim-to-Real: Mapless Navigation for USVs Using Deep Reinforcement Learning - Ning Wang; Yabiao Wang; Yuming Zhao; Yong Wang; Zhigang Li (Journal of Marine Science and Engineering, 2022)
In recent years, mapless navigation using deep reinforcement learning algorithms has shown significant advantages in improving robot motion planning capabilities. However, the majority of past works have focused on aerial and ground robotics, with very little attention being paid to unmanned surface vehicle (USV) navigation and ultimate deployment on real platforms. In response, this paper proposes a mapless navigation method based on deep reinforcement learning for USVs. Specifically, we carefully design the observation space, action space, reward function, and neural network for a navigation policy that allows the USV to reach the destination collision-free when equipped with only local sensors. Aiming at the sim-to-real transfer and slow convergence of deep reinforcement learning, this paper proposes a dynamics-free training and consistency strategy and designs domain randomization and adaptive curriculum learning. The method was evaluated using a range of tests applied to simulated and physical environments and was proven to work effectively in a real navigation environment.

Oceanisphaera pacifica sp. nov., isolated from the intestine of Trichiurus japonicus - Jian-Heng Xue; Li-Fang Shi; Bei-Ning Zhang; Wen-Jie Wu; Yuan Gao; Qian Zhu; Li-Hua Zhao (Archives of Microbiology, 2022)

Follicular Fluid-Derived Exosomal MicroRNA-18b-5p Regulates PTEN-Mediated PI3K/Akt/mTOR Signaling Pathway to Inhibit Polycystic Ovary Syndrome Development - Zhi Zhou; Zhihua Tu; Juan Zhang; Can tan; Xiaoyong Shen; Bangbei Wan; Yejuan Li; Anguo Wang; Liqiang Zhao; Jiajia Hu; Ning Ma; Jing Zhou; et al. (Molecular Neurobiology, 2022)

Pregnancy leads to changes in the brain functional network: a connectome analysis - Tongpeng Chu; Yuna Li; Kaili Che; Fanghui Dong; Heng Ma; Yinghong Shi; Peiyou Gong; Feng Zhao; Xicheng Song; Haizhu Xie; Ning Mao (Brain Imaging and Behavior, 2022)

The CBM48 domain-containing protein FLO6 regulates starch synthesis by interacting with SSIVb and GBSS in rice - Long Zhang; Ning Li; Jing Zhang; Linglong Zhao; Jiajing Qiu; Cunxu Wei (Plant Molecular Biology, 2022)

Association between maternal exposure to PM10 and risk of anorectal atresia/stenosis in offspring: a population-based case-control study in Liaoning Province, China - Tie-Ning Zhang; Qi-Jun Wu; Yan-Hong Huang; Jing Li; Zong-Jiao Chen; Li-Li Li; Yan-Ling Chen; Shu Liu; Cheng-Zhi Jiang; Yu-Hong Zhao (Environmental Science and Pollution Research, 2022)

Stilbenoids from the roots of Stemona tuberosa - Hong-Mei Li; Tian-Tian He; Miao Zhang; Jia-Ning Liu; Xue Zhao; Jie Liu; Lei Fang (Natural Product Research, 2022)

Shifting from homogeneous to heterogeneous surfaces in estimating terrestrial evapotranspiration: Review and perspectives - Yuanbo Liu; Guoyu Qiu; Hongsheng Zhang; Yonghui Yang; Yinsheng Zhang; Quan Wang; Wenzhi Zhao; Li Jia; Xibin Ji; Yujiu Xiong; Chunhua Yan; Ning Ma; et al. (Science China Earth Sciences, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Efficacy and safety of aripiprazole once-monthly versus oral aripiprazole in Chinese patients with acute schizophrenia: a multicenter, randomized, double-blind, non-inferiority study - Le Xiao; Qian Zhao; An-ning Li; Jushui Sun; Bin Wu; Lina Wang; Honggeng Zhang; Ruiling Zhang; Keqing Li; Xiaojin Xu; Tiebang Liu; Wenshun Zhang; et al. (Psychopharmacology, 2022)

Formation Process of Silicate-Iron Oxyhydroxide Complex and Its Influence on the Distribution of Heavy Metals in Mining Area - Qun Zhao; Jiangtao He; Xinrui Yan; Chen Li; Jie Li; YingJie Li; Senlin Tian; Jianhong Huang; Ping Ning (Bulletin of Environmental Contamination and Toxicology, 2021)

RETRACTED ARTICLE: Characterization of Preclinical Pharmacokinetic Properties and Prediction of Human PK Using a Physiologically Based Pharmacokinetic Model for a Novel Anti-Arrhythmic Agent Sulcardine Sulfate - Chang Ren; Yao Wang; Mei Zhang; Dexuan Kong; Chen Ning; Yujie Cheng; Yueying Bian; Mengqi Sun; Shengdi Su; Yucong Wang; Yongjie Zhang; Yang Lu; et al. (Pharmaceutical Research, 2021)

Two New Zn(II)/Cu(II) Compounds: Photoluminescent and Photocatalytic Properties, and Protective Activity on Parkinson Disease - Ning Wang; Fang-Jie Huang; Mang-Suo Zhao; Bing-Xin Shi; Yan Wei; Li-Yan Qiao (Journal of Fluorescence, 2021)

Postnatal development of BAG3 expression in mouse cerebral cortex and hippocampus - Xinlu Li; Geng Lin; Tongtong Liu; Ning Zhao; He Xu; Huaqin Wang; Wei Zheng (Brain Structure and Function, 2021)

Rockburst response in hard rock owing to excavation unloading of twin tunnels at great depth - Fan Feng; Xibing Li; Lin Luo; Xingdong Zhao; Shaojie Chen; Ning Jiang; Wanpeng Huang; Yajun Wang (Bulletin of Engineering Geology and the Environment, 2021)

Compounded chelating agent derived from fruit residue extracts effectively enhances Cd phytoextraction by Sedum alfredii - Jipeng Luo; Jiabin Liang; Yuchao Song; Xinyu Guo; Youzheng Ning; Nanlin Liu; Heping Zhao; Tingqiang Li (Soil Ecology Letters, 2021)

A new benzophenone with biological activities from metabolites of butyrolactone I in rat faeces - Bing Liu; Ning Chen; Ying Xu; Jia-Wei Zhang; Yuan Sun; Li-Zhu Zhao; Yu-bin Ji (Natural Product Research, 2021)

Application of constructed wetlands in treating rural sewage from source separation with high-influent nitrogen load: a review - Xiangyu Li; Longjian Yang; Kaiqin Xu; Ke Bei; Xiangyong Zheng; Shiwen Lu; Ning An; Jinshan Zhao; Zhan Jin (World Journal of Microbiology and Biotechnology, 2021)

Do proinflammatory cytokines play a role in clozapine-associated glycometabolism disorders? - Tongtong Zhao; Kai Zhang; Yelei Zhang; Yating Yang; Xiaoshuai Ning; Yu Hu; Xiaoyue Li; Yulong Zhang; Lei Xia; Zhenhua Ren; Huanzhong Liu (Psychopharmacology, 2021)
Rationale and objective Clozapine (CLZ) is the most effective drug for treatment-resistant schizophrenia but is associated with many side effects, including glycometabolism disorders. Immunological mechanisms may be involved in the development of clozapine side effects. Research relating the immunomodulatory effects of clozapine and its early markers to clinically relevant adverse events is needed to reduce the harmful side effects of clozapine. This study aimed to investigate the role of proinflammatory cytokines in clozapine-associated glycometabolism disorders. Methods We measured the effect of a range of doses of clozapine on glycometabolism-related parameters and proinflammatory cytokines levels in mice peripheral blood. We also examined the differences between these indicators in the peripheral blood of clozapine-treated schizophrenia patients and healthy controls. Furthermore, we detected proinflammatory cytokines expression in mice pancreatic tissue. Results Following clozapine administration, glucagon significantly decreased in mouse serum, and proinflammatory cytokine IL-β levels markedly increased. Clozapine reliably increased proinflammatory cytokines (IL-1β, IL-6, and TNF-α) expression in murine pancreatic tissue. Compared with healthy controls, clozapine-treated patients’ BMI, blood glucose, and proinflammatory cytokines (IL-1β, IL-6, and TNF-α) increased significantly. In clozapine-treated patients, a higher clozapine daily dosage was associated with higher levels of the proinflammatory cytokines IL-1β and IL-6, and a significant positive correlation was observed between blood glucose levels and the proinflammatory cytokines IL-6 and TNF-α. Conclusion Findings from animal experiments and clinical trials have shown clear evidence that clozapine has a regulatory effect on immune-related proinflammatory cytokines and influences glycometabolism indicators.

Changes in carbon fractions with corn straw incorporation and comparison of carbon sequestration efficiency in Phaeozem derived from two parent materials in China - Ning Hu; Lanpo Zhao; Qiao Li; Yimei Jiang; Biao Sui; Hongbin Wang (Arabian Journal of Geosciences, 2021)

Roles of bulk and rhizosphere denitrifying bacteria in denitrification from paddy soils under straw return condition - Ning Wang; Ya-Hui Zhao; Jian-Guang Yu; Li-Hong Xue; Hong-Bo Li; Lin-Zhang Yang (Journal of Soils and Sediments, 2021)

Comprehensive Analysis of Synonymous Codon Usage Bias for Complete Genomes and E2 Gene of Atypical Porcine Pestivirus - Xianglong Yu; Jianxin Liu; Huizi Li; Boyang Liu; Bingqian Zhao; Zhangyong Ning (Biochemical Genetics, 2021)

Iridoid compounds from the aerial parts of Swertia mussotii Franch. with cytotoxic activity - Haixia Wang; Huiming Huang; Jingwei Lv; Ning Jiang; Yujiao Li; Xinmin Liu; Hongping Zhao (Natural Product Research, 2021)

Breast cancer organoids from malignant pleural effusion-derived tumor cells as an individualized medicine platform - Bo Pan; Dongyi Zhao; Yaqian Liu; Na Li; Chen Song; Ning Li; Xuelu Li; Zuowei Zhao (In Vitro Cellular & Developmental Biology - Animal, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Evaluation of the efficacy and safety of hydroxychloroquine in comparison with chloroquine in moderate and severe patients with COVID-19 - Qiuyu Li; Cheng Cui; Fei Xu; Jianping Zhao; Nan Li; Haichao Li; Tianbing Wang; Hua Zhang; Na Liu; Yudong Wei; Xiaoye Niu; Yan Xu; et al. (Science China Life Sciences, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Perinatal Lead Exposure Alters Calsyntenin-2 and Calsyntenin-3 Expression in the Hippocampus and Causes Learning Deficits in Mice Post-weaning - Ning Li; Shuai Cao; Zengli Yu; Mingwu Qiao; Yongxia Cheng; Yue Shen; Lianjun Song; Xianqing Huang; Guojun Yang; Yali Zhao (Biological Trace Element Research, 2021)

Space–time variations of sea ice in Bohai Sea in the winter of 2009–2010 simulated with a coupled ocean and ice model - Rui Li; Youyu Lu; Xianmin Hu; Donglin Guo; Peng Zhao; Ning Wang; Kenneth Lee; Baiyu Zhang (Journal of Oceanography, 2021)

Metabolomics integrated with transcriptomics: assessing the central metabolism of marine red yeast Sporobolomyces pararoseus under salinity stress - Chunji Li; Die Zhao; Jianyu Yan; Ning Zhang; Bingxue Li (Archives of Microbiology, 2021)

Tyrosine kinase Fyn promotes apoptosis after intracerebral hemorrhage in rats by activating Drp1 signaling - Li Zhang; Lu Wang; Han Xiao; Hui Gan; Hui Chen; Shuyue Zheng; Dan Jian; Xuan Zhai; Ning Jiang; Zhao Jing; Ping Liang (Journal of Molecular Medicine, 2021)

Multiple‐scale negative impacts of warming on ecosystem carbon use efficiency across the Tibetan Plateau grasslands - Ning Chen; Yangjian Zhang; Juntao Zhu; Nan Cong; Guang Zhao; Jiaxing Zu; Zhipeng Wang; Ke Huang; Li Wang; Yaojie Liu; Zhoutao Zheng; Ze Tang; et al. (Global Ecology and Biogeography, 2021)
Aim Ecosystem carbon use efficiency (CUEe) is a core parameter of ecosystem process models, but its relationships with climate are still uncertain, especially for ecosystems with harsh environments. Large inconsistencies in climate impacts on the CUEe have been reported among various spatial scales. The goal of this study was to examine whether warming promotes or restricts the CUEe and whether the CUEe responds to a warming gradient in a linear or nonlinear manner. Location Tibetan Plateau. Time period 2000–2018. Major taxa studied Alpine grassland ecosystem. Methods We integrated multiple‐source data of carbon fluxes and CUEe, including warming experiments at a site scale, eddy covariance observations at a landscape scale and synthesized warming experiments and ecosystem process models at a regional scale. Next, we deployed a statistical model to examine the warming impacts on the CUEe across scales; the effects of biotic and abiotic factors on the CUEe and its components were summarized based on the results of standardized major axis tests and routines, structural equation modelling and nonlinear models. Results This study reported a suppressive warming impact on the CUEe, which followed a nonlinear curve with severe inhibition in the high‐level warming treatment. With a warming threshold of 1.5–2.0°C, CUEe response patterns transitioned from no change to a significant decrease. The restriction effects can be ascribed to the joint adverse and asymmetric effects of warming on CUEe components under multiple‐level warming. Warming‐modified relationships among CUEe components and the nonlinear effects of biotic and abiotic factors led to the nonlinear responses of CUEe to warming. Main conclusions This study revealed suppressive and nonlinear effects of warming on the CUEe, including especially dramatic CUEe decreases with high‐level warming. These findings are critical for optimizing model parameters and improving predictions of the carbon sequestration capacity of alpine grasslands.

Monitoring monthly soil moisture conditions in China with temperature vegetation dryness indexes based on an enhanced vegetation index and normalized difference vegetation index - Huichao Zhao; Yi Li; Xinguo Chen; Haoran Wang; Ning Yao; Fenggui Liu (Theoretical and Applied Climatology, 2021)

IbERF71, with IbMYB340 and IbbHLH2, coregulates anthocyanin accumulation by binding to the IbANS1 promoter in purple-fleshed sweet potato (Ipomoea batatas L.) - Zhiyuan Ning; Kangdi Hu; Zhilin Zhou; Donglan Zhao; Jun Tang; Hong Wang; Lixia Li; Chen Ding; Xiaoyan Chen; Gaifang Yao; Hua Zhang (Plant Cell Reports, 2021)

Hypoxia-reoxygenation induces macrophage polarization and causes the release of exosomal miR-29a to mediate cardiomyocyte pyroptosis - Yan Wang; Zhimei Qiu; Jinson Yuan; Chaofu Li; Ranzun Zhao; Weiwei Liu; Wenwen Deng; Ning Gu; Wei Zhang; Shan Hu; Zhixun Bai; Bei Shi (In Vitro Cellular & Developmental Biology - Animal, 2021)

Climatology of equatorial and low-latitude F region kilometer-scale irregularities over the meridian circle around 120°E/60°W - Xiukuan Zhao; Haiyong Xie; Lianhuan Hu; Wenjie Sun; Xiqing Hao; Baiqi Ning; Hisao Takahashi; Guozhu Li (GPS Solutions, 2021)

Comprehensive analysis of synonymous codon usage patterns and influencing factors of porcine epidemic diarrhea virus - Xianglong Yu; Jianxin Liu; Huizi Li; Boyang Liu; Bingqian Zhao; Zhangyong Ning (Archives of Virology, 2021)

Correction to: The H741D mutation in Tac1p contributes to the upregulation of CDR1 and CDR2 expression in Candida albicans - Jin-Yan Liu; Bing Wei; Ying Wang; Ce Shi; Wen-Jing Li; Yue Zhao; Ling-Ning Meng; Ming-Jie Xiang (Brazilian Journal of Microbiology, 2020)

The H741D mutation in Tac1p contributes to the upregulation of CDR1 and CDR2 expression in Candida albicans - Jin-Yan Liu; Bing Wei; Ying Wang; Ce Shi; Wen-Jing Li; Yue Zhao; Ling-Ning Meng; Ming-Jie Xiang (Brazilian Journal of Microbiology, 2020)

In vitro dual-target activities and in vivo antidiabetic effect of 3-hydroxy-N-(p-hydroxy-phenethyl) phthalimide in high-fat diet and streptozotocin-induced diabetic golden hamsters - Bin Xiao; Yunfeng Xiao; Haining Ning; Xiaoyan Han; Wenyan Li; Yuheng Ma; Na Zhao; Guanhua Du; Yu Dong; Jee H. Jung; Zhanfei She (Medicinal Chemistry Research, 2020)

Deinococcus detaillensis sp. nov., isolated from humus soil in Antarctica - Kun Zhang; Jing Zhu; Shuai Li; Manik Prabhu Narsing Rao; Ning-Mei Li; Ang-Yang Guo; Zhao Jiang; Qi-Yong Tang; Yi Wan; Zhi-Dong Zhang; Wen-Jun Li (Archives of Microbiology, 2020)

Genomic diversity and recombination of Seneca Valley viruses emerged in pig herds in Guangdong Province during 2019 - Jianxin Liu; Qianju Guo; Huizi Li; Xianglong Yu; Boyang Liu; Bingqian Zhao; Zhangyong Ning (Virus Genes, 2020)

Soil fungal taxonomic diversity along an elevation gradient on the semi-arid Xinglong Mountain, Northwest China - Salman Khan; Ning Chen; Cankun Zhang; Luning Wang; Chun Han; Kanglong Lu; Yage Li; Muhammad Rafiq; Awais Iqbal; Changming Zhao (Archives of Microbiology, 2020)

Secreted frizzled-related protein 2 prevents pressure-overload-induced cardiac hypertrophy by targeting the Wnt/β-catenin pathway - Wen-Ying Wei; Qing Zhao; Wen-zhong Zhang; Mao-jing Wang; Yan Li; Shi-zhong Wang; Ning Zhang (Molecular and Cellular Biochemistry, 2020)

NLRP6 contributes to inflammation and brain injury following intracerebral haemorrhage by activating autophagy - Han Xiao; Hui Chen; Rong Jiang; Li Zhang; Lu Wang; Hui Gan; Ning Jiang; Jing Zhao; Xuan Zhai; Ping Liang (Journal of Molecular Medicine, 2020)

Influences of ABC transporter and CYP3A4/5 genetic polymorphisms on the pharmacokinetics of lenvatinib in Chinese healthy subjects - Jiaming Li; Xiaoqian Wang; Chen Ning; Zhaoyu Wang; Yao Wang; Ming Zheng; Siliang Zhang; Yang Lu; Yongjie Zhang; Ning Li; Xijing Chen; Di Zhao (European Journal of Clinical Pharmacology, 2020)

Preparation of heterogeneous Fenton catalyst γ-Cu-Ce-Al2O3 and the evaluation on degradation of phenol - Mei Li; Xinyu Gao; Heming Liu; Hongbo Wang; Qian Zhao; Ning Wang (Environmental Science and Pollution Research, 2020)

Mechanism of seepage-stress fault water inrush and grouting seal - Jinhai Zhao; Li Bo; Chen Juntao; Jiang Ning (Arabian Journal of Geosciences, 2020)

Effects and mechanisms of tea for the prevention and management of cancers: An updated review - Xiao-Yu Xu; Cai-Ning Zhao; Shi-Yu Cao; Guo-Yi Tang; Ren-You Gan; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2020)

The Diversity of Associated Microorganisms in Different Organs and Rhizospheric Soil of Arctium lappa L. - Yanping Xing; Yanyun Yang; Liang Xu; Ning Hao; Rong Zhao; Jiahao Wang; Shengnan Li; Dachuan Zhang; Tingting Zhang; Tingguo Kang (Current Microbiology, 2020)

Alleviation of osmotic stress by H2S is related to regulated PLDα1 and suppressed ROS in Arabidopsis thaliana - Min Zhao; Qin Liu; Yue Zhang; Ning Yang; Guofan Wu; Qiaoxia Li; Wei Wang (Journal of Plant Research, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Targeting gut microbiota with dietary components on cancer: Effects and potential mechanisms of action - Jun Tao; Sha Li; Ren-You Gan; Cai-Ning Zhao; Xiao Meng; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2020)

MOA-based linear and nonlinear QSAR models for predicting the toxicity of organic chemicals to Vibrio fischeri - Shengnan Zhang; Ning Wang; Limin Su; Xiaoyan Xu; Chao Li; Weichao Qin; Yuanhui Zhao (Environmental Science and Pollution Research, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

PEG-conjugated triacontanol micelles as docetaxel delivery systems for enhanced anti-cancer efficacy - Xiaoyu Lu; Min Fang; Yue Yang; Yu Dai; Jiaqiu Xu; Di Zhao; Yang Lu; Xijing Chen; Shan Lu; Ning Li (Drug Delivery and Translational Research, 2020)

ABCC2 c.-24 C>T single-nucleotide polymorphism was associated with the pharmacokinetic variability of deferasirox in Chinese subjects - Kangna Cao; Guanghui Ren; Chengcan Lu; Yao Wang; Yanan Tan; Jing Zhou; Yongjie Zhang; Yang Lu; Ning Li; Xijing Chen; Di Zhao (European Journal of Clinical Pharmacology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Chinese stalagmite paleoclimate researches: A review and perspective - Hai Cheng; Haiwei Zhang; Jingyao Zhao; Hanying Li; Youfeng Ning; Gayatri Kathayat (Science China Earth Sciences, 2019)

Warming effects on soil respiration in moss-dominated crusts in the Tengger Desert, northern China - Chao Guan; Xinrong Li; Ning Chen; Peng Zhang; Changming Zhao (Plant and Soil, 2019)

Re-examining the role of ventral tegmental area dopaminergic neurons in motor activity and reinforcement by chemogenetic and optogenetic manipulation in mice - Man-Yi Jing; Xiao Han; Tai-Yun Zhao; Zhi-Yuan Wang; Guan-Yi Lu; Ning Wu; Rui Song; Jin Li (Metabolic Brain Disease, 2019)

Site-specific integration of rotavirus VP6 gene in rabbit β-casein locus by CRISPR/Cas9 system - Hongli Li; Zhipeng Li; Ning Xiao; Xiaoping Su; Shanshan Zhao; Yu Zhang; Kuiqing Cui; Qingyou Liu; Deshun Shi (In Vitro Cellular & Developmental Biology - Animal, 2019)

Solidification/stabilization of municipal solid waste incineration fly ash using uncalcined coal gangue–based alkali-activated cementitious materials - Shujie Zhao; Faheem Muhammad; Lin Yu; Ming Xia; Xiao Huang; Binquan Jiao; Ning Lu; Dongwei Li (Environmental Science and Pollution Research, 2019)

A breeding strategy targeting the secondary gene pool of bread wheat: introgression from a synthetic hexaploid wheat - Ming Hao; Lianquan Zhang; Laibin Zhao; Shoufen Dai; Aili Li; Wuyun Yang; Die Xie; Qingcheng Li; Shunzong Ning; Zehong Yan; Bihua Wu; Xiujin Lan; et al. (Theoretical and Applied Genetics, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

A three-dimensional fluid-solid model, coupling high-rise building load and groundwater abstraction, for prediction of regional land subsidence - Zhao Li; Zujiang Luo; Qi Wang; Jingjing Du; Wei Lu; Di Ning (Hydrogeology Journal, 2019)

Potential effects of exploiting the Yunfu pyrite mine (southern China) on soil: evidence from analyzing trace elements in surface soil - Zhi-hua Tang; Ting-ping Ouyang; Ming-kun Li; Ning-sheng Huang; Yao-qiu Kuang; Qiao Hu; Zhao-yu Zhu (Environmental Monitoring and Assessment, 2019)

The choice of intrinsic axis under multi-cue conditions - Jing Li; Ning Xie; Weixun Zhao (Cognitive Processing, 2019)

A bioactive new protostane-type triterpenoid from Alisma plantago - aquatica subsp. orientale (Sam.) Sam. - Ya-Li Wang; Jian-Chao Zhao; Jia-Hao Liang; Xiang-Ge Tian; Xiao-Kui Huo; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Gang Chen; Ning Li; Cheng-Peng Sun (Natural Product Research, 2019)

Rac1 Modulates Excitatory Synaptic Transmission in Mouse Retinal Ganglion Cells - Ling-Zhu Li; Ning Yin; Xue-Yan Li; Yanying Miao; Shuo Cheng; Fang Li; Guo-Li Zhao; Shu-Min Zhong; Xin Wang; Xiong-Li Yang; Zhongfeng Wang (Neuroscience Bulletin, 2019)

A life support-based comprehensive treatment regimen dramatically lowers the in-hospital mortality of patients with fulminant myocarditis: a multiple center study - Sheng Li; Shengyong Xu; Chenze Li; Xiao Ran; Guanglin Cui; Mengying He; Kun Miao; Chunxia Zhao; Jiangtao Yan; Rutai Hui; Ning Zhou; Yan Wang; et al. (Science China Life Sciences, 2019)

Reconstructing the western boundary variability of the Western Pacific Subtropical High over the past 200 years via Chinese cave oxygen isotope records - Jingyao Zhao; Hai Cheng; Yan Yang; Liangcheng Tan; Christoph Spötl; Youfeng Ning; Haiwei Zhang; Xing Cheng; Zhe Sun; Xianglei Li; Hanying Li; Wen Liu; et al. (Climate Dynamics, 2019)

A comparison of next-generation sequencing with clone sequencing in the diet analysis of Asian great bustard - Minghao Gong; Yu Ning; Morigen Han; Chenyang Zhao; Jingxing Tian; Linwei Li; Hongye Xiao; Gang Liu (Conservation Genetics Resources, 2019)

MnO2-loaded microorganism-derived carbon for U(VI) adsorption from aqueous solution - Wei Liao; Huilin Wang; Feize Li; Changsong Zhao; Jun Liu; Jiali Liao; Jijun Yang; Yuanyou Yang; Ning Liu (Environmental Science and Pollution Research, 2019)

Oligosaccharides as co-encapsulating agents: effect on oral Lactobacillus fermentum survival in a simulated gastrointestinal tract - Ning Liao; Baolong Luo; Jing Gao; Xiaojuan Li; Zhixia Zhao; Yan Zhang; Yongqing Ni; Fengwei Tian (Biotechnology Letters, 2019)

Organic-rich source rock characterization and evaluation of the Cretaceous Qingshankou Formation: results from geophysical logs of the second scientific drilling borehole in the Songliao Basin, NE China - Xiaohuan Zhang; Changchun Zou; Jinhuan Zhao; Ning Li; Shuxia Zhang; Kouamelan Serge Kouamelan; Liang Xiao; Huolin Ma; Yixiong Niu (Geosciences Journal, 2019)

Geochemical and isotopic (U, Th) variations in lake waters in the Qinghai Lake Basin, Northeast Qinghai-Tibet Plateau, China: origin and paleoenvironmental implications - Pu Zhang; Hai Cheng; Weiguo Liu; Lingtong Mo; Xiangzhong Li; Youfeng Ning; Ming Ji; Baoyun Zong; Chen Zhao (Arabian Journal of Geosciences, 2019)

Benzene metabolite 1,2,4-benzenetriol changes DNA methylation and histone acetylation of erythroid-specific genes in K562 cells - Chun-Hong Yu; Yang Li; Xiao Zhao; Shui-Qing Yang; Lei Li; Ning-Xuan Cui; Long Rong; Zong-Chun Yi (Archives of Toxicology, 2019)

Application of a Simple Quantitative Assessment of Atherosclerotic Lesions in Freshly Isolated Aortas from Rabbits - Li-Jun Zhao; Ying Xiao; Xia Meng; Ning Wang; Y. James Kang (Cardiovascular Toxicology, 2018)

Antidepressant-like action of agmatine in the acute and sub-acute mouse models of depression: a receptor mechanism study - Zhao-Di Chen; Wen-Qiang Chen; Zhi-Yuan Wang; Dan-Ni Cao; Ning Wu; Jin Li (Metabolic Brain Disease, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Screening wheat genotypes for better performance on reduced phosphorus supply by comparing glasshouse experiments with field trials - De-Yong Zhao; Shu-Song Zheng; Muhammad Kashif Naeem; Jian-Qing Niu; Ning Wang; Zhong-Jian Li; Hui-Lan Wu; Hong-Qing Ling (Plant and Soil, 2018)

The complete chloroplast genome of Paeonia rockii (Paeoniaceae), an endangered endemic species to China - Guoqing Bai; Hewei Guo; Ning Zhao; Sifeng Li; Ying Zhang (Conservation Genetics Resources, 2018)

The chromatin remodeler ZmCHB101 impacts expression of osmotic stress-responsive genes in maize - Xiaoming Yu; Xinchao Meng; Yutong Liu; Ning Li; Ai Zhang; Tian-Jing Wang; Lili Jiang; Jinsong Pang; Xinxin Zhao; Xin Qi; Meishan Zhang; Shucai Wang; et al. (Plant Molecular Biology, 2018)

Pore structure and adsorption behavior of shale gas reservoir with influence of maturity: a case study of Lower Silurian Longmaxi formation in China - Tianyi Zhao; Xiangfang Li; Zhengfu Ning; Huawei Zhao; Jinglun Zhang; Wen Zhao (Arabian Journal of Geosciences, 2018)

Atlas of the Striatum and Globus Pallidus in the Tree Shrew: Comparison with Rat and Mouse - Rong-Jun Ni; Zhao-Huan Huang; Yu-Mian Shu; Yu Wang; Tao Li; Jiang-Ning Zhou (Neuroscience Bulletin, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

Hsp90 regulation affects the treatment of glucocorticoid for pancreatitis-induced lung injury - Yan Zhao; Ren-Ping Xiong; Xing Chen; Ping Li; Ya-Lei Ning; Nan Yang; Yan Peng; Yu-Lin Jiang; Yuan-Guo Zhou (Molecular and Cellular Biochemistry, 2018)

Amendment of water quality standards in China: viewpoint on strategic considerations - Xiaoli Zhao; Hao Wang; Zhi Tang; Tianhui Zhao; Ning Qin; Huixian Li; Fengchang Wu; John P. Giesy (Environmental Science and Pollution Research, 2018)

Endosymbiont CLS-HI plays a role in reproduction and development of Haemaphysalis longicornis - Chun-Mian Zhang; Ning-Xin Li; Tian-Tian Zhang; Zhao-Xi Qiu; Yuan Li; Li-Wu Li; Jing-Ze Liu (Experimental and Applied Acarology, 2017)

Association between SSR markers and fibre traits in sea island cotton (Gossypium barbadense) germplasm resources - QI MA; JING ZHAO; HAI LIN; XINZHU NING; PING LIU; FUJUN DENG; AIJUN SI; JILIAN LI (Journal of Genetics, 2017)

Mapping stripe rust resistance gene YrZH22 in Chinese wheat cultivar Zhoumai 22 by bulked segregant RNA-Seq (BSR-Seq) and comparative genomics analyses - Yong Wang; Jingzhong Xie; Huaizhi Zhang; Bingmin Guo; Shunzong Ning; Yongxing Chen; Ping Lu; Qiuhong Wu; Miaomiao Li; Deyun Zhang; Guanghao Guo; Yan Zhang; et al. (Theoretical and Applied Genetics, 2017)

Erratum to: Role of dopamine projections from ventral tegmental area to nucleus accumbens and medial prefrontal cortex in reinforcement behaviors assessed using optogenetic manipulation - Xiao Han; Man-yi Jing; Tai-yun Zhao; Ning Wu; Rui Song; Jin Li (Metabolic Brain Disease, 2017)

Role of dopamine projections from ventral tegmental area to nucleus accumbens and medial prefrontal cortex in reinforcement behaviors assessed using optogenetic manipulation - Xiao Han; Man-yi Jing; Tai-yun Zhao; Ning Wu; Rui Song; Jin Li (Metabolic Brain Disease, 2017)

Association of ABCB1 promoter methylation with aspirin exposure, platelet function, and clinical outcomes in Chinese intracranial artery stenosis patients - Xingang Li; Kun Zhao; Ning Ma; Shusen Sun; Zhongrong Miao; Zhigang Zhao (European Journal of Clinical Pharmacology, 2017)

Diabetic nephropathy: serum miR-9 confers a poor prognosis in and is associated with level changes of vascular endothelial growth factor and pigment epithelium-derived factor - Yanxin Xiao; Shuqin Guo; Yunliang Zhang; Zhiying Bian; Liyan Jia; Yanyun Hu; Jie Chen; Chao Yin; Ning Li; Dongxun Zhang; Xincui Zhao; Jun Wang (Biotechnology Letters, 2017)

Mechanism of Lycium barbarum polysaccharides on primary cultured rat hippocampal neurons - Peng Zhao; Ning-Tian Ma; Ren-Yuan Chang; Yu-Xiang Li; Yin-Ju Hao; Wen-Li Yang; Jie Zheng; Yang Niu; Tao Sun; Jian-Qiang Yu (Cell and Tissue Research, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Paeonol protects against TNF-α-induced proliferation and cytokine release of rheumatoid arthritis fibroblast-like synoviocytes by upregulating FOXO3 through inhibition of miR-155 expression - Ning Liu; Xue Feng; Wenbo Wang; Xingkai Zhao; Xia Li (Inflammation Research, 2017)

Retrospective analysis of 55 twin neonates with haemolytic disease of the newborn - Hu Zhao; Bijuan Li; Ning Li; Yamei Shen; Kailiang Liu; Xiangwu Shu; Cheng Mei; Lanlan Tang (Immunologic Research, 2017)

Isolation and characterization of regulators involved in PHOT1-mediated inhibition of hypocotyl phototropism in Arabidopsis - Qing-Ping Zhao; Xiang Zhao; Zi-Yi Zhu; Xi-ning Guo; Nan-Nan Li; Xiao Zhang (Biologia, 2017)

Recombinant heat shock protein 78 enhances enterovirus 71 propagation in Vero cells and is induced in SK-N-SH cells during the infection - Bing Zhu; Tiantian Xu; Zhengfang Lin; Changbing Wang; Yinghua Li; Mingqi Zhao; Liang Hua; Misi Xiao; Ning Deng (Archives of Virology, 2017)

A new phenol glycoside from Physalis angulata - Cheng-Peng Sun; Xiu-Fang Nie; Ning Kang; Feng Zhao; Li-Xia Chen; Feng Qiu (Natural Product Research, 2017)

Antidepressant-Like and Anxiolytic-Like Effects of ZBD-2, a Novel Ligand for the Translocator Protein (18 kDa) - Dong-sheng Wang; Jing Han; Shuo Li; Ting Sun; Yan-yan Guo; Wen-bo Kang; Zhen Tian; Jian-ning Zhao; Gang Liu; Shui-bing Liu; Ming-gao Zhao (NeuroMolecular Medicine, 2017)

Estrogen-like neuroprotection of isopsoralen against spinal cord injury through estrogen receptor ERα - Xiao-ming Li; Qi Yang; Xu-bo Li; Qiang Cheng; Kun Zhang; Jing Han; Jian-ning Zhao; Gang Liu; Ming-gao Zhao (Metabolic Brain Disease, 2017)

The transgenic expression of human follistatin-344 increases skeletal muscle mass in pigs - Fei Chang; Rui Fang; Meng Wang; Xin Zhao; Wen Chang; Zaihu Zhang; Ning Li; Qingyong Meng (Transgenic Research, 2017)

Inhibitory effect of Shenqi Fuzheng injection combined with docetaxel on lung cancer cells - Bo-yu Dong; Cheng Wang; Li Tan; Ning Tan; Meng-di Zhao; Yang Lu; Shou-ying Du (Journal of Zhejiang University-SCIENCE B, 2017)

New Labdane diterpenes from Hedychium yunnanense with cytotoxicity and inhibitory effects on nitric oxide production - Yu-Peng Li; Si-Meng Zhao; Jun-Ju Xu; Guang-Zhi Zeng; Yan Li; Ning-Hua Tan; Ye Yang (Natural Product Research, 2016)

Agmatine Prevents Adaptation of the Hippocampal Glutamate System in Chronic Morphine-Treated Rats - Xiao-Fei Wang; Tai-Yun Zhao; Rui-Bin Su; Ning Wu; Jin Li (Neuroscience Bulletin, 2016)

Characteristics of uranium biosorption from aqueous solutions on fungus Pleurotus ostreatus - Changsong Zhao; Jun Liu; Hong Tu; Feize Li; Xiyang Li; Jijun Yang; Jiali Liao; Yuanyou Yang; Ning Liu; Qun Sun (Environmental Science and Pollution Research, 2016)

Object-based image analysis for mapping geomorphic zones of coral reefs in the Xisha Islands, China - Jingping Xu; Jianhua Zhao; Fang Li; Lin Wang; Derui Song; Shiyong Wen; Fei Wang; Ning Gao (Acta Oceanologica Sinica, 2016)

Risk assessment of dietary exposure to aluminium in the Chinese population - Ning Ma; Zhao-Ping Liu; Da-Jin Yang; Jiang Liang; Jiang-Hui Zhu; Hai-Bin Xu; Feng-Qin Li; Ning Li (Food Additives & Contaminants: Part A, 2016)

Androgenesis, gynogenesis, and parthenogenesis haploids in cucurbit species - Yan-Qi Dong; Wei-Xing Zhao; Xiao-Hui Li; Xi-Cun Liu; Ning-Ning Gao; Jin-Hua Huang; Wen-Ying Wang; Xiao-Li Xu; Zhen-Hai Tang (Plant Cell Reports, 2016)

Impact of genetic polymorphisms related to clopidogrel or acetylsalicylic acid pharmacology on clinical outcome in Chinese patients with symptomatic extracranial or intracranial stenosis - Zhigang Zhao; Xingang Li; Shusen Sun; Shenghui Mei; Ning Ma; Zhongrong Miao; Ming Zhao; Shiqi Peng (European Journal of Clinical Pharmacology, 2016)

Valuation of debris flow mitigation measures in tourist towns: a case study on Hongchun gully in southwest China - Ming-li Chen; Gui-sheng Hu; Ning-sheng Chen; Cun-yao Zhao; Song-jiang Zhao; Da-wei Han (Journal of Mountain Science, 2016)

BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2016)

The effect of immunosuppressive drug cyclosporine A on myeloid-derived suppressor cells in transplanted mice - Chenlu Han; Tingting Wu; Ning Na; Yang Zhao; Weiguo Li; Yong Zhao (Inflammation Research, 2016)

Molecular characterization of different Triticum monococcum ssp. monococcum Glu-A1 m x alleles - H.Y. Li; Z.L. Li; X.X. Zeng; L.B. Zhao; G. Chen; C.L. Kou; S.Z. Ning; Z.W. Yuan; Y.L. Zheng; D.C. Liu; L.Q. Zhang (Cereal Research Communications, 2016)

Atorvastatin inhibits the apoptosis of human umbilical vein endothelial cells induced by angiotensin II via the lysosomal-mitochondrial axis - Ye Chang; Yuan Li; Ning Ye; Xiaofan Guo; Zhao Li; Guozhe Sun; Yingxian Sun (Apoptosis, 2016)

Onset location of scintillation-producing spread-F plume over Sanya - JianChang Zheng; ZhaoGuo Huang; Zhi Wu; XiQing Hao; JiaLun Ji; BaiQi Ning; LianHuan Hu; XiuKuan Zhao; GuoZhu Li (Science China Earth Sciences, 2016)

TNFα-induced M-MDSCs promote transplant immune tolerance via nitric oxide - Fan Yang; Yang Li; Tingting Wu; Ning Na; Yang Zhao; Weiguo Li; Chenlu Han; Lianfeng Zhang; Jun Lu; Yong Zhao (Journal of Molecular Medicine, 2016)

Chicken gga-miR-130a targets HOXA3 and MDFIC and inhibits Marek’s disease lymphoma cell proliferation and migration - Bo Han; Ling Lian; Xin Li; Chunfang Zhao; Lujiang Qu; Changjun Liu; Jiuzhou Song; Ning Yang (Molecular Biology Reports, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Quantitative proteomics reveals an important role of GsCBRLK in salt stress response of soybean - Wei Ji; Jin Koh; Sheng Li; Ning Zhu; Craig P. Dufresne; Xiaowen Zhao; Sixue Chen; Jing Li (Plant and Soil, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Coordinated pattern of multi‐element variability in leaves and roots across C hinese forest biomes - Ning Zhao; Guirui Yu; Nianpeng He; Qiufeng Wang; Dali Guo; Xinyu Zhang; Ruili Wang; Zhiwei Xu; Cuicui Jiao; Nani Li; Yanlong Jia (Global Ecology and Biogeography, 2016)
Aim The elemental composition of plants is of fundamental importance for plant physiology and biogeochemical cycling. Knowledge about how the pattern of multi‐element variability is coordinated between above‐ and below‐ground organs remains limited. Here, we quantify multi‐element variability in the leaves and roots of terrestrial plants, in addition to trying to understand its taxonomic and environmental regulation at large scales. Location C hina. Methods Sixteen elements in the leaves and fine roots of 792 plant species across nine forests located along the north–south transect of eastern C hina were measured. General linear mixed models were used to partition taxonomic and environmental variation. Canonical discriminant analyses were conducted to identify elements with the highest discriminatory power for different plant orders. Results Elemental composition differed significantly between the leaves and roots, with the roots containing higher concentrations of trace metal elements (aluminium, iron, sodium, zinc, copper, lead, nickel and cobalt). A coordinated pattern of multi‐element variability and similar taxonomic regulation was observed between the leaves and roots of terrestrial plants. That is, elements with higher internal concentrations were less variable, with most of the variability being attributed to taxonomic effects rather than the environment. Main conclusions Taxonomic and environmental regulation differed for different elements. Compared with microelements, macroelements exhibited a narrow range of internal concentrations, less environmental control and stronger taxonomic conservatism. The coordinated pattern of multi‐element variability and similar taxonomic effects in the leaves and roots implies that above‐ and below‐ground ecological processes are tightly linked.

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Morphological study of Ophidascaris excavata Hsü & Hoeppli, 1931 (Ascaridida: Ascarididae) from Gloydius brevicaudus (Stejneger) (Reptilia: Viperidae) - Liang Li; Wen-Ting Zhao; Hui-Xia Chen; Yan-Ning Guo; Lu-Ping Zhang (Systematic Parasitology, 2016)

Ultrastructure of Ascaridia galli (Schrank, 1788) (Nematoda: Ascaridida) from the endangered green peafowl Pavo muticus Linnaeus (Galliformes: Phasianidae) - Ting Zhao; Yan-Ning Guo; Lu-Ping Zhang; Liang Li (Acta Parasitologica, 2016)
Ascaridia galli (Schrank, 1788) is a common parasite of various galliform birds worldwide. Although A. galli has been extensively studied by many author, knowledge of the morphology of this species in detail is still insufficient. In the present paper, the detailed morphology of A. galli was further studied using light and scanning electron microscopy, based on specimens collected from the endangered green peafowl Pavo muticus Linnaeus (Galliformes: Phasianidae) in China. The results revealed some erroneous and previously unreported morphological features, including the lips lacking real denticles, the lateral alae beginning at some distance posterior to the base of the ventrolateral lips and the caudal papillae with 4 different morphotypes. The present morphological and morphometric data complement previous descriptions and enable us to recognize this species more precisely.

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

ALDH2*2 Allele is a Negative Risk Factor for Cerebral Infarction in Chinese Women - Qiao-Yan Li; Ning-Min Zhao; Jian-Jun Ma; Hong-Fei Duan; Yong-Cheng Ma; Wei Zhang; Hong-Wei Zhao; Yu-Hua Qin (Biochemical Genetics, 2015)

Characterization of important odorants in four steamed Coilia ectenes from China by gas chromatography–mass spectrometry–olfactometry - Lin-min Zhao; Wei Wu; Ning-ping Tao; Yu-qi Li; Na Wu; Xiao Qin (Fisheries Science, 2015)

Isolation of differentially expressed sex genes in garden asparagus using suppression subtractive hybridization - Chuan-liang Deng; Ning-na Wang; Shu-fen Li; Tian-yu Dong; Xin-peng Zhao; Shao-jing Wang; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2015)

CD33 rs3865444 Polymorphism Contributes to Alzheimer’s Disease Susceptibility in Chinese, European, and North American Populations - Xingwang Li; Ning Shen; Shuyan Zhang; Jiafeng Liu; Qinghua Jiang; Mingzhi Liao; Rennan Feng; Liangcai Zhang; Guangyu Wang; Guoda Ma; Haihong Zhou; Zugen Chen; et al. (Molecular Neurobiology, 2015)

Two new species of the genus Micromonospora: Micromonospora palomenae sp. nov. and Micromonospora harpali sp. nov. isolated from the insects - Baozhu Fang; Chongxi Liu; Xuejiao Guan; Jia Song; Junwei Zhao; Hui Liu; Chuang Li; Wenxi Ning; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2015)

An Updated Analysis with 85,939 Samples Confirms the Association Between CR1 rs6656401 Polymorphism and Alzheimer’s Disease - Ning Shen; Bin Chen; Yongshuai Jiang; Rennan Feng; Mingzhi Liao; Liangcai Zhang; Fujun Li; Guoda Ma; Zugen Chen; Bin Zhao; Keshen Li; Guiyou Liu (Molecular Neurobiology, 2015)

Near infrared radiation rescues mitochondrial dysfunction in cortical neurons after oxygen-glucose deprivation - Zhanyang Yu; Ning Liu; Jianhua Zhao; Yadan Li; Thomas J. McCarthy; Clark E. Tedford; Eng H. Lo; Xiaoying Wang (Metabolic Brain Disease, 2015)

Bacterial community composition at anodes of microbial fuel cells for paddy soils: the effects of soil properties - Ning Wang; Zheng Chen; Hong-Bo Li; Jian-Qiang Su; Feng Zhao; Yong-Guan Zhu (Journal of Soils and Sediments, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Reduced expression of starch branching enzyme IIa and IIb in maize endosperm by RNAi constructs greatly increases the amylose content in kernel with nearly normal morphology - Yajie Zhao; Ning Li; Bei Li; Zhaoxia Li; Guangning Xie; Juren Zhang (Planta, 2015)

Aspect-vegetation complex effects on biochemical characteristics and decomposability of soil organic carbon on the eastern Qinghai-Tibetan Plateau - Ning-Ning Zhao; Georg Guggenberger; Olga Shibistova; Dao Thi Thao; Wen Jing Shi; Xiao Gang Li (Plant and Soil, 2014)

Calcitonin Gene-Related Peptide Inhibits Osteolytic Factors Induced by Osteoblast In Co-Culture System with Breast Cancer - Hui Zhao; Lin-lin Ning; Zhi-yu Wang; Hong-tao Li; Dan Qiao; Yang Yao; Huan-long Qin (Cell Biochemistry and Biophysics, 2014)

Hsa-miR-1246, hsa-miR-320a and hsa-miR-196b-5p inhibitors can reduce the cytotoxicity of Ebola virus glycoprotein in vitro - MiaoMiao Sheng; Ying Zhong; Yang Chen; JianChao Du; XiangWu Ju; Chen Zhao; GuiGen Zhang; LiFang Zhang; KangTai Liu; Ning Yang; Peng Xie; DangSheng Li; et al. (Science China Life Sciences, 2014)

Blockade of PKCβ protects against remote organ injury induced by intestinal ischemia and reperfusion via a p66shc-mediated mitochondrial apoptotic pathway - Guangzhi Wang; Zhao Chen; Feng Zhang; Huirong Jing; Wei Xu; Shili Ning; Zhenlu Li; Kexin Liu; Jihong Yao; Xiaofeng Tian (Apoptosis, 2014)

Migration of Ti from nano-TiO 2 -polyethylene composite packaging into food simulants - Qin-Bao Lin; He Li; Huai-Ning Zhong; Quan Zhao; Da-Hui Xiao; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Supplementation transgenic cow’s milk containing recombinant human lactoferrin enhances systematic and intestinal immune responses in piglets - Qiuling Li; Wenping Hu; Jie Zhao; Jianwu Wang; Yunping Dai; Yaofeng Zhao; Qingyong Meng; Ning Li (Molecular Biology Reports, 2014)

Ground-based platforms for space radiation research at the Institute of Modern Physics - Dan Xu; Tingting Liu; He Li; Junrui Hua; Xin Zhao; Ning Tian; Jufang Wang; Guangming Zhou (Rendiconti Lincei. Scienze Fisiche e Naturali, 2014)

Cotransplantation of human umbilical cord-derived mesenchymal stem cells and umbilical cord blood-derived CD34+ cells in a rabbit model of myocardial infarction - Tong Li; Qunxing Ma; Meng Ning; Yue Zhao; Yuelong Hou (Molecular and Cellular Biochemistry, 2014)

Modeling study of regional severe hazes over mid-eastern China in January 2013 and its implications on pollution prevention and control - ZiFa Wang; Jie Li; Zhe Wang; WenYi Yang; Xiao Tang; BaoZhu Ge; PinZhong Yan; LiLi Zhu; XueShun Chen; HuanSheng Chen; Wei Wand; JianJun Li; et al. (Science China Earth Sciences, 2014)

Coevolution of brachiopod paleobiogeography and tectonopaleogeography during the late Paleozoic in Central Asia - ChengWen Wang; GuoWei Zhao; Ning Li; Pu Zong (Science China Earth Sciences, 2013)

Generation of c-Myc transgenic pigs for autosomal dominant polycystic kidney disease - Jianhua Ye; Jin He; Qiuyan Li; Yuanyuan Feng; Xueyuan Bai; Xiangmei Chen; Yaofeng Zhao; Xiaoxiang Hu; Zhengquan Yu; Ning Li (Transgenic Research, 2013)

Mechanism of random integration of foreign DNA in transgenic mice - Bo-Wen Yan; Yao-Feng Zhao; Wen-Guang Cao; Ning Li; Ke-Mian Gou (Transgenic Research, 2013)

Partial AZFc duplications not deletions are associated with male infertility in the Yi population of Yunnan Province, China - Jun-jie Ye; Li Ma; Li-juan Yang; Jin-huan Wang; Yue-li Wang; Hai Guo; Ning Gong; Wen-hui Nie; Shu-hua Zhao (Journal of Zhejiang University-SCIENCE B, 2013)

Sequence analysis of the whole genome of a recombinant Marek’s disease virus strain, GX0101, with a reticuloendotheliosis virus LTR insert - Shuai Su; Ning Cui; Aijun Sun; Yanpeng Li; Jiabo Ding; Zimeng Chen; Peng Zhao; Zhizhong Cui (Archives of Virology, 2013)

Genome-scale gene expression characteristics define the follicular initiation and developmental rules during folliculogenesis - Kerong Shi; Feng He; Xuefeng Yuan; Yaofeng Zhao; Xuemei Deng; Xiaoxiang Hu; Ning Li (Mammalian Genome, 2013)

Construction of a transgenic pig model overexpressing polycystic kidney disease 2 (PKD2) gene - Jin He; Jianhua Ye; Qiuyan Li; Yuanyuan Feng; Xueyuan Bai; Xiangmei Chen; Changxin Wu; Zhengquan Yu; Yaofeng Zhao; Xiaoxiang Hu; Ning Li (Transgenic Research, 2013)

miR-30a downregulation aggravates pressure overload-induced cardiomyocyte hypertrophy - Xuesong Yin; Chenghai Peng; Wenhu Ning; Chunyan Li; Zhongqiao Ren; Jihong Zhang; Han Gao; Kan Zhao (Molecular and Cellular Biochemistry, 2013)

Chemistry, bioactivity and quality control of Dendrobium, a commonly used tonic herb in traditional Chinese medicine - Jun Xu; Quan-Bin Han; Song-Lin Li; Xiao-Jia Chen; Xiao-Ning Wang; Zhong-Zhen Zhao; Hu-Biao Chen (Phytochemistry Reviews, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Retrieval of atmospheric and land surface parameters from satellite-based thermal infrared hyperspectral data using a neural network technique - Ning Wang; Zhao-Liang Li; Bo-Hui Tang; Funian Zeng; Chuanrong Li (International Journal of Remote Sensing, 2013)

Land surface emissivity retrieval from satellite data - Zhao-Liang Li; Hua Wu; Ning Wang; Shi Qiu; José A. Sobrino; Zhengming Wan; Bo-Hui Tang; Guangjian Yan (International Journal of Remote Sensing, 2013)

Strategy for pH control and pH feedback-controlled substrate feeding for high-level production of l-tryptophan by Escherichia coli - Li-Kun Cheng; Jian Wang; Qing-Yang Xu; Chun-Guang Zhao; Zhi-Qiang Shen; Xi-Xian Xie; Ning Chen (World Journal of Microbiology and Biotechnology, 2013)

Immune responses induced in HHD mice by multiepitope HIV vaccine based on cryptic epitope modification - Yinghui Li; Yuxiao Huang; Jiao Liang; Zhikai Xu; Yan Shen; Ning Zhang; Zhongxiang Liu; Ya Zhao (Molecular Biology Reports, 2013)

Discordant genotypic resistance and HIV-1 genetic diversity from paired plasma and cerebrospinal fluid samples in Chinese settings - Lifeng Liu; Yulin Zhang; Feili Wei; Qingxia Zhao; Xicheng Wang; Lin Yuan; Ning Li; Dexi Chen (Journal of NeuroVirology, 2013)

Disruption of the transcription factor RBP-J results in osteopenia attributable to attenuated osteoclast differentiation - Jing Ma; Ya-Li Liu; Yi-Yang Hu; Ya-Ning Wei; Xing-Cheng Zhao; Guang-Ying Dong; Hong-Yan Qin; Yin Ding; Hua Han (Molecular Biology Reports, 2013)

Secondary metabolites from Marchantia paleacea calluses and their allelopathic effects on Arabidopsis seed growth - Lei Wang; Li-Ning Wang; Yu Zhao; Hong-Xiang Lou; Ai-Xia Cheng (Natural Product Research, 2013)

Seismic response analysis of road vehicle-bridge system for continuous rigid frame bridges with high piers - Yongle Li; Ning Chen; Kai Zhao; Haili Liao (Earthquake Engineering and Engineering Vibration, 2012)

Functional recombinant human anti-HBV antibody expressed in milk of transgenic mice - Ran Zhang; Dan Cui; Hong Wang; Chuan Li; Xin Yao; Yaofeng Zhao; Mifang Liang; Ning Li (Transgenic Research, 2012)

Different effects of omega-3 fatty acids on the cell cycle in C2C12 myoblast proliferation - Yunqian Peng; Yu Zheng; Yunsheng Zhang; Jie Zhao; Fei Chang; Tianyu Lu; Ran Zhang; Qiuyan Li; Xiaoxiang Hu; Ning Li (Molecular and Cellular Biochemistry, 2012)

An initial screening for HIV-associated neurocognitive disorders of HIV-1 infected patients in China - Yulin Zhang; Luxin Qiao; Wei Ding; Feili Wei; Qingxia Zhao; Xicheng Wang; Ying Shi; Ning Li; Davey Smith; Dexi Chen (Journal of NeuroVirology, 2012)

Polymorphisms in chicken extracellular fatty acid binding protein gene - Zhi-yuan Zhao; Li Zhang; Bing-wang Du; Ning-xian Cao; Xin-sheng Jiang; Wen-xia Tian; Shu-jun Li; Wei-wei Wu; Chang-hui Ye (Molecular Biology Reports, 2012)

Inhibition of porcine reproductive and respiratory syndrome virus replication by RNA interference in MARC-145 cells - Yonghua Bao; Yongchen Guo; Liying Zhang; Zhihui Zhao; Ning Li (Molecular Biology Reports, 2012)

Molecular-based environmental risk assessment of three varieties of genetically engineered cows - Jianxiang Xu; Jie Zhao; Jianwu Wang; Yaofeng Zhao; Lei Zhang; Mingxing Chu; Ning Li (Transgenic Research, 2011)

Characterization of the MHC class II α-chain gene in ducks - Liming Ren; Zhi Yang; Tao Wang; Yi Sun; Ying Guo; Ziding Zhang; Jing Fei; Yonghua Bao; Tong Qin; Jing Wang; Yinhua Huang; Xiaoxiang Hu; et al. (Immunogenetics, 2011)

Effects of SLCO1B1 polymorphisms on the pharmacokinetics and pharmacodynamics of repaglinide in healthy Chinese volunteers - Jiake He; Zhixia Qiu; Ning Li; Yang Yu; Yang Lu; Deen Han; Tingting Li; Di Zhao; Wei Sun; Fang Fang; Jianheng Zheng; Hongwei Fan; et al. (European Journal of Clinical Pharmacology, 2011)

Cis-cinnamic acid-enhanced 1 gene plays a role in regulation of Arabidopsis bolting - Di Guo; Wai Shing Wong; Wen Zhao Xu; Fei Fei Sun; Dong Jin Qing; Ning Li (Plant Molecular Biology, 2011)

Over-expression of AGPase genes enhances seed weight and starch content in transgenic maize - Ning Li; Shujuan Zhang; Yajie Zhao; Bei Li; Juren Zhang (Planta, 2011)

Expression of Pdx1 mediates differentiation from mesenchymal stem cells into insulin-producing cells - Huijuan Yuan; Jie Li; Ning Xin; Zhigang Zhao; Guijun Qin (Molecular Biology Reports, 2010)

Characterization of a novel wheat NAC transcription factor gene involved in defense response against stripe rust pathogen infection and abiotic stresses - Ning Xia; Gang Zhang; Xin-Ying Liu; Lin Deng; Gao-Lei Cai; Yi Zhang; Xiao-Jie Wang; Jie Zhao; Li-Li Huang; Zhen-Sheng Kang (Molecular Biology Reports, 2010)

Chemical constituents of Gentiana macrophylla Pall. - Zhi-Bo Jiang; Hong-Li Liu; Xiao-Qing Liu; Ji-Ning Shang; Jia-Rui Zhao; Cheng-Shan Yuan (Natural Product Research, 2010)

Could protein tertiary structure influence mammary transgene expression more than tissue specific codon usage? - Zuyong He; Yiqiang Zhao; Gui Mei; Ning Li; Yaosheng Chen (Transgenic Research, 2010)

Epidemiological study of human calicivirus infection in children with gastroenteritis in Lanzhou from 2001 to 2007 - Wei-xia Cheng; Xin-hua Ye; Xue-mei Yang; Yu-ning Li; Miao Jin; Yu Jin; Zhao-jun Duan (Archives of Virology, 2010)

Synthesis of cyclopropane fatty acid and its effect on freeze-drying survival of Lactobacillus bulgaricus L2 at different growth conditions - Chun Li; Jia-Liang Zhao; Yu-Tang Wang; Xu Han; Ning Liu (World Journal of Microbiology and Biotechnology, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Comparison of human post-embryonic, multipotent stem cells derived from various tissues - Baijun Fang; Ning Li; Yongping Song; Quande Lin; Robert Chunhua Zhao (Biotechnology Letters, 2009)

Cloning and characterization of class 1 and class 2 insulin-like growth factor-I mRNA in Songliao black pig - Shuqi Xiao; Shuang Li; Jiabao Zhang; Shumin Zhang; Lisheng Dai; Yonghua Bao; Ning Jiang; Yan Gao; Zhongli Zhao; Delin Mo; Yaosheng Chen; Zhihui Zhao (Molecular Biology Reports, 2009)

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)

High level expression of a functional human/mouse chimeric anti-CD20 monoclonal antibody in milk of transgenic mice - Bo Tang; Shanshan Yu; Min Zheng; Fangrong Ding; Rui Zhao; Jianmin Zhao; Yunping Dai; Ning Li (Transgenic Research, 2008)

The effects of inflammatory cytokines on steroidogenic acute regulatory protein expression in macrophages - Y. Ma; S. Ren; W. M. Pandak; X. Li; Y. Ning; C. Lu; F. Zhao; L. Yin (Inflammation Research, 2007)

Remote wireless transmission and error recovery of log data - Yipeng Zhao; Ning Li; Caizhi Wang (Applied Geophysics, 2007)

Self-organized Polymer Aggregates with a Biomimetic Hierarchical Structure and its Superhydrophobic Effect - Ning Zhao; Xiao-Yan Zhang; Yan-Fang Li; Xiao-Ying Lu; Si-Lu Sheng; Xiao-Li Zhang; Jian Xu (Cell Biochemistry and Biophysics, 2007)

UCP2 and 3 Deletion Screening and Distribution in 15 Pig Breeds - Yanhua Li; Hanjie Li; Xingbo Zhao; Ning Li; Changxin Wu (Biochemical Genetics, 2007)

Fine mapping of S32(t), a new gene causing hybrid embryo sac sterility in a Chinese landrace rice (Oryza sativa L.) - Danting Li; Liangming Chen; Ling Jiang; Susong Zhu; Zhigang Zhao; Shijia Liu; Ning Su; Huqu Zhai; Hiroshi Ikehashi; Jianmin Wan (Theoretical and Applied Genetics, 2007)

Comparative Analysis of the Prion Protein Open Reading Frame Nucleotide Sequences in Peacock and Parakeet - Jian-Min Yang; De-Ming Zhao; Hong-Xiang Liu; Ning Li; Yong-Xin Hao; Zhang-Yong Ning; Xiu-Hui Qin (Virus Genes, 2005)

HLA polymorphisms are associated with Helicobacter pylori infected gastric cancer in a high risk population, China - Zhaohui Li; Dafang Chen; Chunfeng Zhang; Yong Li; Bangwei Cao; Tao Ning; Yiming Zhao; Weicheng You; Yang Ke (Immunogenetics, 2005)

Analysis of libraries encoded with GC tags: Compound elution, tag decode analysis, and statistical sampling analysis - Roland E. Dolle; Joan Guo; Wenni Li; Ning Zhao; James A. Connelly (Molecular Diversity, 2000)